Thermal kinetics of biochar-ethylene vinyl acetate for waste-to-energy: Particle swarm optimization, cloud computing, and artificial intelligence - Wei-Hsin Chen; Che-An Lin; Partha Pratim Biswas; Chih-Chun Chen; Biqing Liang; Sheng-Lun Lin; Hwai Chyuan Ong; Aristotle T. Ubando (Fuel, 2026)

Combined targeting poly (ADP-ribose) polymerase and receptor tyrosine kinase inhibits ovarian clear cell carcinoma progression through disrupted ribosome biogenesis - Chiao-Yun Lin; An-Shine Chao; Angel Chao; Ren-Chin Wu; Alice L. Yu; Chiung-Hui Fu; Yu-Chuan Teng; Ruby Yun-Ju Huang; Chyong-Huey Lai (Journal of Molecular Medicine, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Correction to: Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Development of an isoform-discriminating RT-qPCR assay for transcript-level profiling of human ASAH2 in colorectal cancer cell models - You Shan Ngui; Yi-Wen Huang; Shao-Chi Hung; Shih-Han Huang; Chieh-Ju Wen; Yi-An Chang; Hsing-Chen Wu; Hsiu-Chuan Chan; Mei-Lin Chan; Liang-Yin Ke; Hua-Chen Chan (Molecular Biology Reports, 2026)

Unlocking the Size-Dependent mechanism of CO2 reduction on Carbon-Supported Nin clusters - Yimeng Sun; Lin Tao; Meixu Lu; Xin Quan; Mingjie Wu; Javed Rehman; Nan Wang; Lixiang Li; Baigang An (Fuel, 2026)

Chronic paternal exposure to low-dose OBS reprograms progeny's intestinal cholesterol metabolism and increases IBD susceptibility - Wang Yang; Yongsheng Teng; Zeyu Yang; Xiaomei Song; Le He; Yan Liu; Wei Tan; Huihui An; Ping Shi; Chaoqun Hu; Lin Ao; Hong Guo (Environmental Pollution, 2026)

Engineered bacteria as ultrasound-responsive carbon monoxide vehicles for Cancer gas therapy and synergistic immunotherapy - Xiaorui Chen; Xiao Xiao; Wei Zhao; Bin Liu; Hongzhou Lian; He Ding; Piaoping Yang; Ping'an Ma; Lingjie Song; Shifang Luan; Ziyong Cheng; Jun Lin (Chemical Engineering Journal, 2026)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

Vision-based autonomous leaf-level spraying using wrist-inspired manipulators for integrated pest management in papaya greenhouses - Nhu Tuong An Nguyen; Dang Khanh Linh Le; Wei-Chih Lin (Computers and Electronics in Agriculture, 2026)

Revealing spatiotemporal patterns of metro tidal ridership and their relationships with TOD features: A dual-sequence clustering and explainable machine learning approach - Rui An; Zhaomin Tong; Xiping Yang; Yaping Wang; Ying Jing; Yaolin Liu; Lin Luo; Jiayu Liu (Travel Behaviour and Society, 2026)

Chemical-free closed-loop conversion of nitrate into struvite fertilizer via exsolved high-entropy perovskite electrocatalyst - Li-Hui Yang; Yi-Heng Liu; Si-Hao Lv; Man-Ting Liao; Hui Lin; Wei Li; Cao Yang; An-Qi Wang; Hao-Yi Cheng (Journal of Environmental Chemical Engineering, 2026)

Thermal evolution of biomarker profiles in the Ordovician biodegraded reservoirs of the Tabei Uplift, Tarim Basin, northwestern China: implications from closed-system thermal simulation experiments - Yuwei Yang; Yuhong Liao; Yijun Zheng; Yueyi Huang; Bin Cheng; Huanyu Lin; Yunpeng Wang; Ping’An Peng (Journal of Asian Earth Sciences, 2026)

Metal-polyphenol network-coated probiotic microcapsules: Enhancing Limosilactobacillus fermentum storage stability and yogurt characteristics - Yi-han Cai; Fang Huang; Si-ying Yan; Xiao-jin Lin; Shu-ling Huang; Shao-fu Feng; Jie-ying Chen; Yan-yan Huang; Xin-An Zeng; Xiang-ze Jia (International Dairy Journal, 2026)

Comprehensive quality profiling and comparative metabolic characterization of seven dominant fresh-eating Chinese olive (Canarium album Lour.) cultivars in Southern China - Lijuan Fu; Wenjing Liu; Yuying Xu; Xiangxin Lin; Jia Guo; Hao Chen; Jianwei Fu; Sun'an Yan (Food Chemistry, 2026)

Triazine and other herbicides in sediments of lower Laurentian Great Lakes – pre- and post-depositional mobility and in-situ degradation - Shanshan Zhou; Huan He; Tian Lin; Jiehong Guo; Xiusen Yang; Xinyue Jia; Neil C. Sturchio; Karl J. Rockne; John P. Giesy; An Li (Environmental Pollution, 2026)

Application of mass-balance modeling to assess the ecosystem effects of dam removal on the restoration of the Formosan landlocked salmon (Oncorhynchus masou formosanus) - An-Cheng Lin; Hsing-Juh Lin (Ecological Engineering, 2026)

Green-engineered superhydrophobic and photothermal CuO nanofiber membranes for solar-assisted membrane distillation - Jiaxin Guo; Shangzhen Xie; Jiawei Sun; Pengfei Lin; Xinping He; Zhenyao Wang; Chunhai Yi; Alicia Kyoungjin An (Desalination, 2026)

Corrigendum to “flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction” [Chem. Eng. J. 521 (2025) 166451] - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2026)

Hierarchically ordered 2D/1D Bi2O2S/Bi2S3 heterostructure enabled by topotactic transformation for ppb-level NO sensing under humid conditions - Chenda Wei; Shixin Huang; Wei Liu; Hailong Lin; Zhicheng Wen; Chunjin Hang; Rong An (Chemical Engineering Journal, 2026)

Salivary Mycobiome and Metabolomic Profiles in HIV-Infected Men Who Have Sex with Men: An Exploratory Study - Lu Lin; Miao Zhang; Meilin Guan; Si Chen; Yan Wang; Jie Cao; Wei An; Ying Guo (Current Microbiology, 2026)

Efficiently photocatalytic synthesis of a special dye intermediate with CO2 for preparing a disperse dye SCFM-ANCY suitable for supercritical coloration of bio-based fibers - Yang-Sheng Zhou; An-Tong Liu; Yi-Wei Shi; Lin Xie; Jia-Jie Long (Process Safety and Environmental Protection, 2026)

S-methoprene affected the population growth of Ephestia elutella (Hübner) - Lin-chong An; Xiao-fei Yu; Si-qi Wan; Mao-fa Yang (Journal of Stored Products Research, 2026)

Microplastic-derived dissolved organic matter is associated with increased N2O emissions and altered denitrification-related microbial signatures in constructed wetlands - Yong Lin; Dianpeng Li; Mengshuo Liu; Teng Wen; Xuebin Lu; Jun Chen; Shuqing An (Journal of Hazardous Materials, 2026)

Root exudates recruit microbial allies to override their own mobilization effects for cadmium immobilization in intercropped rice - Ye Li; Jie Hou; Mengqi Liu; Hongan Chen; Xinyi Wang; Peizhe Sun; Lin Zhao; Yanpo Yao; Zhaolin Du; Yi An (Journal of Hazardous Materials, 2026)

Dynamics simulation on microstructural properties evolution of high-alkali coal slag in reducing conditions: The roles of alkali oxide, alkaline earth oxides, and iron oxide - Guowei Ma; Junyan Gu; Maoyun Luo; Chang’an Wang; Jiamiao Liu; Yonggang Zhao; Lin Zhao; Limin Wang; Wanzhu Wu; Hu Wang; Defu Che (Fuel, 2026)

PhenolFingerprint DB: an open-access platform for phenolic fingerprinting, quantification, and automated species authentication, validated on 93 floral and herbal plants - Tingwei Li; Xiaodong Liu; Xu Jin; Quanying Sun; Yulu Wang; Lin Yang; Yesong Zhang; Wenlong Wei; Hua Qu; Qirui Bi; Ping Li; Xiangmei Chen; et al. (Food Chemistry, 2026)

The effect of thermal ultrasonic treatment on the interaction between tea polyphenols and goat milk proteins at different ratios - Nanqi Zhao; Yutong Ma; Xiaosong Feng; Wenbang An; Xin Wang; Lin Chen; Qingkun Zeng; Ling Li; Xianchao Feng (Food Chemistry, 2026)

Rural domestic waste generation characteristics and treatment-related greenhouse gas emissions: A case study of Guangdong Province, China - Yao He; Jie Zhang; Chen Lin; Linlin Xia; Yazhuo Wang; Hewen Zhou; Xun-an Ning (Environmental Pollution, 2026)

Steering catalytic pathways via nanoconfinement-tuned d-band centers in Fe clusters - Hong-Lin Zhang; An-Qi Kang; Hai-Yin Xu; Wei-Ping Xiong; Hai-Hao Peng; Yuan-Ling Luo; Mei-Ying Jia; Zhao-Hui Yang (Chemical Engineering Journal, 2026)

Piezo-coupled triboelectric self-powered tactile sensor based on a self-healable polymer for object recognition - Manikandan Venkatesan; Wei-Wen Chen; Yu-Chen Wang; Yung-Chi Hsu; Jayashree Chandrasekar; Hao-Yuan Chen; Shih-Yu Lin; Chia-Jung Cho; Shang-Jui Huang; Ming-An Chung; Wen-Ya Lee; Yu Wen; et al. (Chemical Engineering Journal, 2026)

Constructing hydrophobic carbon-encapsulated Fe5C2 catalysts for enhanced Fischer-Tropsch synthesis to olefins with reduced CO2 selectivity - Ranqing Zhang; Xuan Zhou; Derun Li; Kun Gong; Yunlei An; Jing Xin; Peipei Zhang; Yanfang Song; Yuanyuan Dai; Tiejun Lin; Liangshu zhong (Chemical Engineering Journal, 2026)

Myeloid-derived suppressor cells-guided mesoporous silica nanoplatform delivering a BET inhibitor exerts anticancer effects by reprogramming the immunosuppressive tumor microenvironment - Li-Chan Chang; Li Xu; Yin-Fen Liu; Chang-An Lin; Si-Han Wu; Wen-Pin Su (Chemical Engineering Journal, 2026)

Go north: Isotope and aDNA analysis reconstructing the life history of a first-generation immigrant in the early Western Zhou Yan state - Xinyi Ouyang; Nina An; Jing Wang; Chen Duan; Yingliang Yang; YiHsien Lin; Chao Ning; Jingning Guo; Xiaohong Wu (Archaeological and Anthropological Sciences, 2026)

Phylogeny and taxonomic revisions of Piper (Piperaceae) in Taiwan - Po-Hao Chen; Chia-Hao Chang; Kuan-Ning Kung; Hung‑Chih Lin; An-Ching Chung; Chia-Ying Ou; Shih-Hui Liu (Journal of Plant Research, 2026)
Taiwan, located at the northernmost extent of Huxley’s Line, marks the furthest point along this biogeographic boundary where exchanges of flora and fauna occur. The genus Piper , a globally distributed and taxonomically complex group of both economic and evolutionary importance, has a convoluted taxonomic history in this transitional zone that requires comprehensive study. Here, we integrate morphological, molecular, and distributional data to revise the taxonomy of Taiwanese Piper , resolve their evolutionary relationships, and infer their biogeographic history. Our revision recognizes 11 species in Taiwan, including seven native taxa, of which three are endemic. The present analysis establishes the first comprehensive phylogenetic framework for Taiwanese Piper and reveals that native species arose from lineages on both sides of Wallace’s Line. Collectively, these findings provide the first evidence of bidirectional expansion within a genus in Taiwan and position Piper as an exemplary system for examining phylogeographic dynamics in transitional biogeographic zones.

Surfactant Regulation of the Solution-Mediated Phase Transformation of Nitrofurantoin Anhydrate to Monohydrate - Zhuangzhuang Chen; Xiyan Wang; An Chen; Lin Li; Zhongting Zhuang; Minshan Guo; Ting Cai (Pharmaceutical Research, 2026)

Water pressure distribution around tunnels in pipeline-type karst and lining response characteristics induced by rainfall - An Pengtao; Fan Lin; Ma Shaokun; Zhang Jiabing; Huang Zhen; Fu Helin (Tunnelling and Underground Space Technology, 2026)

Shifting the processing boundary: On-Farm Pulsed Electric Field Intervention (OFPI) for proactive bioburden reduction and functionalization of raw milk - Bing Yan; Lang-Hong Wang; Jin-Lin Cai; Xiao-Jun Zhang; Cai-Yun Wang; Jian Li; Rui Wang; Xin-An Zeng; Jian He (Trends in Food Science & Technology, 2026)

Unveiling the molecular diversity of toxins and non-toxins in the medicinal sea snake Hydrophis cyanocinctus through integrated venomics investigation - Jiayi Lin; Zhaoran Yu; Yue Cheng; Sheng Han; Ruiwei Ye; Dandan Yang; Xiawen Dang; Haorui Dai; Zhiping Zhao; Yonghong Zhou; Yiming Lu; An Li (Toxicon, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Electrolyte-enabled reversible ICl intercalation in graphite as transition metal-free cathodes - Zhaoheng Ruan; Hao Zhang; Huipeng Zeng; Baichuan Cui; Ruifan Lin; An Phan; Chun Hu; Jijian Xu (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Precise nanodelivery of screened compounds alleviates sepsis-associated encephalopathy by targeting microglial ANXA2 - Daoyi Lin; Yuan Huang; Shuyan Wu; Zefu Li; Hanhao Dai; Fei Gao; Danfeng Wang; Maokai Xu; Ziqi An; Xinmu Li; Peng Ye; Yingjie Chen; et al. (Science Bulletin, 2026)

Argo trajectory-derived current assimilation and its impact on the mid-layer circulation in the South China Sea - Jingyi Liu; Xiaohui Wang; Senliang Bao; Pinqiang Wang; Huizan Wang; Xiang Wang; Conghao Lin; Ciqiang Luo; Yuzhu An (Ocean Modelling, 2026)

Differential thermal sensitivity among shallow-water octocorals and its association with holobiont composition - Hsien-Yu Cheng; Yu-Chien Wang; Yan-Zhen Meng; Chien-Yi Wu; An-Chi Liu; Yen-Chih Lin; Jui-Hsun Hung; Shan-Hua Yang (Marine Environmental Research, 2026)

Seasonal variation of fish biodiversity in Xisha Islands based on dual-marker eDNA metabarcoding - Shengming Deng; Yuguo Ye; Min Liu; Bai-an Lin; Chengdan Ma; Yifeng Xu; Yongcan Zhou; Shifeng Wang; Weiliang Guo; Huilong Ou; Xiang Zhang; Jianlong Li (Marine Environmental Research, 2026)

BmFOXP1 and BmSGF1 divergently cooperate with BmGATAβ4 to regulate vitellogenin expression during vitellogenesis of the silkworm, Bombyx mori - Na Wan; Hongling Liu; Yanan Wu; An Wang; Yingying Mao; Jiayi Liu; Lei Xin; Yong Hou; Ying Lin; Qingyou Xia (Insect Biochemistry and Molecular Biology, 2026)

Engineering an amino-modified MOF@COF interface to construct a light-responsive oxidase-like nanozyme for rapid total antioxidant capacity assay in foods - Yanhui Feng; An Xu; Huan Li; Xiumei Lin; Hongxu Guo (Food Chemistry, 2026)

Defect engineering in conductive MOFs: A strategy for high-performance paraquat electrochemical sensing - Xiao-Qin Li; Hao Ma; Deng-Yue Ma; Tiao-Bin Zhao; Lin-An Cao (Chemical Engineering Journal, 2026)

Formation gassing and high-temperature cycling of 5 Ah batteries with lithium-rich ferrite lithium as pre-lithiation reagent - Youzhi Song; Yun Gao; Fuqiang An; Boyuan Lin; Yuhan Wang; Xiaoyu Li; Yiding Li; Xiaoguang Yang; Jiuchun Jiang; Wenwei Wang (Chemical Engineering Journal, 2026)

Boosting electron transfer for high-performance microbial fuel cell with Cu2O-modified cathodes: Regulated pathway, reduced impedance, and remodelled microbial functions - Jinyan Guo; Hongxue An; Yingzhen Li; Lin Yue; Yankai Guo; Jing Lian (Bioresource Technology, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Three bioactive dibenzocyclooctadiene lignans from the fruits of Kadsura coccinea - Wen-Ming Wu; Jian Liu; Chao Chen; Bao-Lin Wang; An Jin (Natural Product Research, 2026)

Corrigendum to “The impact of filament winding configurations on the ultimate load-bearing capacity of non-metallic flexible pipes”[Ocean Eng. 341 (2025)] - Yingying Wang; Yangdong Hu; Kai Zhang; Weizheng An; Hanchen Zhou; Zeqing Lin; Segen Farid Estefen (Ocean Engineering, 2026)

The effect of hydrology on the spatial–temporal distribution and transport of PAHs in the Yangtze River mainstream - Xudong Guo; Moshan Cen; Yan Zeng; Ying An; Tian Lin; Jing Zhang; Yuchun Wang; Jingfu Wang; Jingan Chen (Journal of Hydrology, 2026)

Cretaceous sediment provenance, dispersal systems, and tectono-paleogeography of the western Tarim Basin, Northwest China: Far-field effects of Neo-Tethyan flat subduction - Hong-Xiang Wu; Feng-Qi Zhang; Cai-Yun Wang; Xiao-Gan Cheng; Kai-Xuan An; Yildirim Dilek; Cai Chen; Yu-Qing Zhang; Xiu-Bin Lin; Shuan-Hong Zhang; Han-Lin Chen (Global and Planetary Change, 2026)

Short anti-aging peptides from edible microalgae using a multi-targets virtual screening strategy combined with Caenorhabditis elegans model - Yan-yan Yuan; Xin Li; Ming-hui Han; Xue An; Yong-Qiang Lin; Hong-Bing Liu (Food Research International, 2026)

Engineering over-oxidized cu on CNTs for sensitive non-enzymatic glucose sensing and energy applications - Songxin Zhong; Rida Li; Hui Chen; Chao Xiao; Yining Lan; Qi-an Chen; Jian Li; Changqiang Feng; Shizhan Li; Hengchan Qi; Chi Gong; Zukun He; et al. (Chemical Engineering Journal, 2026)

Mechanically robust and electrolyte-stable 2D MOF-based nanocomposite membrane with rich low-resistance highways for high-performance osmotic energy harvesting - Chia-An Lung; Guang Hui Teoh; Wen-Hung Lin; Kalon Gopinadhan; Soorathep Kheawhom; Li-Hsien Yeh (Chemical Engineering Journal, 2026)

Breaking the sensitivity barrier in ELISA: A molecularly engineered peptide nanointerface achieves ultrasensitive detection of zearalenone - Zijun Yang; Zhiwei Liu; Zhongqi Lin; Wenjuan Xu; Xiu'an Duan; Zhenlin Xu; Xiangmei Li (Analytica Chimica Acta, 2026)

Lactate acts as a metabolic brake on inflammation by repressing NLRP3 transcription via NF-κB inhibition - Hsin-An Lin; Hsin-Chung Lin; Chih-Yung Chiou; Hao-Hsuan Peng; Yu-Jen Chen; Bo-Ying Bao; Kuen-Jou Tsai; Chao-Feng Lin; Chieh-Tien Shih; Sheng-I. Hu; Kuo-Yang Huang; Lih-Chyang Chen (Inflammation Research, 2026)

Bacillus subtilis modulates the intestinal microbiome and metabolism to promote growth and disease resistance in Micropterus salmoides - Meiyu Li; Wengen Zhu; Shuhui Niu; Xingxing An; Lin Chen; Houxiong He; Yaohua Wang; Song Zhang; Yong Yang; Qirui Li; Huanping Liu; Shuhan Zhang; et al. (Aquaculture, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Association of dietary intake of copper and zinc with systemic inflammation: A cross-sectional study integrating machine learning - Xuefei Zhang; Yuqing Deng; Huan Su; Xueran Huang; Yongfen Gao; Zhuangzhuang An; Zouyan He; Dan Li; Haiying Zhang; Rui Lin (Journal of Trace Elements in Medicine and Biology, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Surface nickel doping and boronization with island-sea effect for sustainable hydrodechlorination via a non-radical pathway - Wenjie Lin; Xinran Xiong; Wei Peng; Sai Yang; Junyue Ji; Zelong Zheng; You-an Chen; Yi-bo Hu (Journal of Environmental Chemical Engineering, 2026)

Liquid-phase hydrogenation of benzaldehyde to benzyl alcohol over NiCoAl‑R catalysts: Synergistic metal–metal oxide interfaces for enhanced catalytic performance - Lingmei Yang; An Wei; Ru kuan Liu; Guo ling Zhang; Bing Han; Baining Lin; Lianhua Li (Journal of Environmental Chemical Engineering, 2026)

Study on the synergistic high-temperature corrosion mechanism of NH3-H2S on different water wall tube materials under a strongly reducing atmosphere in an ammonia-coal co-firing environment - Rui Ma; Guoqiang Bu; Tiantian An; Bo Wei; Qianjin Lin; Lijuan Chen; Shan Wang; Kunpeng Liu; Lijie Song (Fuel, 2026)

Submicroparticle in chrysanthemum infusion inhibit oxidative stress, inflammation, and intestinal epithelial barrier dysfunction: a new alternative for intervention of ulcerative colitis - Lezhen Dong; An Peng; Mouming Zhao; Lianzhu Lin (Food Bioscience, 2026)

Melatonin safeguards embryo and blastoid development against oxybenzone toxicity via a mitochondrial-linked NAD+ and glucose metabolic axis - Yuying Xiong; Haiying Zhu; Han Xie; Yunqi Wu; Ruojin Shi; Xueling Zhang; Lin Zhu; Yiwen Wang; Ke Zhong; Lei Li; Yaming Meng; Minyu Xie; et al. (Environmental Pollution, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Dual effects of montmorillonite on CO2 hydrate formation kinetics in saline sand–clay systems: Experimental study and growth modeling - Xiran Lin; Ying Teng; Ying Liu; Mingkun Bai; Yiqi Chen; Pengfei Wang; Liangbin Xu; Jinlong Zhu; Songbai Han; Huiru Sun; Senyou An; Jianbo Zhu (Chemical Engineering Journal, 2026)

Dynamic electronic and spin-state modulations of ternary single-atom catalysts for ultrahigh power density and ultra-stable rechargeable zinc-air batteries - Yu-Chieh Ting; Shao-I Chang; Kai-An Lee; Chiung-Wen Chang; Tzu-Hsiang Lin; Chih-Heng Lee; Hsin-Yi Tiffany Chen; Shih-Yuan Lu (Chemical Engineering Journal, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

Multi-stage synthetic microbial consortia outperform single-stage augmentation by remodeling metabolism and mediating function-stability trade-off in anaerobic digestion - Miaomiao An; Jiarui Yu; Xianghao Lin; Yanjuan Lu; Xiaoxu Li; Jinling He; Guozhu Zhao (Bioresource Technology, 2026)

Drying-wetting cycles alter the balance between physical fragmentation and leaching during leaf litter decomposition: a laboratory incubation experiment - Le-Lin Yu; Rui-Jing Chai; Qi-Han Tu; An He; Le-Cheng Ai; Rong Mao (Plant and Soil, 2026)

Synthesis and antiproliferative evaluation of L-amino acid-6-gliotoxin ester trifluoroacetates - Xue An; Kexin Lin; Lihong Shan (Natural Product Research, 2026)

Research on Production–Living–Ecological Space recognition and evolutionary characteristics based on time-series Landsat images and POIs in a coastal economic and technological development zone - Yanghua Zhang; Bin Liu; Li Zhang; Lingxiao An; Weipeng Lin; Yiran Yan (International Journal of Remote Sensing, 2026)

Corrigendum to “Virus-induced redox cycling in Fe(II)/peracetic acid systems: dual roles as reactant and catalytic promoter” [Water Research 289 (2026) 124920] - Xiao Liu; An Ding; Wei Lin; Wei Qiu; Geoffroy Lesage; Marc Heran; Yan Zhao; Chuyang Y. Tang (Water Research, 2026)

Revealing uncertainties of on-road emissions in a mountainous city using multi-source data - Zeyu Zhang; Qiuzi Chen; Weizhen Lin; Ran Tu; Wenyu Wang; Xiaotong Zhang; An Wang (Transportation Research Part D: Transport and Environment, 2026)

A stimulating effect induced by Bisphenol A bis (diphenylphosphate) in HepG2 cells via vascular endothelial growth factor (VEGF)/VEGF receptor axis - Jing An; Yuting Yi; Na Li; Miao Lin; Yufang Zhong; Guofa Ren; Yu Shang (Toxicology Letters, 2026)

Description of a novel organic acid-degrading bacterium with biotechnological potential, Denitratimonas organivorans sp. nov., genomic assessment of the genus Denitratimonas, and proposal of a new species Denitratimonas yunnanensis sp. nov. named following the rules of the SeqCode - Miaomiao An; Rongrong Wang; Ruina Liang; Xianghao Lin; Xiaoxu Li; Yanjuan Lu; Guozhu Zhao (Systematic and Applied Microbiology, 2026)

Enhanced cycling and thermal stability of nickel-rich cathodes for lithium-ion batteries via molecular-weight-tuned polyaniline–polyethylene glycol interphase - Lin-Jie Xie; Jun-Cheng Jiang; Chen Liang; Qing-Song Wang; Hui-Qi Sun; Yan Tang; An-Chi Huang; Fei-Hao Zhu; Chi-Min Shu (Process Safety and Environmental Protection, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

Boosting multi-heavy metal sequestration in king grass: Unveiling the role of Serendipita indica symbiosis and the key root exudate GABA - Yali Duan; Jialiang Luo; Miaomiao Wang; Dong Li; Huiping Feng; Li Lin; Qianli An; Shunqing Xu; Zhiqiang Zhu (Journal of Environmental Sciences, 2026)

Ce-Fe bimetallic zeolite-imidazolate framework catalyzed ozonation for enhanced tetracycline degradation: synergistic electron transfer and multi-radical reaction pathways - Lin Yue; Shiqi Xing; Mengfei Wang; Hongxue An; Yunlong Yao; Yuxuan Li; Jing Lian (Environmental Research, 2026)

High-sensitivity and ultra-wide-range flexible piezoresistive sensor with surface microsphere and gradient cell structure for human gait correction - Xiangfang Peng; Shengguo Gu; Wen Xiao; Yuhuan Lin; Shulei Wu; Shuai Wang; Bin Tan; Haoyang Mi; Suiyi Li; Zhixiang Cui; Yongchao Xu; Feifan Yi; et al. (Chemical Engineering Journal, 2026)

Rational design of one-dimensional chain-like metal-organic frameworks featuring engineered nano-pockets for highly selective and efficient uranium sequestration - Zhi Wu; Shu-Yuan Zhang; Bin Lin; An-Min Song; Fei-Yi Kong; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2026)

Bridging accelerated cell-level degradation to module-relevant failure mechanisms in TOPCon solar cells and modules - Xinyuan Wu; Wei Wu; Weiguang Yang; Yan Zhang; Jiexi Fu; Xutao Wang; Jing Yuan; Jianjun Nie; Zhencong Qiao; Chao An; Feng Li; Lin Lv; et al. (Chemical Engineering Journal, 2026)

Hydroxylamine enhances the iron double-cycle system to improve the removal efficiency of norfloxacin via Fe3O4@N-rGO/PMS system - Lingzi Fu; Chao Wang; Aiguo Lin; Zhangbin Pan; Bin Wang; Li'’an Hou (Chemical Engineering Journal, 2026)

A high-performance bimodal sub-nanoporous polyelectrolyte complex membrane for organic solvent nanofiltration constructed by MOF-reinforced nano-unit - Hui-Qian Huo; Bing-Xin Gu; Jin-Lin Wang; Jia-Chen Zhang; Kai Zhang; Ming-Jie Yin; Yan-Li Ji; Quan-Fu An (Chemical Engineering Journal, 2026)

OH-initiated aqueous oxidation of methylglyoxal: Implications for organic acid and oligomer formation - Jiaxin Wang; Ying Chen; Wenjie Gao; Sihao Lin; Wenjian Li; Yongpeng Ji; Xiaolei Zhao; Yanpeng Gao; Yuemeng Ji; Taicheng An (Atmospheric Environment, 2026)

The scleractinian coral Pocillopora damicornis Linnaeus, 1758 released polyps with different physiological characteristics under heat stress - Kai Tang; Zhaoqun Liu; Zhicong Yan; Mingxun An; Jia Tang; Jiamin Lin; Chuanliang Wu; Zhi Zhou (Journal of Oceanology and Limnology, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Petrological and Geochemical Characteristics of the Lower Cambrian Shuijingtuo Formation in the Middle Yangtze Block, South China: Implications for Organic Matter Accumulation on Carbonate Platform - Baomin Zhang; Quansheng Cai; Guotao Zhang; Oumar Ibrahima Kane; Lin Chen; An Liu; Peng Zhou; Ruyue Wang (Journal of Marine Science and Engineering, 2026)
Understanding the development characteristics and controlling factors of organic-rich shales in carbonate platform settings is essential for predicting their distribution and assessing their natural gas exploration potential. However, the mechanisms governing the accumulation of such shales in these specific sedimentary environments remain poorly constrained, and the lack of integrated petrological and geochemical studies limits accurate evaluation of their resource potential. The key objective of this study is to investigate the development characteristics and formation mechanisms of organic-rich shales within intraplatform depressions. To address this objective, we conducted a comprehensive petrological and geochemical analysis of the Cambrian Shuijingtuo Formation organic-rich shale deposits deposited in a carbonate platform setting, particularly from Well EYY3 in Western Hubei, Central Yangtze region. The obtained results indicate that total organic carbon (TOC) contents in the Shuijingtuo Formation can reach up to 4.77%, with a thickness of approximately 9.5 m for shales containing over 2% TOC. Vertically, TOC content exhibits a rapid increase at the base, followed by a gradual decline toward the top, reflecting the evolution of depositional environments. The characteristics of organic-rich shale indicate a significant presence of carbonate minerals, which increase in concentration, alongside tuff lenticular bodies and lithological transition surfaces between tuff and shale. While the longitudinal variation of SiO2 content in shale is subtle, there is a slight increase in land-sourced clasts and excess silica, and TOC has a significant positive correlation. At the base of the Shuijingtuo Formation, redox parameters, including U-EF and Mo-EF, display a rapid increase followed by a gradual decrease. Conversely, changes in Ni-EF, which indicate paleoproductivity, are less pronounced, and their correlation with TOC is relatively poor. These findings suggest that rapid sea-level rise associated with Cambrian transgressions was the main factor influencing organic matter enrichment in the carbonate platform depressions. This rise supplied nutrients and silica-rich organisms, altering the biological landscape and fostering anoxic conditions in the intraplatform depressions, promoting organic-rich shale formation. As sea levels declined, water circulation became restricted, leading to oxidation of shallow water bodies, decreased paleoproductivity, and shale deposits transitioned to tuff. Therefore, organic-rich shale can also be developed on carbonate platforms, with its formation primarily controlled by fluctuations in sea level. During highstand periods, intraplatform depressions may serve as favorable zones for shale gas exploration.

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

High-frequency observation reveals the impacts of suspended sediment and hysteresis effect on water quality in soil erosion areas - Yongqiang Lin; Zhixiang Sun; Jiacheng Li; Jiayu Jiang; Qingqing Zuo; Tengyu Zhang; Kun An; Zhenyao Shen; Lei Chen (Journal of Hydrology, 2026)

Selective separation of bismuth from high-acid copper electrolytes: design of highly stable antimony-based adsorbent and investigation of strong adsorption mechanisms - Ao Gong; Yingdan Lin; Zixuan Zhang; Guangping An; Zheqiu Zhang; Zanhui Fu; Bin Zeng; Kuifang Zhang; Zhifeng Xu (Journal of Cleaner Production, 2026)

Screening, risk assessment, and rapid detection of mycotoxins in edible herbs based on UPLC-MS/MS and FT-NIR - Kangnan Liu; Ling Fang; Yaling An; Zijun Tang; Wenjie Zhao; Chunqian Song; Lin Feng; Xiaokang Liu; Zhenwei Li; Daidi Zhang; De-an Guo (Food Research International, 2026)

Regulation of metal-support interaction for enhanced Fischer-Tropsch synthesis over Co/TiO2 catalysts - Xuan Zhou; Ding Du; Shan Qiao; Xiao Yang; Ranqing Zhang; Yuanyuan Dai; Tiejun Lin; Yunlei An; Liangshu Zhong (Chemical Engineering Journal, 2026)

Multi active sites regulation of buried interface defects in n-i-p perovskite solar cells with tryptophan derivatives - Yanan Liu; Xinbao Lin; Xiaozheng Zhao; Tianci An; Wenya Zhao; Miaoran Zhang; Linfeng Cui; Taoyu Weng; Bo Liu (Chemical Engineering Journal, 2026)

CBC3T-3: a novel patient-derived cisplatin-resistant distal cholangiocarcinoma cell line harboring multiple TP53 missense mutations - Jiahui Xi; Mingzhen Bai; Ruyang Zhong; Chongfei Huang; Ruoshui An; Long Gao; Haidong Ma; Liang Tian; Jinyu Zhao; Ningzu Jiang; Xiang He; Leiqing Wang; et al. (Human Cell, 2026)
Distal cholangiocarcinoma (dCCA) is a malignant tumor characterized by a challenging diagnosis, high invasiveness, and extremely poor prognosis. Research on dCCA is limited by the scarcity of reliable patient-derived preclinical tumor models. This study established a novel human distal cholangiocarcinoma cell line, CBC3T-3, and systematically characterized its biological properties, genomic features, and potential for clinical application. This cell line was extracted from postoperative distal cholangiocarcinoma tumor from a 54-year-old male patient. It was stably passaged (> 50 generations) through primary culture and condition optimization, preserving the same pathology as that of the primary tumor. Whole-exome sequencing (WES) confirmed somatic mutations, tumor mutation burden, single-sample clonal structure, driver genes, and drug resistance genes in CBC3T-3 cells, revealing their genomic characteristics. Functional assays demonstrated that CBC3T-3 cells exhibit strong capabilities for proliferation, migration, and invasion in vitro. In a subcutaneous xenograft model in immunodeficient mice, palpable tumor nodules developed within 4 weeks, reflecting the clinical characteristics of rapidly progressive disease. Drug sensitivity analysis revealed that, compared with TFK-1 cells, CBC3T-3 cells presented significantly greater responses to paclitaxel, gemcitabine, and oxaliplatin but relatively poor responses to 5-FU and cisplatin. The integration of drug resistance gene findings from WES suggests that TP53 missense mutations may mediate primary resistance to cisplatin. The establishment of the CBC3T-3 cell line enhances the research toolkit for dCCA. Its genomic characteristics and functional plasticity provide a reliable preclinical tumor model for developing precision therapies and investigating drug resistance mechanisms.

Retraction Note: Tetraspanin 1 inhibits TNFα-induced apoptosis via NF-κB signaling pathway in alveolar epithelial cells - Lawei Yang; Yahong Wang; Zhanchun Pan; Shenglan Gao; Bao’an Zou; Ziying Lin; Dehui Feng; Changmei HuangFu; Gang Liu (Inflammation Research, 2026)

Determination of local site characteristics in the Hanoi urban area using microtremor data - Tien-Hung Nguyen; Hong-Phuong Nguyen; Le-Minh Nguyen; Che-Min Lin; Van-Duong Nguyen; Van-Bang Phung; The-Truyen Pham; An-Nguyen Tran; Quang-Khoi Le (Acta Geophysica, 2026)

Mechanisms of phosphorus release from coastal sediments driven by organic matter enrichment at high nitrogen concentrations - Chun-Pu Zhao; An-Hao Wang; Ying Zeng; Wen-Hao Yin; Cheng Luo; Shi-Xia Liu; Miao Liu; Hai-Jun Wang; Xiao-Wen Li; Ji-Lin Xu; Shuo-Nan Ma (Marine Pollution Bulletin, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Unified quasi-solid electrolyte design for coupled stabilization of Zn anode and I2 cathode in aqueous Zn-I2 batteries - Meng’an Wang; Tao Li; Shicong Zhang; Hexian Ma; Yang Xu; Yi Shen; Chenyu Wei; Tao Zhang; Tianquan Lin (Science Bulletin, 2026)

Neonicotinoids disrupt flight, bioenergetic homeostasis and neurotransmission in honey bees - Zepu Gao; Lin Ji; Wennan Luo; Zibo Feng; Xuebing Leng; Yongqiang Ma; Yaoguang Wei; Sen Pang; Dong An; Huizhe Lu (Journal of Hazardous Materials, 2026)

Detecting global ocean subsurface density change with high-resolution via dual-task densely-former - Hua Su; Weiqi Xie; Luping You; Sihui Li; Dian Lin; An Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Fabrication of synergistic photocatalytic–photothermal nanofibrous membrane for photo-assisted membrane distillation process - Xiaochan An; Jinhui Zhang; Jingjiao Li; Dandan Ma; Lin Cheng; Fenghui Chen; Jinsong He (Desalination, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Preferential N2-transport thin-film composite membrane for energy-efficient CO2 capture - Jin-Lin Wang; Cheng-Gang Jin; Hui-Qian Huo; Bing-Xin Gu; Yue Li; Wen-Hai Zhang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

Role of ITIH4 in Modulating YAP/TAZ-Mediated Apoptosis of Type II Alveolar Epithelium during Acute Respiratory Distress Syndrome - Yu-Syuan Shih; Xiao-Yue Chen; Yi-Wei Lin; Zih-An Liao; Yi-Hsuan Liu; Vincent Laiman; Syue-Wei Peng; Kazuhiro Ito; Hsiao-Chi Chuang (Pharmaceutical Research, 2026)

Whole-genome sequencing reveals the genetic diversity of Aeromonas from freshwater fish and the presence of novel genomic islands carrying clinically important antimicrobial resistance genes - Xiao-Qin Wang; Ke Wu; Run-Min Kang; Heng Lin; Lu-Ya Liu; Ting Xian; Yi-Zhi Tang; Xin Yang; An-Yun Zhang; Hong-Ning Wang; Chang-Wei Lei (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Two new naphthopyrones and a new prenylisoflavone from Berchemia lineata - Ling Li; Lin Feng; Lihua Peng; Weilin Qiao; Wei Li; De-an Guo (Phytochemistry Letters, 2026)

Decoupled intracontinental convergence between the South Tian Shan and northern Tarim Basin since the Neogene: Constraints from stratigraphy and detrital zircon U Pb geochronology of the Alparlek section - Kaixuan An; Jialun Huang; Xiubin Lin; Hanlin Chen; Yong Li; Xianzhang Yang; Liang Zhang; Cai Chen; Jinkai Xia; Xiaogan Cheng; Fengqi Zhang; Ziyi Wang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Topography and rural settlement control the evolution of sloping cropland toward diversity—evidence from the Three Gorges Reservoir Area over half a century - Xinyi Sun; Wenxin Zhao; Yangbing Li; Ying Huang; Lin Liu; Jing'an Shao (Journal of Cleaner Production, 2026)

Multi-scale assessment of energy transition and emission patterns in industrial coastal regions - Ying Teng; Mingkun Bai; Xiran Lin; Jiajie Li; Tao Zhang; Shuyang Liu; Senyou An; Liangbin Xu; Pengfei Wang; Songbai Han; Jinlong Zhu; Jianbo Zhu; et al. (Fuel, 2026)

Zero-energy, capillarity-gravity self-filtration system: A sustainable and ultra-low cost solution for high-efficiency microalgae removal - Haochuan Lin; Junjie Yang; Yuqin An; Mo Dong; Zupei Wang; Yiqi Tang; Huanhuan Tang; Hong Yao; Xinyang Li; Wen Zhang (Chemical Engineering Journal, 2026)

Benzo[c]chromene-based light-emitting conjugated polymer for high performance deep-blue PLEDs - Hong Ren; Zhiyang Sun; Xiang An; Qian Wu; Xinyu Du; Xiaoqi Guo; Wenyu Chen; Mengyuan Li; Jiabin Liu; Dunliang He; Ning Sun; Lubing Bai; et al. (Chemical Engineering Journal, 2026)

Engineering local donor-acceptor architecture in a porphyrin-based metal-organic framework for enhanced sonocatalytic immunotherapy - Yarui Hu; Sainan Liu; Jiwei Wang; Zhendong Liu; Xinyu Ma; Junhao Shao; Binbin Ding; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2026)

Quorum quenching driven enzymatic activity and metabolic pathway modulation in anaerobic reactor for enhanced methane production - Zijing An; Yibin Bao; Yuwei Yang; Xiaomei Su; Feng Dong; Xiao Xiao; Chongjun Chen; Hailu Fu; Hongjun Lin; Faqian Sun (Bioresource Technology, 2026)

A UAV-based multispectral imaging approach for tea shoots aerial mapping and assessment - Hsin-Cheng Chen; Shiou-Ruei Lin; Po-An Chen; Ta-Te Lin (Precision Agriculture, 2026)

Rhododendron dauricum essential oil obtained by enzyme-assisted hydrodistillation for antibacterial application - Nan An; Gaofeng Zhang; Lin Lu; Haoyang Chen; Liuke Zhang; Gaolei Xi; Xu Zhao; Xinran Zhang; Shuai Yu; Tao Jia; Xiuhua Zhao; Lei Yang (Plant Biosystems, 2026)

Design of asymmetric combined flow-guiding valve core structure in hydraulic spool valve - Zhao-tong Wang; Wen-qing Li; Xu-han Wang; Tong An; Zhen-hao Lin; Zhi-jiang Jin; Jin-yuan Qian (Annals of Nuclear Energy, 2026)

Gliotoxin isolated from soil fungus Aspergillus fumigatus induces apoptosis of human NSCLC and breast cancer - Rui Qi; Kexin Lin; Xue An; Ruiyun Zhao; Lihong Shan (Natural Product Research, 2026)

The migrations of Trichiurus japonicus in response to Kuroshio Current in northern Taiwan during winter based on satellite measured data - Yu-Chun Lin; Ming-An Lee (International Journal of Remote Sensing, 2026)

Evaluation of MarR-deleted Streptococcus agalactiae as a live-attenuated vaccine candidate for Nile Tilapia (Oreochromis niloticus) - Tian-Yu Ma; Feng-yang Li; Chang-Song Wu; Jian-Hao Lin; Ming Chen; Yong-An Zhang; Hui Zeng (Aquaculture, 2026)

Virus-induced redox cycling in Fe(II)/peracetic acid systems: dual roles as reactant and catalytic promoter - Xiao Liu; An Ding; Wei Lin; Wei Qiu; Geoffroy Lesage; Marc Heran; Yan Zhao; Chuyang Y. Tang (Water Research, 2026)

Early Cretaceous shortening event recorded by the emplacement of the Tiantai pluton, Eastern South China Block - Ran An; Wei Wei; Wei Lin; Chao Song; Yang Chu (Tectonophysics, 2026)

The variability of phosphorus fractions and transport driven by rainfall at both plot and catchment scales - Zhixiang Sun; Lei Chen; Yu Pu; Yongqiang Lin; Qingqing Zuo; Jiayu Jiang; Tengyu Zhang; Kun An; Zhenyao Shen (Journal of Hydrology, 2026)

Multiple-level fault controlled hydrothermal system in Huangshadong, Southeast China: Insights from coupled geophysical and geochemical investigations - Lu Liu; Xianan Qin; Zheng’an Wei; Min Zhang; Honglei Shi; Xiting Long; Wenjing Lin; Mingxiang Qiu; Guiling Wang; Shihua Qi; Fei Liu (Geothermics, 2026)

Predicting in-situ CO2 solubility in formation brines using Raman spectroscopy and machine learning: Implications for offshore geological carbon storage - Ying Teng; Yiqi Chen; Xiran Lin; Mingkun Bai; Senyou An; Shuyang Liu; Pengfei Wang; Tao Zhang; Songbai Han; Jinlong Zhu; Jianbo Zhu; Heping Xie (Gas Science and Engineering, 2026)

Effect of extrusion parameters on the quality of extruded reconstituted konjac glucomannan Rice - Rui Lai; Jie Liu; Hanxiao Qin; Qing Li; Yong Chen; Wenxuan Pan; Jikai Zhao; Qing Huang; Hongzhou An; Qian Lin; Yanru Li (Food Chemistry, 2026)

Electrochemically activated polypyrrole for full-polymer electrochemical deionization: Unraveling potential-gated ion exchange behavior and its application to oxyanion removal - Hung-Yi Huang; Yi-Heng Tu; Yi-An Chen; Cheng-Wei Lin; Yu-Hung Cheng; Hsing-Mei Chou; Yu-Hsiang Yang; Yun Ku; Zhiyin Yang; Sophia Uemura; Hsin-Lung Chen; Richard B. Kaner; et al. (Chemical Engineering Journal, 2026)

Pulsed electric fields as a green alternative to chemical treatment: Toward enhanced molecular interactions and performance in biodegradable preservation films - Rui Wang; Pei-Feng Guo; Ying Xu; Xing-Chan Xie; Dan-Dan Lin; Yu-Wei Wu; Dong-Yang Xu; Lang-Hong Wang; Xin-An Zeng (Chemical Engineering Journal, 2026)

Exploring the Role of B-Cell Biotherapy in Myasthenia Gravis from a Genetic Perspective: A Mendelian Randomization Study - Mengyuan Zhang; Cen Yue; Jie Fang; Jiahui Tang; Caihong Chen; Caili Zhou; Wanli Yang; Xingkai An; Qing Lin; Jiawei Zhang (Molecular Neurobiology, 2026)

Alterations in Gut Microbiota and their Association with Colonic Permeability and Inflammation in LPS-induced Sepsis Mice - Mengke Zhang; Yanyan Shu; Jingnan Yang; Sen Sang; Xiaoming Liu; Yuxia Li; Changjiang Qin; Lei An; Xuhong Lin (Current Microbiology, 2026)

Phillyrin promotes flap survival by mitigating pyroptosis through the TLR4/NF-κB/NLRP3 signaling pathway - Jiapeng Deng; Wenrui Kang; An Wang; Jialong Yang; Kaitao Wang; Lekai Quan; Hebin Pan; Weilong Song; Panshen Xu; Dingsheng Lin (Apoptosis, 2026)

Research on Subsea Cluster Layout Optimization Method Considering Three-Dimensional Terrain Constraints - Weizheng An; Wenze Liu; Xiaohui Song; Yingying Wang; Qiang Ma; Yangqing Lin; Yiyang Xue (Journal of Marine Science and Engineering, 2025)
Seabed topography is a key factor affecting the layout of underwater production systems. Developing a more scientific, intelligent, and integrated layout optimization method is the key to optimizing the layout of underwater production systems. To address the challenge of acquiring a more scientific, intelligent, and integrated optimization method, this paper proposes a multi-level integrated optimization model that incorporates three-dimensional seabed topography, obstacle areas, target locations, pipeline paths, and manifold connection relationships, with the primary objective of minimizing total investment cost. A hybrid algorithm combining H-MOPSO (Hierarchical Multi-Objective Particle Swarm Optimization) with K-means-ILP clustering, dynamic programming, and TEWA* pathfinding is raised to collaboratively solve for the global optimal layout, achieving a coupled “target grouping-manifold connection-path optimization” design. Based on the actual oilfield seabed topography and target data, this paper carries out case analysis and algorithm comparison experiments. The results show that the optimization method in this paper can significantly improve the layout economy and cost accuracy under the premise of meeting the engineering constraints. Among them, the PLEM parallel connection method reduces the pipeline laying cost by 25.72% and the overall layout investment cost by 5.39% compared with the traditional manifold series scheme.

Pilot study on integrating multidisciplinary technologies to implement an autonomous and smart harvester for asparagus - Joe-Air Jiang; Jen-Cheng Wang; Hung-Jen Lin; Cheng-Ying Chou; Chia-Chun Chien; Wei-Hao Huang; An-Chi Liu; Cheng-Chun Lee; Ming-Chi Guo; Jui-Chu Peng (Computers and Electronics in Agriculture, 2025)

Excavation-induced soil disturbance assessment of soft clay behind the diaphragm wall - Yan-Guo Zhou; Mu-Zhi Li; Yu Tian; Jun-Neng Ye; Wei-An Lin; Yun-Min Chen (Tunnelling and Underground Space Technology, 2025)

Cenozoic out-of-sequence structural expansion across the northern Tibetan Plateau margin: Insights from differential exhumation of the Altyn Shan and basin deformation - Shibao Gao; Xiaogan Cheng; Xiubin Lin; Baotian Pan; Yuhui Ye; Lei Wu; Kaixuan An; Hanlin Chen; Shufeng Yang (Tectonophysics, 2025)

Biocontrol efficiency and potential mechanism of dimethyl trisulfide against postharvest Diplodia stem-end rot in pummelo (Citrus maxima) - Yankun Lin; Shun Feng; Haijin Cai; Haibo Wang; Xiuli Zhang; Fangfang Wu; Shuoyu An; Xinguo Li (Postharvest Biology and Technology, 2025)

The impact of filament winding configurations on the ultimate load-bearing capacity of non-metallic flexible pipes - Yingying Wang; Yangdong Hu; Kai Zhang; Weizheng An; Hanchen Zhou; Zeqing Lin; Segen Farid Estefen (Ocean Engineering, 2025)

Diagenesis and burial history controls on Oligocene Huagang sandstones, southern Xihu Sag (East China Sea Basin): Implications for the formation of effective reservoirs - Hong-Liang Huo; Cheng-Lin Liu; Dao-Wu Huang; An-Qi Tian; Rizwan Sarwar Awan; Hong-Yan Gao; Chuang-Xin Liu; Xue-Yong Chen; Zi-Ye Tian; Tao-Zheng Yang; Bin-Bin Liu; Chao-Jun Liang (Marine and Petroleum Geology, 2025)

Perinatal maternal lead exposure induces intergenerational neurotoxicity via mitochondrial dysfunction and mediation by perturbation of thyroid function - Lin Zhang; An-Xin Lu; Ling Li; Qian Wei; Yin Lin; Jun-Xia Liu; Li Ma; Ren-Tong Chen; Bin Luo; Chong-Huai Yan (Journal of Hazardous Materials, 2025)

Cross-border cooperation increases agro-pastoral production resilience in climate extremes of transboundary river basins - Jiayue Lin; Ruslan Izimov; Tuolei Wu; Yi'an Huang; Ahebali Yeerboli; Peixuan Yang; Shijun Chen; Bin Qiu (Journal of Cleaner Production, 2025)

Multiomics and machine learning unveil root exudate-microbiota interactions for cadmium control in rice - Ye Li; Jie Hou; Mengqi Liu; Zhaolin Du; Hongan Chen; Guofei Liu; Yajun Wang; Yanpo Yao; Peizhe Sun; Lin Zhao; Yi An (Journal of Environmental Management, 2025)

Late Permian strike-slip tectonics in the northern North China Craton: new insights from geological and geophysical data of the Longwangmiao granitic pluton - Chao Song; Wei Lin; Wei Wei; Lingtong Meng; Yang Chu; Qinying Wu; Zhao Guo; Yin Wang; Ran An; Fei Liu; Jinhui Yang (Journal of Asian Earth Sciences, 2025)

Multi-omics analysis reveals PkNF-YA7a as a transcriptional activator that promotes glycerolipid biosynthesis in Pinus koraiensis seeds - Zeyu An; Yuxin Song; He Zhang; Xin Wang; Dongran Zheng; Peitian Yu; Yangxin Wang; Wenqian Hao; Lin Wu; Yang Zhang; Hailong Shen; Yuhua Li; et al. (Food Chemistry, 2025)

Advances in food flavor analysis and sensory evaluation techniques and applications: Traditional vs emerging - Boru Chen; Xiangyang Lin; Zhuotao Liang; Xiaoyue Chang; Zhen Wang; Mingquan Huang; Xin-An Zeng (Food Chemistry, 2025)

Near real-time subsidence monitoring and AI forecasting with multi-depth extensometers - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Guan-Zhong Lin; Shao-Hung Lin; Yi-An Chen (Engineering Geology, 2025)

Molecular planarity tailored hole-transporting materials for efficient perovskite solar cells - Xiaozheng Zhao; Xinbao Lin; Can Meng; Yanan Liu; Tianci An; Taoyu Weng; Linfeng Cui; Miaoran Zhang; Bo Liu (Chemical Engineering Journal, 2025)

Ultra-small medium-entropy nanozymes for targeting catalysis therapy of tumor - Meng-Qi He; Meng-Ying An; Zhenyu Wang; Cai-Shi Lin; Wenhao Shi; Hong-bin Sun; Fazheng Ren; Qionglin Liang; Yongjian Ai (Chemical Engineering Journal, 2025)

High-yield hydrogen from fluidized-bed biomass gasification via waste-derived anti-sintering composite sorbents - Baokun Li; Liangliang An; Shaoxiang Pu; Aoyang Zhang; Lin Li; Lunbo Duan; Ryang-Gyoon Kim; Xing Zhu; Hua Wang; Dongfang Li (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Synergistic enhancement of CO2 hydrate growth by montmorillonite and tryptophan: Insights from piecewise kinetic modeling - Xiran Lin; Ying Teng; Mingkun Bai; Yiqi Chen; Pengfei Wang; Liangbin Xu; Senyou An; Jianbo Zhu; Jinlong Zhu; Songbai Han (Chemical Engineering Journal, 2025)

Flexible solar evaporator for simultaneous desalination and VOCs removal from seawater - Long-Feng Hu; Huiting Zhang; Huan Lin; Hui Niu; Hao-Ran Chen; Quan-Fu An (Chemical Engineering Journal, 2025)

A pH-responsive and nitric oxide-producing nanocarrier for targeted therapy of melanoma - Shuai Cui; Qing Yu; Ziyuan Su; Yiting Han; Sujuan Wang; Xiangyu Zou; Lin An; Nannan Yin; Hao Hong; Dongzhi Yang (Chemical Engineering Journal, 2025)

Mountain ecosystem health response to landscape pattern in the Three Gorges Reservoir Area, China - Lin Liu; Qingrong Wang; Yangbing Li; Jing’an Shao; Ying Huang (CATENA, 2025)

Hydrodynamic forces on small-diameter pipelines in combined wave-and-current flows - Yunfei Teng; Terry Griffiths; Hongwei An; Scott Draper; Liang Cheng; Henning Mohr; Cheng Zhang; Guoqiang Tang; Lin Lu (Coastal Engineering, 2025)

Photochemistry of acetylacetone: Droplets-mediated H2O2 generation and SO2 oxidation - Yu Lu; Lingdong Kong; Jiandong Shen; Beibei Liu; Yixuan An; Yuwen Wang; Jie Tan; Lin Wang (Atmospheric Environment, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Coplanar DCA-based hypofractionated stereotactic radiotherapy for very small brain metastasis from non-small cell lung cancer: treatment planning comparison with coplanar VMAT and preliminary clinical outcome - Shipai Zhu; An Li; Jia Liu; Qin Deng; Qingfang Li; Jialu Lai; Lin Zhou (Physical and Engineering Sciences in Medicine, 2025)

The IL-6 autocrine loop promoting IFN-γ-induced fibroblast senescence is involved in psychological stress-mediated exacerbation of vitiligo - Cheng Cao; Wen Xu; Jingdi Lei; Yujie Zheng; An Zhang; Aie Xu; Fuquan Lin; Miaoni Zhou (Inflammation Research, 2025)

Cryptococcal antigen cross-reactivity is associated with fatal trichosporonosis in patients with hematologic diseases - Ting-An Lin; Yi-Tsung Lin; Chia-Jen Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Testing and modeling of chemically induced changes in mechanical characteristics of cement-stabilized sensitive marine clays - Yang An; Yubin Li; Can Yang; Zhuoma Yangjin; Lin Yuan (Marine Georesources & Geotechnology, 2025)

RNAi bioassays targeting bursicon reveal potential targets for pest control of Henosepilachna vigintioctopunctata - Quanxing Lei; Aili Lin; Jizhen Wei; Mengfang Du; Qisheng Song; Yunhui Zhang; Xiaoming Liu; Shiheng An (Pesticide Biochemistry and Physiology, 2025)

Stability of RL-modified n-FeS and its mechanisms for Cr(VI) removal efficiency - Kaipian Shi; Junfeng An; Lin Xu; Li Yin; Chunqing Peng; Yong Zhang; Shiyin Li; Lixiao Ni (Journal of Water Process Engineering, 2025)

Simulation study on mineral transformation behaviors and ash fusion characteristics during high-alkali coal combustion under deep peaking conditions - Jiamiao Liu; Guowei Ma; Yongbo Du; Chang’an Wang; Yonggang Zhao; Wanzhu Wu; Longping Shi; Lin Zhao; Defu Che (Fuel, 2025)

Hierarchically plasticized intrinsically stretchable fully π-conjugated polymer films for flexible and large-area printed RGB light-emitting diodes - Ningning Yu; Zhiqiang Zhuo; Yingying Zheng; Mingjian Ni; Wenyu Chen; Jiabin Liu; Dunliang He; Jingyao Ma; Man Xu; Xiang An; Lubing Bai; Jinyi Lin; et al. (Chemical Engineering Journal, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

An overlooked health risk of PM2.5: Elevated respiratory viral susceptibility revealed by assessing inflammatory and antiviral responses to chemical constituents - Shuyi Peng; Juying Lin; Wei Sun; Yaohao Hu; Baichuan Gou; Guohua Zhang; Wei Song; Bin Jiang; Chenglei Pei; Jinpu Zhang; Jianwei Dai; Xinming Wang; et al. (Atmospheric Environment, 2025)

The effect of photosensitization reaction of imidazole-2-carbaldehyde on the heterogeneous uptake of sulfur dioxide on hematite - Yixuan An; Lingdong Kong; Beibei Liu; Jiandong Shen; Yu Lu; Yuwen Wang; Jie Tan; Lin Wang (Atmospheric Environment, 2025)

Characteristics and influencing factors of ambient ozone pollution in Hangzhou in the relative humidity range with high ozone levels - Yu Lu; Lingdong Kong; Jiandong Shen; Beibei Liu; Yixuan An; Yuwen Wang; Jie Tan; Lin Wang (Atmospheric Pollution Research, 2025)

COMPERA 2.0 risk stratification in patients with severe aortic stenosis: implication for group 2 pulmonary hypertension - Zongye Cai; Xinrui Qi; Dao Zhou; Hanyi Dai; Abuduwufuer Yidilisi; Ming Zhong; Lin Deng; Yuchao Guo; Jiaqi Fan; Qifeng Zhu; Yuxin He; Cheng Li; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

How to promote green transformation of mariculture industry under the influence of financial constraints? A policy simulation based on peer incentive perspective - An Yan; Ying Liu; Chunyu Lin; Wenwen Gu; Qiaorong Yin; Xiumei Fu (Marine Pollution Bulletin, 2025)

Inspecting urban transit-oriented development from the perspective of human activity: A case study of Xi'an, China - Jiayu Liu; Xiping Yang; Lin Luo; Junyi Li; Hongfei Chen; Rui An; Jiyuan Li (Journal of Transport Geography, 2025)

Halogenated flame retardants in the sediments of the lower Great Lakes and region-wide discoveries - Tian Lin; Shanshan Zhou; Huan He; Jiehong Guo; Neil C. Sturchio; Karl J. Rockne; John P. Giesy; An Li (Journal of Hazardous Materials, 2025)

Molecular and microscale–level insights into the potential mobilization of toxic elements in Pb/Zn smelting contaminated soils under freeze–thaw cycles - Yu–Xiang Shi; Da–Mao Xu; Dong–Sheng Dai; Ze–Lin Xu; Bai–Hong An (Journal of Hazardous Materials, 2025)

A machine learning and counterfactual reasoning-integrated decision framework for cadmium remediation: Predictive optimization and cost-benefit analysis driven by iron plaque regulation - Ye Li; Jie Hou; Mengqi Liu; Ruilin Li; Zhaolin Du; Yanpo Yao; Peizhe Sun; Lin Zhao; Yi An (Journal of Hazardous Materials, 2025)

Efficient utilization of low-grade ilmenite: An innovative approach integrating pre-oxidation with CH₄-H₂ direct reduction for titanium carbide production - Tingting Lv; Jianwei Song; Yunfei An; Tu Hu; Guo Lin; Baocheng Zhou (Journal of Environmental Chemical Engineering, 2025)

Sustained moderate oxidation system driven by gas-liquid-solid microenvironment under Mn(VII)-Fe(III)/sodium percarbonate (SPC) treatment: Mechanism and application in sludge dewatering - Wei Lin; Chuangxin Gong; Xiuxiang Ding; Xu He; Jun Ma; Mohamed E.A. Ali; Ahmed Shahat; Piotr Oleskowicz-Popiel; An Ding (Journal of Environmental Chemical Engineering, 2025)

Classification and identification of chicken-derived adulteration in pork patties: A multi-dimensional quality profile and machine learning-based approach - Hui Lu; Cong Yao; Lin An; Aiying Song; Feng Ling; Qiliang Huang; Yuling Cai; Yunguo Liu; Dacheng Kang (Food Control, 2025)

Ceramic fiber aerogels based flexible solar steam generators enabling efficient thermal localization and high salt resistance - Yun Jiang; Yumin Liu; Lin Li; Zhibin Li; Pengzhang Li; Xianshu Qiao; Wenyan Zhao; Chuanjin Tian; Weiwei Sun; Yanhao Dong; Zhipeng Xie; Chang-An Wang (Desalination, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

S-scheme heterojunction of N‐carbon dots/g-C3N4/MIL-101(Fe) photocatalytic membrane for peroxymonosulfate-activated photodegradation of enrofloxacin - Zhi-Fu Lin; Cheng-Kuo Tsai; YenJung Sean Lai; Thanh-Binh Nguyen; Prashanth Venkatesan; Ruey-An Doong (Chemical Engineering Journal, 2025)

Flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2025)

Facilitating extensive CC bond cleavage in lignin models through customized CeO2/C3N4 S-scheme heterojunction - Hongwu Liao; Chong Wang; Jiaxian Zheng; Zhuo Chen; Yulin Zhou; Chengning Ye; Xiangfeng Lin; Meng An; Yusuke Yamauchi; Yusuke Asakura; Zhanhui Yuan (Chemical Engineering Journal, 2025)

Chitosan-based Janus dressing with asymmetric wettability for rapid hemostasis, antibacterial protection, and tissue regeneration in hemorrhagic wound management - Jiyuan Wang; Haowen Ye; Kaitong He; Weikang Jiang; Wei Lan; Zu’an Zeng; Peiran Lin; Han Wang; Botao Gao; Wenlong Wang; Yadong Tang (Carbohydrate Polymers, 2025)

Recycling of continental crust into the deep mantle in orogens: Constraints from zircon U-Pb-Hf-O and whole-rock Mg-Fe isotopes of Baihua complex, North Qinling Orogen - Gang Yang; Juan Zhang; Hong-Fu Zhang; An-Ping Chen; A-Bing Lin (Chemical Geology, 2025)

Aqueous photochemistry of brown carbon: H2O2 formation, enhanced SO2 oxidation, and the real role of excited triplets - Beibei Liu; Lingdong Kong; Yixuan An; Yu Lu; Yuwen Wang; Jie Tan; Xingfu Tang; Lin Wang (Atmospheric Environment, 2025)

Critical factors and cost estimation for the immobilization of cadmium-contaminated paddy fields for rice safety - Shuqi Li; Dasong Lin; Lili Huo; Bo Wu; Lixia Sun; Yi An; Yuqing Xia (Journal of Soils and Sediments, 2025)

A new approach to inferring the threshold range for quality control of ocean T/S profiles based on probability distribution of historical data - Lin Conghao; Wang Huizan; Bao Senliang; Liu Zenghong; Yan Hengqian; An Yuzhu (Acta Oceanologica Sinica, 2025)

Distribution pattern of cetaceans in the northern South China Sea based on visual surveys and environmental DNA metabarcoding - Shengming Deng; Xiang Zhang; Min Liu; Bai‐An Lin; Yongcan Zhou; Mingming Liu; Wenzhi Lin; Mingli Lin; Lijun Dong; Hui Kang; Binshuai Liu; Shenglan Chen; et al. (Conservation Biology, 2025)
The South China Sea (SCS) is vital habitat and potential nursery and feeding grounds for large cetaceans, such as the sperm whale ( Physeter macrocephalus ), making understanding of the temporal and spatial patterns of cetaceans in this region essential. We examined the accuracy of environmental DNA (eDNA) in detecting cetacean species diversity and determine the spatial and temporal distribution of cetaceans in the northern SCS. We conducted 5 ship‐based visual surveys for cetaceans in 3 summers and 2 springs from 2020 to 2023 and used eDNA metabarcoding to determine the relative abundance and spatial and temporal distribution of cetaceans in offshore and abyssal areas of the northern SCS. We detected 18 cetacean species through visual observations and eDNA metabarcoding. Both methods identified 12 species in common. Cetaceans’ presence varied temporally. We detected 7 species in the springs and 17 species in the summers. Expedition route design, meteorological conditions, and sea conditions between the 2 seasons partly explained the seasonal differences. The species of Ziphiidae, Physeteridae, and Kogiidae tended to occupy regions with high bathymetric drop gradients, particularly those situated on continental slopes and seamounts. The Delphinidae were more widely distributed and relatively more abundant. Of the cetaceans successfully identified by eDNA metabarcoding, species with relatively large group sizes and that were relatively close to the sampling sites tended to be more easily detected. Our results provide new information on the relative abundance and spatial and temporal distribution of cetaceans and indicate that eDNA techniques can provide additional information and serve as a complementary tool for cetacean monitoring and conservation.

Integrin CD11b Alleviates Cerebral Ischemia/Reperfusion Injury via a Mechanism Involving Microglia/Macrophage Polarization - Gui-Nan Jiang; Qiu-Yue Lin; Xiang-Bo An; Wei-Jia Yu; Jie Bai; Xin Yu; Feng Wang; Hui-Hua Li (Journal of Molecular Neuroscience, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Artificial intelligence boosting multi-dimensional information fusion: Data collection, processing and modeling for food quality and safety assessment - Hengrui Zhang; Yuandong Lin; Shilin Cao; Jun-Hu Cheng; Xin-An Zeng (Trends in Food Science & Technology, 2025)

Deciphering the venom components of Sea snakes: Integrating dual proteomic techniques to uncover the bioactive potential of Hydrophis curtus - Yingying Li; Haorui Dai; Zhiping Zhao; Ruiwei Ye; Sheng Han; Dandan Yang; Hanyu Pan; Jiayi Lin; Xiawen Dang; Yue Cheng; Zhaoran Yu; An Li; et al. (Toxicon, 2025)

Antimony induces mitochondria-dependent and ER stress-triggered apoptosis via the oxidative stress-activated JNK signaling pathway in pancreatic islet β-cells - Ken-An Lin; Chin-Chuan Su; Shing-Hwa Liu; Kuan-I. Lee; Kai-Min Fang; Chih-Hsin Tang; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology, 2025)

Establishment of in vitro grafting system for Tree Peony - Bingjie An; Shuangshuang Yang; Yimiao Sun; Xinrong Fu; Zijing Lin; Wen Gao; Zhengjing Wu (South African Journal of Botany, 2025)

Detrital zircon U Pb geochronology of the Cenozoic succession in the southern Tarim Basin: Implications for the northward expansion of the West Kunlun Orogen and the evolution of intracontinental convergence in the northwestern Tibetan Plateau - Chunyang Li; Kaixuan An; Xiubin Lin; Yong Li; Xianzhang Yang; Liang Zhang; Cai Chen; Shujun Liang; Xiaochun Wei; Yang Qu; Xinyue Zhao; Jialun Huang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Development of a pilot ultrasound equipment and its optimal parameters for the rapid debitterizing of apricot kernels - Chen-Xiang Zhang; Guangmin Nie; Xue-Hui Fan; Ya-Qi Lin; Qing-An Zhang (Journal of Food Engineering, 2025)

Water flow-driven high piezo-photocatalytic efficacy in superthin and densely porous GO-TiO2/PVDF-HFP composite film for ROS generation - Jialin Zhuang; Yechen Wang; Liping Lin; Jiaying Xiao; Jiahui Cai; Yingmo Hu; Qi An (Chemical Engineering Journal, 2025)

Strontium diorthovanadate anode for fast-charging lithium-ion battery with low redox potential - Xiaolei Li; Shuangdui Wu; Jian Su; Jing Zhang; Xuguang An; Weitang Yao; Hongli Sun; Borong Lin; Qingquan Kong (Chemical Engineering Journal, 2025)

Block copolymer architectures with poly(ε-caprolactone) for modulating interactions to enhance selectivity and stability of semiconducting single-walled carbon nanotube dispersions - Mei-Nung Chen; Rin Iwasaki; Mayoh Ashiya; Haoyu Zhao; Qi-An Hong; Yen-Ting Li; Kai-Lin Chen; Maina Moses Mburu; Wei-Ting Li; Xiaodan Gu; Wei-Hung Chiang; Takuya Isono; et al. (Chemical Engineering Journal, 2025)

Potential prognostic biomarker of OSBPL10 in pan-cancer associated with immune infiltration - Jiapeng Qi; Kun Yu; Bei Liu; Yan Wang; Wei Wang; Ran An; Chaojun Wang; Na Li; Dongqian Xu; Lin Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Cadmium exposure causes trophoblast abnormal syncytization and endocrine dysfunction in preeclampsia - Weilong Lin; Xuemeng Li; Xiangyou An; Jiancai Yin; Ziyan Zhao; Xiaorui Yan; Rong Xu; Baojing Zhao; Xue Du; Huiru Cheng; Zhen Yu; Yuanyuan Yang (Reproductive Toxicology, 2025)

Advancements in gas-liquid separation based on membrane contactors: Critical factors enhancing separation efficiency - Helin Wang; Tao Zhang; Ruochen An; Lin Sun; Xiaohui Weng; Zhiyong Chang (Process Safety and Environmental Protection, 2025)

Harmonizing stakeholder interests in urban renewal: A novel planning approach using explainable machine learning and spatial optimization - Chuan Lin; Yilun Liu; Zhongyou Yuan; Hongmei Wang; Guang Li; Zegen Zhou; Han Wang; Xinyue An (Land Use Policy, 2025)

SpecDETR: A transformer-based hyperspectral point object detection network - Zhaoxu Li; Wei An; Gaowei Guo; Longguang Wang; Yingqian Wang; Zaiping Lin (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Unlocking the healing power of Jinhua white tea fermented by Eurotium cristatum using the unique “flowering” technology: A promising ally against inflammatory bowel disease - Yong Lin; Xirui Zhou; Silin Xie; Jian-an Huang; Jie Li; Yanyan Yao; Maiquan Li; Jiahui Bo; Lizheng Xiao; Zhonghua Liu; Wei Quan (Food Research International, 2025)

Early-life long-term exposure to di(2-ethylhexyl) phthalate (DEHP) impairs pathogenic avoidance behavior associated with dopaminergic pathway in Caenorhabditis elegans - Ting-An Lin; Chun-Han Chang; Tzu-Ting Chang; Vivian Hsiu-Chuan Liao (Environmental Toxicology and Pharmacology, 2025)

Combining the life cycle model and corrosion model to analyze the impact of corrosion on carbon emissions of steel pipelines - An Yan; Ying Xiao; Hongyang Ren; Bing Lin; Hailong Zhang; Yingying Wang; Xi Li; Bing Wang; Junlei Tang (Environmental Impact Assessment Review, 2025)

Changes in soil organic carbon and its forms in recovering alpine meadows of various lengths in relation to altitude - Chunying Lin; Xilai Li; Huafang Sun; Xiaoxue Su; Hongmei Li; Rongna Liu; Chengyi Li; Yonghui Hou; Shizhen Zhu; Di Yu; Liyan Zhang; Jiexia Li; et al. (CATENA, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

Detrital Zircon U-Pb Age Analysis of Late Pliocene Deposits from the Lower Yangtze River, South China: Implications for Sedimentary Provenance and Evolution of the Yangtze River - Xu Lin; Yuxuan Pang; Chang’an Li; Jing Liu-Zeng; Marc Jolivet; Haijin Liu; Chengwei Hu; Xiaokang Chen (Journal of Earth Science, 2025)

Karst Trough Control of Solute Transport Processes at Two Karst Groundwater Flow Systems, Western Hubei, Central China - Yi’an Wang; Ruichao Zhao; Lin Ding; Shuai Xiong; Yin Li; Jianwei Bu; Wei Chen; Hong Zhou; Wei Liu (Journal of Earth Science, 2025)

Research on Optimization Design of Ice-Class Ship Form Based on Actual Sea Conditions - Yu Lu; Xuan Cao; Jiafeng Wu; Xiaoxuan Peng; Lin An; Shizhe Liu (Journal of Marine Science and Engineering, 2025)
With the natural evolution of the Arctic route and advancements in related technologies, the development of new green ice-class ships is becoming a key technological breakthrough for the global shipbuilding industry. As a special vessel form that must perform icebreaking operations and undertake long-distance ocean voyages, an ice-class ship requires sufficient icebreaking capacity to navigate ice-covered water areas. However, since such ships operate for most of their time under open water conditions, it is also crucial to consider their resistance characteristics in these environments. Firstly, this paper employs linear interpolation to extract wind, wave, and sea ice data along the route and calculates the proportion of ice-covered and open water area in the overall voyage. This provides data support for hull form optimization based on real sea state conditions. Then, a resistance optimization platform for ice-class ships is established by integrating hull surface mixed deformation control within a scenario analysis framework. Based on the optimization results, comparative analysis is conducted between the parent hull and the optimized hull under various environmental resistance scenarios. Finally, the optimization results are evaluated in terms of energy consumption using a fuel consumption model of the ship’s main engine. The optimized hull achieves a 16.921% reduction in total resistance, with calm water resistance and wave-added resistance reduced by 5.92% and 27.6%, respectively. Additionally, the optimized hull shows significant resistance reductions under multiple wave and floating ice conditions. At the design speed, calm water power and hourly fuel consumption are reduced by 7.1% and 7.02%, respectively. The experimental results show that the hull form optimization process in this paper can take into account both ice-region navigation and ice-free navigation. The design ideas and solution methods can provide a reference for the design of ice-class ships.

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

N,O-interlocked cavity-structured functionalized metal–organic frameworks for one-step efficient removal of highly toxic thorium from tailings wastewater - An-Min Song; Zhi Wu; Bin Lin; Meng-Jie Yang; Qing Yang; Shu-Yuan Zhang; Xiao-Xing Wang; Zhi-Hai Peng; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Electronic state reconfiguration of NiMoCox boosts electrocatalytic upcycling of polyethylene terephthalate plastic wastes for simultaneous production of formate and green hydrogen - Shaofeng Wang; Shuaidong Li; Yutong Li; Yue Xu; Zhaomeng Wu; Yingjian He; Yongwei Zhao; Zheer An; Ying Lan; Yanxiao Hu; Jingzi Zhang; Yan Huang; et al. (Chemical Engineering Journal, 2025)

Correlation study of 5-HT in brain with cognitive function and anxious-like behavior in APP/PS1 transgene mice - Li Yuan; Linshan An; Rui Xie; Jiahong Cai; Dong Li; Xiaorong Chen; Wenjing Guo; Yinran Lin; Chunjing Zhu; Yongli Chang; Kunbo Wang; Weina Han; et al. (Sleep and Biological Rhythms, 2025)

Breast cancer image classification based on H&E staining using a causal attention graph neural network model - Xiaoya Chang; Zhongrong Zhang; Jianguo Sun; Kang Lin; Ping’an Song (Medical & Biological Engineering & Computing, 2025)

Characterizing the antecedent rainfall and ATI-MODIS-derived soil moisture content of shallow landslides in Taiwan - Yuei-An Liou; Jung-Jun Lin (Landslides, 2025)

Safranal ameliorates atherosclerosis progression partly via repressing PI3K/Akt and NF-κB signaling pathways in ApoE (−/−) mice - Yining Geng; Manping Song; Bing Huang; Ru Lin; Shiwen Wu; An Lin (Journal of Natural Medicines, 2025)

Application and scenario simulation of multimodal GPT in circular economy transformation: A case study of Taiwan's material flow data - Rui-an Lin; Hwong-wen Ma (Resources, Conservation and Recycling, 2025)

Genome-wide association study of tea plant based on SLAF-seq revealed SNP variations regulating timing of bud flush - Xiaozeng Mi; Dahe Qiao; Yanlin An; Chun Yang; Kaiqin Lin; Congling Peng; Juan Chen (Plant Gene, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Geochemistry, geochronology and Fe-Mg-S isotopic composition of the Liaoshang gold deposit, Jiaodong Peninsula, China: Implications for ore-forming processes and mineral exploration - Yuan-lin Chen; Huan Li; Shang-yi Gu; Scott A. Whattam; Chao-yang Zheng; Li-gong Wang; Da-dou Li; Liu-an Duan (Journal of Geochemical Exploration, 2025)

Recycled polyethylene terephthalate/reduced graphene oxide modified with magnesium ferrite for organic dye degradation with benign toxicity towards Vigna radiata L and Ipomoea aquatica, and photocatalytic water splitting to produce H2O2 - Nguyen Huu Hieu; Tong Hoang Lin; Ton That Buu; Che Quang Cong; Hoang An; Nguyen Thanh Hoai Nam (Journal of Environmental Chemical Engineering, 2025)

Atomevo-odor: A database for understanding olfactory receptor-odorant pairs with multi-artificial intelligence methods - Heng-Yun Zhao; Si-Min Xu; Si-Nuo Xie; Wan-Lin Ye; Jian Li; Lang-Hong Wang; Shi-Lin Cao; Jun-Hu Cheng; Xin-An Zeng; Ji Ma (Food Chemistry, 2025)

The role of electroactive biofilms in enhanced para-chlorophenol transformation collaborated with biosynthetic palladium nanoparticles - Shaofeng Zhou; Yanjing Li; Shan Yang; Lizhou Lin; Tongchu Deng; Cuifen Gan; Wenwen An; Meiying Xu (Environmental Pollution, 2025)

Corrigendum to “Smart glucose-responsive hydrogel with ROS scavenging and homeostasis regulating properties for diabetic bone regeneration” [Chem. Eng. J. 497 (2024) 154433] - Ziyang Liu; Jing Mao; Weiqi Li; Chenci Xu; An Lao; Airi Shin; Jiaqing Wu; Anqi Gu; Zhen Zhang; Lixia Mao; Kaili Lin; Jiaqiang Liu (Chemical Engineering Journal, 2025)

N6-methyladenosine-modified circ_0000517 promotes non-small cell lung cancer metastasis via miR-1233-3p/CDH6 axis - Weixian Lin; Lifang Huang; Zhu’an Ou; Yiwen Xuan; Daoqi Zhu; Qipeng Zhang; Enwu Xu (Journal of Molecular Histology, 2025)

The influence of shading facilities on outdoor thermal comfort, pedestrian walking speed, and indoor satisfaction - Zi-En Lin; Shiang-Yu Wang; Kuo-An Hung; Chiao-Jou Hsieh; Tzu-Ping Lin (International Journal of Biometeorology, 2025)

Microbiological Activity and Oxygen Availability Influence Arsenic Mobilization and Redox Transformation in an Arsenic-Rich Aquifer - Yu-Chen Su; Yu-Ju Chu; Chia-Cheng Wei; Chan-Wei Yu; Pei-Ling Yen; Yu-Hsuan Kuo; Ting-An Lin; Vivian Hsiu-Chuan Liao (Exposure and Health, 2025)

Characteristics of Humic Acid–Iron Colloid Stability and Its Mechanism of Binding with As(III) - Junfeng An; Conghui Wang; Jia Yu; Kaipian Shi; Youru Yao; Jingyi Zhang; Chonghong Zhang; Yuesheng Lin; Shiyin Li (Bulletin of Environmental Contamination and Toxicology, 2025)

A 10-Year Dataset of Land Surface Observations for the Semi-Humid Alpine Grassland in the Source Region of the Yellow River - Xianhong Meng; Yu Zhang; Lunyu Shang; Shaoying Wang; Zhaoguo Li; Shihua Lyu; Yinhuan Ao; Siqiong Luo; Lijuan Wen; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2025)
The source region of the Yellow River, accounting for over 38% of its total runoff, is a critical catchment area, primarily characterized by alpine grasslands. In 2005, the Maqu land surface processes observational site was established to monitor climate, land surface dynamics, and hydrological variability in this region. Over a 10-year period (2010–19), an extensive observational dataset was compiled, now available to the scientific community. This dataset includes comprehensive details on site characteristics, instrumentation, and data processing methods, covering meteorological and radiative fluxes, energy exchanges, soil moisture dynamics, and heat transfer properties. The dataset is particularly valuable for researchers studying land surface processes, land–atmosphere interactions, and climate modeling, and may also benefit ecological, hydrological, and water resource studies. The report ends with a discussion on perspectives and challenges of continued observational monitoring in this region, focusing on issues such as cryosphere influences, complex topography, and ecological changes like the encroachment of weeds and scrubland.

Review on Quantitative Methods of Fish School Behaviors - Yaoguang Wei; Lin Ji; Dong An (Reviews in Aquaculture, 2025)
In aquaculture, the quantitative analysis of fish school behavior refers to the systematic application of mathematical and statistical tools for the precise measurement and description of fish school behavior characteristics through metrics, statistics, and modeling. Compared to studies on individual behavior, the analysis of fish school behavior is crucial for managing fish health and enhancing aquaculture efficiency. Quantitative analysis deepens our understanding of fish school structure and interaction patterns, facilitating the development of more rational and efficient feeding strategies. Traditional manual detection methods are time‐consuming, labor‐intensive, and have limited accuracy, resulting in inadequate quantitative analysis of fish schools and difficulties in parametrically assessing their behavior and physiological states, which pose challenges to accurate evaluations. However, in recent years, with the emergence of new technologies and quantification indicators, the assessment of fish school behavior has become more accurate and objective. This review summarizes three key technologies for quantitatively analyzing fish school behavior: computer vision, acoustics, and sensors. It outlines three types of quantitative indicators: behavior, biomass estimation, and environment. Furthermore, it provides insights into the response of fish school behavior to four key factors: environmental stress, feeding, disease, and reproduction. The study indicates that comprehensive behavior recognition information often requires selecting suitable technologies or integrating multiple technologies based on the specific needs and conditions of the aquaculture site. Therefore, future research in multimodal data fusion will likely contribute to further advancements in the field of aquaculture.

Turbo Equalization Based on a Virtual Decoder for Underwater Acoustic Communication - Cong Peng; Lei Wang; Lerong Hong; Zehua Lin; An Luo (Journal of Marine Science and Engineering, 2025)
By transferring external information between the equalizer and the decoder iteratively, the performance of turbo equalization is close to the channel capacity. Conventional turbo equalization (CTE) relies on channel coding, while the transmission of external information is a problem in an uncoded system, and turbo equalization without channel coding (TECC) remains unexplored. Therefore, this paper introduces a TECC framework with a virtual decoder constructed by bidirectional processing. The main innovation is that the existence of the virtual decoder enables the transmission of external information. Under this new framework, we implement it with a minimum mean square error decision feedback equalizer (MMSE-DFE) and evaluate its performance across stationary channels and multipath fading channels. Simulation results demonstrate significant communication performance enhancement after three to four iterations, surpassing both conventional bidirectional and unidirectional equalization. In addition, the proposed TECC is verified through underwater acoustic communication in a sea trial. The results also demonstrate that the TECC achieves better bit error performance.

Upper limit of ice content at the lunar south pole as revealed by the Earth-based SYISR–FAST bistatic radar system - Mingyuan Li; Jinghai Sun; Xin’an Yue; Honglei Lin; Zhiqing Chen; Feng Ding; Baiqi Ning; Yong Wei; Chi Wang; Peng Jiang (Science Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Dabrafenib upregulates hypoglycosylated MUC1 and improves the therapeutic efficacy of Tn-MUC1 CAR-T cells - Ziwei Zhou; Yinghua Zhu; Jianli Zhao; Yiming Zhao; Wenkui Fu; Chao Zhou; Jinfang Hu; Yewen Zeng; Yiguang Lin; Hong An; Haibin Yin; Herui Yao; et al. (Science Bulletin, 2025)

Functional characterization of chemosensory proteins in three sympatric Tomicus bark beetles feeding on Pinus yunnanensis: Implication for the conservation and divergence of ligand-binding profiles - Lin-Mei Pu; Peng-Fei Wang; Yu-Yue Lu; An-Jin Yang; Li-Li Liu; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Development of an alkali-producing bioelectrochemical system for sewage-polluted seawater: nutrient removal, scalant mitigation, and resource recovery - Chao-Chin Chang; Chieh-Yun Wu; Jia-Zhe Jiang; Chen-An Hsu; Chang-Ping Yu; Yi-Li Lin (Journal of Water Process Engineering, 2025)

Regulation strategies of microplastics with different particle sizes on cadmium migration processes and toxicity in soil-pakchoi system - Qirui An; Na Zheng; Changcheng Chen; Xiaoqian Li; Yining Ji; Liyuan Peng; Zhifei Xiu; Qiuyan Lin (Journal of Hazardous Materials, 2025)

Research on combustion characteristics of new high energy composite materials − using tungsten powder as fuel and DAP-4 as oxidizer - Guangwei Xiao; Erhai An; Hua Fang; Xueli Zhang; Yingxin Tan; Lin Li; Peng Deng; Zhuoxin Fei; Xiong Cao (Fuel, 2025)

Fu brick tea supplementation ameliorates non-alcoholic fatty liver disease and associated endotoxemia via maintaining intestinal homeostasis and remodeling hepatic immune microenvironment - Gaolong Zuo; Menghua Li; Xiaoli Guo; Ling Wang; Yanyan Yao; Jian-an Huang; Zhonghua Liu; Yong Lin (Food Research International, 2025)

Enhanced uranium extraction from seawater using bifunctional-modified molecular sieves with high selectivity and adsorption capacity - Wen Guo; Zixin Lin; Kun Jiang; Hao Li; Xiangfeng Liang; Weizhong An; Huizhou Liu; Haiyan Luo; Haoyu Yao (Desalination, 2025)

Electrochemically enhanced adsorption of perfluorooctanoic acid (PFOA) on CuO-CNTs composite electrodes - Huan Lin; Yong-Lei Feng; Daying Lin; An-Guo Wang; Afzalshoh Qahramon Zarifzoda; Si Zhou; Fuming Chen; Guangguo Ying (Desalination, 2025)

Facile preparation of isolation columns filled with integral hybrid materials for efficient isolation of extracellular vesicles from microliter sample - Yujie Lin; Mengxi Chen; Yuanyuan Yu; Pengfei Xu; Fengyu Chen; Shenyue Zhou; Jiayu Xu; Wen Wu; Song Zhu; Yuxin An; Haiyang Zhang; Weipeng Wang (Analytica Chimica Acta, 2025)

Gastrodin Protects Neuronal Cells Against Oxidative Stress Through miRNA-125b-5p/Mamdc2 Axis - Lei Hu; Chao Lin; Renfu Li; Shouying Xu; Qiang Xu; Zihao An; Chao Tang (NeuroMolecular Medicine, 2025)

The impact of carbon emissions trading policy on low-carbon economic development in China: an empirical analysis based on the environmental triple effect - Yongkai Wang; Qiguang An; Ruoyu Wang; Yunpeng Ma; Lin Li (Environment, Development and Sustainability, 2025)

Solar evaporator coupled with strong/weak convection and its cascade utilization - Zhengtong Li; Jia-Han Zhang; Jing Zhang; Peng Yan; Tao Yang; Chao Yang; Peng Lin; Taotao Meng; Meng An; Yingtang Zhou; Xingtao Xu (Science Bulletin, 2025)

A robust Bayesian Multi-Machine learning ensemble framework for probabilistic groundwater level forecasting - Feilin Zhu; Yimeng Sun; Mingyu Han; Tiantian Hou; Yurou Zeng; Meiyan Lin; Yaqin Wang; Ping-an Zhong (Journal of Hydrology, 2025)

Long-term suppression of Microcystis aeruginosa by tannic acid: Risks of microcystin pollution and proteomic mechanisms - Li Yin; Kaipian Shi; Yu Yin; Yong Zhang; Lin Xu; Junfeng An; Chunqing Peng; Conghui Wang; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Journal of Hazardous Materials, 2025)

Urinary metabolic alterations associated with occupational exposure to metals and polycyclic aromatic hydrocarbons based on non-target metabolomics - Ping Lu; Rujian He; Yingjun Wu; Bizhi Wu; Hailing Li; Chang He; Meiqing Lin; Mengmeng Wang; Wenwen Cai; Xiantao Shen; Guiying Li; Zhiguo Cao; et al. (Journal of Hazardous Materials, 2025)

Effect of tertiary amine carbon quantum dots incorporation on oil/water separation performance of membranes - Gabriel V. Carballo; Hsin-Yi Lin; Pei-Chen Chen; Hong-Li Yang; Rhoda B. Leron; Chi-Lan Li; Hui-An Tsai; Kueir-Rarn Lee (Journal of Environmental Chemical Engineering, 2025)

Effects of residual carbon on slag flow characteristics of Zhundong high-alkali coal under oxy-fuel condition - Yuanmao Chen; Chang’an Wang; Maoyun Luo; Lin Zhao; Pengbo Zhao; Defu Che (Fuel, 2025)

Exploring calcium pillaring of O3-type NaNi0.9Ti0.1O2 cathodes to advance Na-ion battery technology - Siyu An; Leonhard Karger; Philipp Müller; Jing Lin; Sami Vasala; Volodymyr Baran; Sören L. Dreyer; Ruizhuo Zhang; Fatih Ulusoy; Aleksandr Kondrakov; Jürgen Janek; Torsten Brezesinski (Chemical Engineering Journal, 2025)

The herbicide 2,4-dichlorophenoxyacetic acid induces pancreatic β-cell death via oxidative stress-activated AMPKα signal downstream-regulated apoptotic pathway - Ken-An Lin; Chin-Chuan Su; Kuan-I Lee; Shing-Hwa Liu; Kai-Min Fang; Chih-Hsin Tang; Wei-Cheng Lia; Chun-Ying Kuo; Kai-Chih Chang; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology Letters, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Study on hydrocarbon retention and expulsion of kerogen based on centrifugal swelling method - Tian Liang; Feng Zhu; Zhao-Wen Zhan; Xiao-Hui Lin; Yan-Rong Zou; Ping’an Peng (Organic Geochemistry, 2025)

Uncovering toxin production and molecular-level responses in Microcystis aeruginosa exposed to the flame retardant Tetrabromobisphenol A - Li Yin; Yu Yin; Lin Xu; Yong Zhang; Kaipian Shi; Juan Wang; Junfeng An; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Journal of Hazardous Materials, 2025)

Resistance and propulsion trade-offs induced by different morphologies: Insights for fish conservation - Lin Sun; Jia Li; Min Chen; ChingHao Yu; Ruidong An (Journal of Environmental Management, 2025)

Carbonyl-amine condensation coupled ozonolysis of dipropylamine and styrene: Decay kinetics, reaction mechanism, secondary organic aerosol formation and cytotoxicity - Wanying Li; Jiangyao Chen; Qinhao Lin; Yuemeng Ji; Taicheng An (Journal of Environmental Sciences, 2025)

The thermal decomposition and combustion properties of DAP-4/FG composite materials - Guangwei Xiao; Erhai An; Xueli Zhang; Yingxin Tan; Tengyue Song; Lin Li; Peng Deng; Xiong Cao (Fuel, 2025)

Structural characterization of two poly-galacturonic acids: the important basis to elucidate spherical conformation of pectin from submicroparticles in chrysanthemum tea infusion - An Peng; Lianzhu Lin; Mouming Zhao (Food Chemistry, 2025)

Modifying pea protein by cold plasma for the development of functional vegan cheese - Bing-Fan Chuang; Sheng-Yi Chen; Jer-An Lin; Gow-Chin Yen (Food Bioscience, 2025)

Exploration of the regulatory mechanism of pulsed electric field on the aggregation behavior of soybean protein isolates - Rui Wang; Pei-Feng Guo; Jin-Peng Yang; Yan-Yan Huang; Lang-Hong Wang; Jian Li; Song-Yi Lin; Qing-Lin Sheng; Xin-An Zeng; Yong-Xin Teng (Food Hydrocolloids, 2025)

A novel MOF-on-MOF-derived carbon-encapsulated CeO2/Co/Co3O4 humidity-resistant heterojunction with abundant oxygen vacancies for efficient ozone removal - Abiyu Kerebo Berekute; An-Yu Wang; Kun-Yi Lin; Sepridawati Siregar; Kuo-Pin Yu (Environmental Research, 2025)

Ultrathin surface-amination-modified membrane with ion-charge shielding effect for ultraselective nanofiltration - Qiangqiang Song; Yuqing Lin; Ning Gan; Hussain Sadam; Yaguang An; Zheng Wang; Kecheng Guan; Junyong Zhu; Jing Wang; Yatao Zhang; Hideto Matsuyama (Desalination, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Production and evaluation of a bivalent adjuvant inactivated vaccine against infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus - Zhen Zhang; Chunyan Guan; Jingzhuang Zhao; Jingnan Lin; Yizhi Shao; Linfang Li; Tongyan Lu; Peng Chen; Yong-An Zhang; Liming Xu (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Effects of combustor wall temperature on the outer recirculation zone combustion modes transition in lean premixed DME/air swirling flames - Wenjun Lin; Weijie Zhang; Zhenhua An; Jinhua Wang; Zuohua Huang; Huangwei Zhang (Fuel, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Thermomechanically micronized sugar beet pulp: Elucidating the interaction of soluble elements and insoluble fibrous particles for enhancing emulsification - Jiawei Lin; Zhong Han; Xin-An Zeng (Food Hydrocolloids, 2025)

One-step open-ring strategy for constructing sandwich-like metal–organic framework with highly selective removal of thorium - Meng-Jie Yang; An-Min Song; Qing Yang; Zhi Wu; Bin Lin; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Indirect Z-scheme MXene@g-C3N4/MIL-101(Fe) heterojunction for the enhanced visible-light-responsive enrofloxacin photodegradation - Zhi-Fu Lin; Tzu-Heng Wang; Prashanth Venkatesan; Ruey-An Doong (Chemical Engineering Journal, 2025)

A bHLH transcription factor RrUNE12 regulates salt tolerance and promotes ascorbate synthesis - Zhenying Yang; Ling Lin; Min Lu; Wentao Ma; Huaming An (Plant Cell Reports, 2025)

An Improved RNA Extraction Method for Octocorals and Its Application in Transcriptome Analysis of Dark-Induced Bleaching Octocoral - Jing-Wen Michelle Wong; An-Chi Liu; Hsuan-Tung Lin; Chuya Shinzato; Sung-Yin Yang; Shan-Hua Yang (Marine Biotechnology, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

Shade watch: Mapping citywide shade dynamics through ray tracing and LiDAR data in Hong Kong's complex 3-D built environment - Shengbiao Wu; Bin Chen; Yimeng Song; Jiafu An; Chen Lin; Peng Gong (Sustainable Cities and Society, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

Molecular characteristics of organic matters in PM2.5 associated with upregulation of respiratory virus infection in vitro - Juying Lin; Wei Sun; Shuyi Peng; Yaohao Hu; Guohua Zhang; Wei Song; Bin Jiang; Yuhong Liao; Chenglei Pei; Jinpu Zhang; Jianwei Dai; Xinming Wang; et al. (Journal of Hazardous Materials, 2025)

Experimental study on characteristics and mechanism of hydrogen production from aluminium–water reaction for carbon-free power generation - Xinyue Gao; Chang’an Wang; Yujie Hou; Lin Zhao; Wengang Bai; Defu Che (Fuel, 2025)

Al-based metal-organic framework for piezocatalytic hydrogen peroxide production: Efficiency, pathway, and mechanism - Jiawei Huang; Haojie Dong; Lin An; Mingshan Zhu; Junhao Qin (Chemical Engineering Journal, 2025)

Mechanistic insights into the impact of calcium and magnesium ions on ferrous sulfide aggregation and reducing activity - Kaipian Shi; Li Yin; Junfeng An; Lin Xu; Chunqing Peng; Yong Zhang; Yuechun Zeng; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Using chondroitin sulfate lithium hydrogel for diabetic bone regeneration via regulation of macrophage polarization - Chenci Xu; Weiqi Li; Jing Mao; Ziyang Liu; An Lao; Lixia Mao; Anqi Gu; Jiaqing Wu; Aili Shen; Kaili Lin; Jiaqiang Liu (Carbohydrate Polymers, 2025)

Epigenetic Modifications as Novel Therapeutic Strategies of Cancer Chemoprevention by Phytochemicals - Hui-Hsia Hsieh; Min-Zhan Kuo; I-An Chen; Chien-Ju Lin; Victor Hsu; Wei-Chun HuangFu; Tien-Yuan Wu (Pharmaceutical Research, 2025)

The importance of porewater exchange process on carbon lateral export from saltmarsh creek to coastal sea - Jian’an Liu; Xueqing Yu; Xinyi Lin; Tong Peng; Liming Xue; Jinzhou Du (Journal of Oceanology and Limnology, 2025)

Molecular characterization of ovarian squamous cell carcinoma originating from mature teratoma - Angel Chao; Chyong-Huey Lai; An-Shine Chao; Chiao-Yun Lin; You-Chen Wang; Huei-Jean Huang; Ren-Chin Wu (Journal of Molecular Medicine, 2025)

Correction to: Effects of an intraoperative intravenous Bolus Dose of Dexmedetomidine on postoperative catheter-related bladder discomfort in male patients undergoing transurethral resection of bladder tumors: a randomized, double-blind, controlled trial - Tianhua Zhang; Huiting Li; Chunnan Lin; Rui An; Wenqian Lin; Hongying Tan; Longhui Cao (European Journal of Clinical Pharmacology, 2025)

Characterization and functional analysis of small heat shock protein gene HSP20.1 in Bombyx mandarina - Hui An; Jiaqi Ding; Enxi Chen; Ruonan Li; Mingjun Lin; Heying Qian; Guodong Zhao (International Journal of Tropical Insect Science, 2024)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Research on antibiotic resistance genes in wild and artificially bred green turtles (Chelonia mydas) - Xin Niu; Liu Lin; Ting Zhang; Xiaoyu An; Yupei Li; Yangfei Yu; Meiling Hong; Haitao Shi; Li Ding (Science of The Total Environment, 2024)

Modification of gut and airway microbiota on ozone-induced airway inflammation - Fei Xu; Qiong Wu; Lin Yang; Han Sun; Juan Li; Zhen An; Huijun Li; Hui Wu; Jie Song; Wen Chen; Weidong Wu (Science of The Total Environment, 2024)

Long-term subculture induces syncytialization and influent the response to bisphenol A (BPA) of placental JEG-3 cells - Yu-Shiuan Huang; Ai-An Chang; Zhi-Jie Yang; Jung-An Chen; Chi-Kang Lin; Hsin-Chieh Lan (Reproductive Toxicology, 2024)

Effect of steady boundary-layer flow on the hydrodynamic forces on a near-wall cylinder in currents - Yunfei Teng; Terry Griffiths; Liang Cheng; Yan Qu; Hongwei An; Scott Draper; Zhe Gao; Guoqiang Tang; Lin Lu (Ocean Engineering, 2024)

A metabolic roadmap of waxy corn flavor - Jingyun Luo; Chunmei He; Shijuan Yan; Chenglin Jiang; An Chen; Kun Li; Yongli Zhu; Songtao Gui; Ning Yang; Yingjie Xiao; Shenshen Wu; Fajun Zhang; et al. (Molecular Plant, 2024)

Tissue-specific distribution and fatty acid content of PFAS in the northern Bohai Sea fish: Risk-benefit assessment of legacy PFAS and emerging alternatives - Zhifei Xiu; Na Zheng; Qirui An; Changcheng Chen; Qiuyan Lin; Xiaoqian Li; Sujing Wang; Liyuan Peng; Yunyang Li; Huicheng Zhu; Siyu Sun; Shuai Wang (Journal of Hazardous Materials, 2024)

Unveiling the release mechanism of potentially toxic elements from Pb/Zn smelter contaminated soils under the coupled effects of freeze–thaw and acidification: Insights from mineralogical analysis - Da–Mao Xu; Bai–Hong An; Shao–Jun Jiang; Dong–Sheng Dai; Ze–Lin Xu; Lai Zhou; Xue–Qiang Zhu; Hong Yang; Rong–Bing Fu (Journal of Hazardous Materials, 2024)

Combining fermentation broth with spent water recycling for microalgae cultivation: Nutrient reutilization, biodiesel production and techno-economic simulation - Ruoyu Chu; Haolun An; Lefei Cai; Yu Chen; Guangming Zeng; Jie Yuan; Lin Tang (Journal of Cleaner Production, 2024)

Light driven depolymerization of tobacco waste: A multi-scale simulations - Jia-hao Wang; Xian-jie Zhang; Lin-can Fang; Wen-xian Chen; An-Fu Hu; Gui-lin Zhuang (Journal of Environmental Chemical Engineering, 2024)

Membrane modification in enhancement of virus removal: A critical review - Jie Zeng; Peter Desmond; Huu Hao Ngo; Wei Lin; Xiao Liu; Bingsheng Liu; Guibai Li; An Ding (Journal of Environmental Sciences, 2024)

Experimental study and chemical equilibrium calculation on the mineral transformation of high-alkali coal under oxy-fuel condition - Lin Zhao; Chang’an Wang; Yingchao Nie; Yongxu Chen; Jinming Zhang; Maoyun Luo; Defu Che (Fuel, 2024)

Effect of multi-processing technologies on the quality of sweet potato starch and associated starch pearl products - Min-Yu Lan; Jer-An Lin; Sheng-Yi Chen; Gow-Chin Yen (Food Bioscience, 2024)

Biochar addition mitigates asymmetric competition of water and increases yield advantages of maize–alfalfa strip intercropping systems in a semiarid region on the Loess Plateau - Shuai hou; Xingrong Sun; Guohao Chen; Kadambot H.M. Siddique; Zelin Chen; Fu Liu; Shiyu Ping; Hongtao Lai; Hongheng Guo; Yajing An; Zhiling Lin; Zhixin Zhang; et al. (Field Crops Research, 2024)

Di(2-ethylhexyl) phthalate disrupts circadian rhythm associated with changes in metabolites and cytochrome P450 gene expression in Caenorhabditis elegans - Pei-Ling Yen; Ting-An Lin; Chun-Han Chang; Chan-Wei Yu; Yu-Hsuan Kuo; Tzu-Ting Chang; Vivian Hsiu-Chuan Liao (Environmental Pollution, 2024)

Synergistic adsorption and photocatalytic degradation of ciprofloxacin in aqueous medium using advanced g-C3N4/MoS2 heterostructures - Preeti Pal; Zhi-Fu Lin; Ruey-An Doong (Chemical Engineering Journal, 2024)

Biodegradable bio-film based on Rhizopus oryzae and metal–organic frameworks for fruit preservation and pesticide degradation - Nan An; Xueting Zhu; Shiqi Xu; Xinhe Lin; Yingchun Zhu; MengYang Huang; Qing Xu; Feng Xue; Lina Wu (Chemical Engineering Journal, 2024)

Removal and recovery of nitrogen from anaerobically treated leachate based on a neglected HNAD nitrogen removal pathway: NH3 stripping - Facai An; Yunfei Gao; Maomin Yu; Tianxiao Xiao; Hui Lin; Dezhi Sun (Bioresource Technology, 2024)

SLC10A1 rs2296651 variant (S267F mutation) predicts biochemical traits, hepatitis B virus infection susceptibility and the risk of gallstone disease - Yu-Lin Ko; Wei-Lun Tuan; Ming-Sheng Teng; Wei-Chih Su; Chia‑Chi Wang; Leay-Kiaw Er; Semon Wu; Lung-An Hsu (Molecular Genetics and Genomics, 2024)

Perceptual information processing in table tennis players: based on top-down hierarchical predictive coding - Ziyi Peng; Lin Xu; Jie Lian; Xin An; Shufang Chen; Yongcong Shao; Fubing Jiao; Jing Lv (Cognitive Neurodynamics, 2024)

A highly specific two-photon fluorescent probe for real-time monitoring of acetylcholinesterase in neurogenic disorders in vivo - Weizhen An; Zhongxi Huang; Wei Jiang; Fangning Du; Chenfeng Xu; Qian Shen; Naidi Yang; Jia Zhou; Lin Li; Changmin Yu (Analytica Chimica Acta, 2024)

The Complete Mitochondrial Genome of Chilo infuscatellus (Lepidoptera: Pyralidae), and Related Phylogenetic Analysis - Jiequn Yi; Jianbai Liu; Yongkai Mao; Yinjie Cheng; Minjiang Lin; Hanliang Xu; Yuxing An; Jihu Li; Han Wu (Biochemical Genetics, 2024)

Beach erosion and typhoons reduce green turtle nesting grounds on the Xisha Islands, South China Sea - Ting Zhang; Chenglong Zhang; Yupei Li; Yangfei Yu; Xiaoyu An; Yongkang Jiang; Jichao Wang; Liu Lin; Hai-Tao Shi (Frontiers in Marine Science, 2024)
Introduction Sea turtles are ideal flagship and umbrella species for marine biodiversity conservation. The quality of nesting grounds is crucial for the successful reproduction of sea turtles, as it determines whether they can successfully nest and hatch. The Xisha Islands represent the largest remaining nesting grounds for green turtles in China. However, they face numerous threats and lack management guidelines for nesting ground restoration. Methods In this study, we continuously monitored the beach changes and coastal erosion on North Island, which is located in the northern region of the Xisha Islands, from 2019 to 2022. Results From 2020 to 2022, the beach area on North Island decreased annually by 11,800 m 2 , accounting for 24.39% of the beach area in 2020. The proportion of suitable nesting sand types (including coarse and medium sands) also decreased annually, with a reduction of 40–70% on the southern beach of North Island. The peak nesting period of green turtles on North Island coincides with the frequent occurrence of typhoons in the South China Sea, causing tidal surges that inundate green turtle nests, resulting in an average nest loss rate of 35.25%. Discussion Based on the above threats, it is recommended to promptly initiate habitat restoration in severely eroded areas of green turtle nesting grounds to prevent further declines in nesting area and quality. Additionally, measures such as nest relocation should be implemented to enhance green turtle reproductive success.

Social media-based multi-modal ensemble framework for forecasting soybean futures price - Wuyue An; Lin Wang; Yu-Rong Zeng (Computers and Electronics in Agriculture, 2024)

Genetic diversity, antibiotic resistance, and pathogenicity of Aeromonas veronii isolated from farmed largemouth bass (Micropterus salmoides) in the main aquaculture regions of China - Qikai Chen; Yunfei Xing; Yan Lei; Guixiang Tong; Xiaobu Lin; Pengcheng He; Shaolin Tang; Feifei Zheng; Hui Zeng; Xinxian Wei; Yong-An Zhang; Yang Zhou (Aquaculture, 2024)

Analysis of urban composite non-point source pollution characteristics and its contribution to river DOM based on EEMs and FT-ICR MS - Bingquan Lin; Xinqi An; Chen Zhao; Yahong Gao; Yuxuan Liu; Bin Qiu; Fei Qi; Dezhi Sun (Water Research, 2024)

Synthesis of hydrothermal carbonation carbon with tunable photocatalytic performance for trimethoprim degradation using an ethanol-water co-solvent strategy: Influence of ethanol concentration - Jiashuai Hu; Jie Chen; Xiaoling Liu; Jie Liang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Xiaochan An; Xiaobing Chen; Xiaojun Chen; Wei Chen; et al. (Journal of Cleaner Production, 2024)

Insights on aggregation-algae consortium based removal of sulfamethoxazole: Unraveling removal effect, enhanced method and toxicological evaluation - Yongtao Cheng; Yuanyuan Wu; Chuanyue Peng; Yang Yang; Liang Xuan; Lin Wang; Yan Wang; An Xu; Ying Liu (Journal of Environmental Management, 2024)

Corrigendum to “Anthropogenically-induced atmospheric Pb cycle in low-latitude Asia since the industrial revolution recorded by high-resolution stalagmites” [Global and Planetary Chang, 232 (2024) 104337] - Tianli Wang; Pei-Hsuan Yao; Chuan-Chou Shen; Sakonvan Chawchai; Adi Torfstein; Ashish Sinha; Hai Xu; Tsai-Luen Yu; Fangyuan Lin; Xiqian Wang; Dong Li; Hai Cheng; et al. (Global and Planetary Change, 2024)

Effects of physical sterilization on microbial safety, nutritional composition, and antioxidant activity of queen bee larva powder, a by-product of royal jelly production - Yu-Hsin Chen; Jer-An Lin; Chi-Chung Peng; Pei-Shou Hsu; Tzu-Hsien Wu; Yen-Hou Chen; Ming-Cheng Wu (Food Control, 2024)

A three-stage oxidation method improves sludge dewaterability by achieving sustained oxidation and phased enhanced coagulation: Ingeniously using H2O2 as a “converter” - Wei Lin; An Ding; Chuangxin Gong; Xiuxiang Ding; Peter Desmond; Piotr Oleskowicz-Popiel; Xu He; Jun Ma; Huu Hao Ngo (Chemical Engineering Journal, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

Hepatic and metabolic outcomes induced by sub-chronic exposure to polystyrene microplastics in mice - Sheng-Han Lee; Ting-An Lin; Yuan-Horng Yan; Chu-Chun Chien; Tsun-Jen Cheng (Archives of Toxicology, 2024)

Accumulation of persistent organic pollutants by MPs in coastal wastewater treatment plants - Jia-An Ye; Lin-Chi Wang; Ta-Kang Liu (Marine Pollution Bulletin, 2024)

Phthalate monoesters accumulation in residential indoor dust and influence factors - Qiuyan Lin; Na Zheng; Qirui An; Zhifei Xiu; Xiaoqian Li; Huicheng Zhu; Changcheng Chen; Yunyang Li; Sujing Wang (Science of The Total Environment, 2024)

Response of N, P, and metal ions in deep soil layers to long-term cultivation of rubber and rubber-based agroforestry systems - Chang-An Liu; Yu Nie; Jia-Lin Zhang; Jian-Wei Tang; Xin Rao; Kadambot H.M. Siddique (Science of The Total Environment, 2024)

Preparation of cementing material and recovery of iron resources using converter slag - Shuai Hao; Guoping Luo; Lin Wang; Shengli An; Yifan Chai; Wei Song (Process Safety and Environmental Protection, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Experimental investigation on the horizontal impact response of precast RC bridge piers with grouted sleeve connections considering defects - An He; Dun-Cong Zheng; Jian Cai; Qing-Jun Chen; Xu-Lin Tang; Jia-Bin Ye (Engineering Structures, 2024)

Analysis of two-dimensional consolidation behavior of soils under cyclic loading considering exacerbated tunnel leakage - Sen-Lin Xie; An-Feng Hu; Zhi-Rong Xiao; Mei-Hui Wang; Xun-Jian Hu; Gabriele Della Vecchia; Stefano Mariani (Computers and Geotechnics, 2024)

Large-area and high-efficiency carbon nanotube/silicon heterojunction solar cells enabled by self-similar fiber electrodes and solid-state gel electrolytes - Xian-Gang Hu; Bingsheng Li; Yi-Ming Zhao; An-Ping Wu; Zhenhua Lin; Peng-Xiang Hou; Chang Liu; Yue Hao; Jingjing Chang (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

NaCe0.7FX:Gd0.1,Tb0.2 nanoscintillator as a new sonosensitizer for potentiating cancer sonodynamic-immune therapy - Luyao Liu; Yuqi Yang; Yan Wang; Tian Qiu; Xingrun Li; Jiayuan Lin; Jin Wang; Xianwen Wang; Yan An; Xiaoyan Zhong; Jianxiang Li; Liang Cheng (Chemical Engineering Journal, 2024)

Smart glucose-responsive hydrogel with ROS scavenging and homeostasis regulating properties for diabetic bone regeneration - Ziyang Liu; Jing Mao; Weiqi Li; Chenci Xu; An Lao; Airi Shin; Jiaqing Wu; Anqi Gu; Zhen Zhang; Lixia Mao; Kaili Lin; Jiaqiang Liu (Chemical Engineering Journal, 2024)

Concentration characteristics and emission estimates of major HCFCs and HFCs at three typical fluorochemical plants in China based on a Gaussian diffusion model - Zehua Liu; Jing Wu; Tengfei Ma; Minde An; Tong Ye; Xingchen Zhao; Mingzhu Li; Fan Wang; Mao Yuan; Dongmei Hu; Yueling Zhang; Lin Peng (Atmospheric Environment, 2024)

Analysis of Torsional Mechanical Behavior of Adjustable Air Cushion Sole Structures: Impact Simulation on Cutting Maneuvers - Md Samsul Arefin; Chien-Ju Lin; Hsiao-Feng Chieh; Kai-Nan An; Ying-Chun Huang; Fong-Chin Su (Journal of Medical and Biological Engineering, 2024)

Amentoflavone Induces Ferroptosis to Alleviate Proliferation, Migration, Invasion and Inflammation in Rheumatoid Arthritis Fibroblast-like Synoviocytes by Inhibiting PIN1 - Yan Ma; Hongjun Lin; Yunman Li; Zhuoling An (Cell Biochemistry and Biophysics, 2024)

Retraction Note: Green supply chain, green leadership, consumer preferences, sustainability attitudes, and sustainable business advantage: a case of Vietnamese textile industry - Ka Yin Chau; Chen-Hsien Lin; Purevdulam Altantsetseg; Bushra Tufail; Thi Ha An Pham; Tran Thai Ha Nguyen (Environmental Science and Pollution Research, 2024)

Healthy lifestyles ameliorate an increased risk of periodontitis associated with polycyclic aromatic hydrocarbons - An Li; Yuntao Chen; Mi Du; Ke Deng; Xin Cui; Chunhua Lin; Geerten-Has E. Tjakkes; Xiaodong Zhuang; Shixian Hu (Chemosphere, 2024)

The impact of the urban landscape on PM2.5 from LCZ perspective: A case study of Shenyang - Ye Lin; Xin An; Jingcheng Yuan; Jing Yuan; Boyu Chen (Urban Climate, 2024)

MCT1-mediated transport of valeric acid promotes porcine preimplantation embryo development by improving mitochondrial function and inhibiting the autophagic AMPK-ULK1 pathway - Xiu-Li Zhang; Zhi-Yong An; Gao-Jie Lu; Tuo Zhang; Cheng-Wei Liu; Meng-Qi Liu; Qing-Xin Wei; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Heterostructure g-C3N4/Bi2MoO6 PVDF nanofiber composite membrane for the photodegradation of steroid hormone micropollutants - Zhi-Fu Lin; Han-Ya Lin; Ruey-An Doong; Andrea I. Schäfer (Journal of Hazardous Materials, 2024)

Carbon footprint of fresh sea cucumbers in China: Comparison of three aquaculture technologies - Lin Yang; Dong An; Yuhu Cui; Xuexiu Jia; Dong Yang; Wensheng Li; Yanliang Wang; Longjie Wu (Journal of Cleaner Production, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Cation-vacancy-rich NiFe2O4 nanoparticles embedded in Ni3Se2 nanosheets as an advanced catalyst for oxygen evolution reaction - Baoxin Wu; Zijie Zhang; Yan Hu; Jia Liu; Xiaohong Zou; Qing Zhang; Kejun Yan; Shibo Xi; Guanxiong Wang; Xiao Zhang; Lin Zeng; Liang An (Chemical Engineering Journal, 2024)

Integration of surface-based and space-based atmospheric CO2 measurements for improving carbon flux estimates using a new developed 3-GAS inversion model - Shu'an Liu; Xiaofeng Pan; Xiangyun Xiong; Tianle Sun; Lin Xue; Huifang Zhang; Junjun Fang; Jingchun Fang; Guchun Zhang; Hui Xu; Baozhang Chen (Atmospheric Research, 2024)

Early-onset and later-onset cancer: trends, risk factors, and prevention in Northern China - Tong Liu; Chen-An Liu; Qing-Song Zhang; Qi Zhang; Yi-Ming Wang; Meng-Meng Song; Shi-Qi Lin; Li Deng; Shou-Ling Wu; Han-Ping Shi (Science China Life Sciences, 2024)

Enhancement of beneficial microbiomes in plant–soil continuums through organic fertilization: Insights into the composition and multifunctionality - Wen-Jing Li; Xin-Yuan Zhou; Xin-Li An; Li-Juan Li; Chen-Shuo Lin; Hua Li; Hong-Zhe Li (Soil Ecology Letters, 2024)

Highly efficient treatment of tetracycline using coupled electro-Fenton and electrocoagulation process: Mechanism and toxicity assessment - Feng Yan; Xin Xu; Lili An; Wenjun Du; Wendi Shen; Kun-Lin Yang; Jianfeng Ye; Ruihua Dai (Chemosphere, 2024)

High-value utilization of boron mud waste: preparation of magnesium oxysulfate cement after primary blank roasting and secondary (NH4)2SO4 roasting - Jing Wen; Hongyu Sui; Tao Jiang; Lin Li; Xinyu An (Process Safety and Environmental Protection, 2024)

Vibration controlling effect of tuned liquid column damper (TLCD) on support structural platform (SSP) - Mi-An Xue; Jing Yang; Xiaoli Yuan; Zhimei Lu; Jinhai Zheng; Pengzhi Lin (Ocean Engineering, 2024)

Northward expansion of the West Kunlun orogenic belt during the Cenozoic and its implications for the evolution of the northwest Tibetan Plateau: Constraints from sediment dispersal patterns in the Buya Basin, China - Shujun Liang; Xiubin Lin; Chunyang Li; Xiaochun Wei; Yang Qu; Kaixuan An; Cai Chen; Xianzhang Yang; Yong Li; Liang Zhang; Jiangwei Shang; Li Li; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

New simple method for calculating large-strain consolidation settlement of layered soft soils with horizontal drains and vacuum preloading with comparison to test data - Ze-jian Chen; Peng-lin Li; An Li; Jian-hua Yin; Ding-bao Song (Geotextiles and Geomembranes, 2024)

Dynamic mechanism of CO2 capture from flue gas via hydrate-based method induced by using IB group transition metal functionalized carbon nanotubes - Fang Wang; Wenjing Lin; Jinchi Mu; Xiaosheng An; Ruiyang Zhang; Lihong Guo; Ying Zhou (Gas Science and Engineering, 2024)

Rapid differential diagnosis of periprosthetic joint infection by microdroplet reaction on portable biochip and indicator - Zheng Liu; Jimei Chi; Zewei Lian; Yaqi Yang; Lijun Cheng; Xiaoxue Lin; Xuwei He; Xiaojian Ji; Chenxuan Yang; Yunhao Tang; Minzhi Yang; Zhisen Gao; et al. (Chemical Engineering Journal, 2024)

Designers' guided site shading strategies: A simplified model for radiative cooling - Zih-An Lin; Cing Chang; Tzu-Ping Lin (Building and Environment, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Novel GaN-Based Substrates with Gold Nanostructures for Ultra-Sensitive SERS Analysis: Micro-Nano Pit Morphology for Enhanced Molecular Detection - Tsung-Shine Ko; Chen-An Deng; Jiann Shieh; Hung Ji Huang; Yung-Sheng Lin; Yang-Wei Lin; Yi-Chun Du (Journal of Medical and Biological Engineering, 2024)

Interdecadal variability of winter and spring Eurasian snow depth and its impact on Eastern China precipitation - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Chan Wang; Hao Chen; Lunyu Shang; Shaoying Wang; Yumeng Liu; Hanhui Zhu (Climate Dynamics, 2024)
Empirical orthogonal function (EOF) and correlation analyses were employed to investigate the winter and spring snow depth in Eurasia and its relationship with Eastern China precipitation based on the observed and reanalyzed data from 1980 to 2016. The results show that the winter and spring snow cover in Eurasia not only highlights a decreasing trend due to global warming (the first EOF mode, its variance accounted for 24.4% and 22.6% of the total variance) but also exhibits notable interdecadal variation (the second EOF mode, its variance accounted for 10.2% and 11.5% of the total variance). The second EOF mode of winter snow depth in Eurasia is characterized by a west-east dipole pattern. It was observed that the spatial correlation pattern between the EOF2 of Eurasian snow depth and summer precipitation in China closely resembles the meridional quadrupole structure of the third EOF mode of summer precipitation in China. This pattern is characterized by excessive rainfall in Northeast China and the lower-middle reaches of the Yangtze River, and less rainfall over the Yellow River basin and southern China. The EOF mode of spring snow depth not only reflects the declining trend but also regulates precipitation in Eastern China. The possible mechanisms by which snow depth causes changes in soil moisture and subsequently affects atmospheric circulation are then explored from the perspective of the hydrological effects of snow cover. Decreased (Increased) snow depth in Eurasia during the winter and spring directly leads to diminished (increased) soil moisture while increasing (decreasing) net radiation and sensible heat flux at the surface. The meridional distribution of surface temperature also exhibits a dipole pattern, leading to enhanced subtropical westerly jet in the upper troposphere. The Eurasian snow cover anomalies pattern triggered an anomalous mid-latitude Eurasian wave train, which strengthened significantly in the Western Siberian Plain. It then splits into two branches, one continuing to propagate eastward at high latitudes and the other shifting towards East Asia, thereby impacting precipitation in Eastern China. This work indicates that the second EOF mode of Eurasian snow cover can impact the precipitation variability in Eastern China during the same period and in summer on an interdecadal scale.

Establishing Virtual Bioequivalence and Clinically Relevant Specifications for Omeprazole Enteric-Coated Capsules by Incorporating Dissolution Data in PBPK Modeling - Ruwei Yang; Yaqi Lin; Kaifeng Chen; Jie Huang; Shuang Yang; An Yao; Xiaoyan Yang; Deqing Lei; Jing Xiao; Guoping Yang; Qi Pei (The AAPS Journal, 2024)

Smoke diffusion mechanism and mitigation design for fire accidents in a tunnel-groove structure of a large hydropower station - Ruinan An; Peng Lin; Chang Liu; Maohua Zhong; Zichang Li; Wenfu Chen; Yong Xia (Tunnelling and Underground Space Technology, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

Intelligent chemical profiling of 73 edible flowers by liquid chromatography-high resolution mass spectrometry combined with HRMS database and their authentication based on large-scale fingerprints - Ziqing Li; Jianqing Zhang; Lin Yang; Xiaolan Li; Qian Meng; Yun Li; Shuai Yao; Wenlong Wei; Qirui Bi; Hua Qu; Yaling An; De-an Guo (Food Chemistry, 2024)

Attitude inversion of space debris based on the laboratory-tested photometry dataset - Shu-Shu Wang; Hou-Yuan Lin; An-Ming Kang; Jin-Rui Men; Chang-Yin Zhao (Advances in Space Research, 2024)

Differential bioaccumulation and tolerances of massive and branching scleractinian corals to polycyclic aromatic hydrocarbons in situ - Xiaocong Cao; Licheng Wang; Jiamin Lin; Guowen Wu; Kai Tang; Jia Tang; Zhicong Yan; Mingxun An; Zhaoqun Liu; Zhi Zhou (Science of The Total Environment, 2024)

Long-term species-level observations indicate the critical role of soil moisture in regulating China's grassland productivity relative to phenological and climatic factors - Shuai An; Xiaoqiu Chen; Fangjun Li; Xuhui Wang; Miaogen Shen; Xiangzhong Luo; Shilong Ren; Hongfang Zhao; Yan Li; Lin Xu (Science of The Total Environment, 2024)

Multifaceted impacts of Ukraine’s Kakhovka Dam destruction - Bin Chen; Jiafu An; Yufei Huang; Xidong Chen; Shengbiao Wu; Chen Lin; Peng Gong (Science Bulletin, 2024)

Can drinking tea become an effective way to alleviate the extraintestinal manifestations of inflammatory bowel disease: A comprehensive review - Yong Lin; Siling Xie; Lizheng Xiao; Zhenyun Liu; Wanping Ke; Jian-an Huang; Zhonghua Liu; Wei Quan (Food Bioscience, 2024)

Extending the freshness of tilapia surimi with pulsed electric field modified pea protein isolate-EGCG complex - Zhong Han; Ze-Ling Chen; Xin-Dong Xu; Songyi Lin; Yan Wang; Lang-Hong Wang; De-Bao Niu; Xin-An Zeng; Meng-Wai Woo; Ruo-Yong Wang (Food Hydrocolloids, 2024)

From theory to practice: Dissociation of AsMA under reactive metal perturbations for the harmlessness and resourcefulness of copper slag - Xingyuan Wan; Kaixi Jiang; Ting'an Zhang; Kun Wang; Han Yang; Shengnan Lin (Chemical Engineering Journal, 2024)

Engineering ZIF-67 loaded nanofibrous membrane with thermal stabilization treatment for efficient photocatalytic CO2 reduction - Pengfei Lin; Xiwei Qu; Bhaskar Jyoti Deka; Chao Hu; Lei Zhao; Dongyun Wu; Chunhai Yi; Min Wei Boey; Muhammad Usman Farid; Alicia Kyoungjin An; Jiaxin Guo (Chemical Engineering Journal, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

Metabolomic profiling of maternal plasma identifies inverse associations of acetate and urea with anti-SARS-CoV-2 antibody titers following COVID-19 vaccination during pregnancy - An-Shine Chao; Chiao-Yun Lin; Meng-Han Chiang; Kuan-Ying Lu; Cheng-Kun Tsai; Kuan-Ju Chen; Chih-Wei Chien; Ting-Shu Wu; Yao-Lung Chang; Angel Chao; Gigin Lin; Chih-Yung Chiu (Journal of Molecular Medicine, 2024)

Neuropsychiatric comorbidities in tuberous sclerosis complex patients with epilepsy: results of the TAND checklist survey - Hom-Yi Lee; Chien-Heng Lin; Xing-An Wang; Jeng-Dau Tsai (Acta Neurologica Belgica, 2024)

Evaluation of marine economic development demonstration zone policy on marine industrial structure optimization: a case study of Zhejiang, China - Yuhu Cui; Hanxiao Xu; Dong An; Lin Yang (Frontiers in Marine Science, 2024)
The marine economic development demonstration zone (MEDDZ) is the regional marine functional policy that assumes the significant tasks of innovation in the system and mechanism of the marine economy, optimization of the marine industrial structures, and the construction of marine ecological civilization. This paper constructs a panel database of 11 coastal provinces in China from 2006 to 2019, takes the Zhejiang Marine Economy Development Demonstration Zone Plan officially approved by the State Council of China in 2011 as a quasi-natural experiment, applies the synthetic control method (SCM) to evaluate the effect of implementation of the MEDDZ policy on marine industrial structure optimization in Zhejiang. The results show that: (1) The MEDDZ policy significantly promotes the structure optimization of the marine industry in Zhejiang and the existence of the policy lag phenomenon. (2) Based on the results of the robustness tests, we find that the fitted path of policy effects is better when the time of MEDDZ implementation is adjusted to 2012. (3) Government financial support and marine cargo capacity play a role in implementing the MEDDZ policy, positively affecting and optimizing the coastal marine industry’s structure. Therefore, we make some suggestions from the perspectives of strengthening the policy implementation process, focusing on the policy lag phenomenon, and broadening funding sources, thus enriching theoretical research on policies in the field of the marine industry and providing practical references for the development of other coastal demonstration zones.

Climate change, corporate risk-taking, and financialization: evidence from Chinese A-share non-financial listed companies - Lin Zheng; Qiguang An; Mu Yang (Environment, Development and Sustainability, 2024)
Climate change-induced risks, such as global warming, can affect the economic development of entities and, consequently, the stability of financial markets. Businesses are progressively making the transition to green in order to lessen the negative consequences of climate threats. This study examines the relationship between corporate risk-taking (CRISK) and financialization (FIN) in light of climate change. The impact of business risk-taking on financialization is experimentally investigated through the transmission chain of “CRISK - enterprise value – FIN” using a fixed-effects model. The study also analyzes the moderating effect of climate change on the direct and indirect channels of climate change by using “temperature” and “investors’ concern about climate,” respectively. In addition, the empirical results are tested for robustness using propensity score matching and an instrumental variable method. This study’s findings reveal the following key insights. First, CRISK significantly enhances FIN by improving firm value. Second, enterprises with high financing constraints and manufacturing enterprises are more likely to have a positive correlation between CRISK and FIN. Third, the relationship between CRISK and FIN is enhanced by the direct transmission channel of increasing climate risk, but the indirect transmission channel is not significant. This study proposes policy recommendations to address the effect of climate risk on CRISK and FIN. Among these suggestions are the prudent distribution of financial resources among enterprises according to their level of risk-taking and the reinforcement of regulatory authorities’ financial oversight of businesses with high financing constraints and the manufacturing sector. By implementing these policies, companies can better manage climate-related risks and contribute to financial stability.

Hybrid attention network for citrus disease identification - Fukai Zhang; Xiaobo Jin; Gang Lin; Jie Jiang; Mingzhi Wang; Shan An; Junhua Hu; Qiang Lyu (Computers and Electronics in Agriculture, 2024)

Direct aqueous photochemistry of methylglyoxal and its effect on sulfate formation - Jie Tan; Lingdong Kong; Yuwen Wang; Beibei Liu; Yixuan An; Lianghai Xia; Yu Lu; Qing Li; Lin Wang (Science of The Total Environment, 2024)

Effects of SO2 and H2O on the ash deposition and NO emission during oxy-fuel combustion of high-alkali coal - Lin Zhao; Chang’an Wang; Tianlin Yuan; Liangxu Dai; Yingchao Nie; Guowei Ma; Lei Zhou; Maoyun Luo; Defu Che (Process Safety and Environmental Protection, 2024)

Calorimetric and kinetic evaluation of thermal stability and process safety in tert-butyl peroxy-2-ethylhexanoate and tert-butyl peroxybenzoate - Hai-Lin Zhou; Jun-Cheng Jiang; An-Chi Huang (Process Safety and Environmental Protection, 2024)

Sustained oxidation of Tea-Fe(III)/H2O2 simultaneously achieves sludge reduction and carbamazepine removal: The crucial role of EPS regulation - Wei Lin; Renglu Chen; Chuangxin Gong; Peter Desmond; Xu He; Jun Nan; Guibai Li; Jun Ma; An Ding; Huu Hao Ngo (Journal of Hazardous Materials, 2024)

'Environmental standard limit concentration' arsenic exposure is associated with anxiety, depression, and autism-like changes in early-life stage zebrafish - Yuanhui Zhu; Qianlei Yang; Jie Gu; Zhicheng Chen; Nan Jing; Tingxu Jin; Jiayuan Lin; Xin Wang; Jingwen Hu; Guixiang Ji; Yan An (Journal of Hazardous Materials, 2024)

Corrigendum to “An end-to-end approach to predict physical properties of heterogeneous porous media: Coupling deep learning and physics-based features” [Fuel 352 (2023) 128753] - Yuqi Wu; Senyou An; Pejman Tahmasebi; Keyu Liu; Chengyan Lin; Serveh Kamrava; Chang Liu; Chenyang Yu; Tao Zhang; Shuyu Sun; Samuel Krevor; Vahid Niasar (Fuel, 2024)

Experimental study on metal removal characteristics of Zhundong coal to produce ultra-clean coal using acid-alkali method - Yuanmao Chen; Chang'an Wang; Yang Li; Maoyun Luo; Chenglong Yang; Lin Zhao; Zhefan Wang; Ning Fu; Defu Che (Fuel, 2024)

Synthesis and characterization of a host–guest complex based on acetylated-β-cyclodextrin and its application in improving the viscosity of supercritical carbon dioxide - Wei-An Huang; Rui Su; Jing-Wen Wang; Yu Fan; Lin Jiang; Xuan Li; Jie Cao (Fuel, 2024)

Preferentially in-situ generated copper nanograins boosting fast kinetic conversion magnesium storage of bimetallic copper-cobalt sulfide cathode - Yaping Xia; Chunxiao Chen; Lin Ran; Hou-an Zhang; Shuai Cui; Panfei Xiao; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2024)

Boosting the electrochemical performance of LiCoO2 by triple-phase interface via “island-bridge” shaped surface coating - Yu-Wei Zhao; Wei Zeng; Sheng-Qi Su; Si-Dong Zhang; Si-Jie Guo; Jian-Hua Qiu; Yong-Gang Sun; An-Min Cao; Xi-Jie Lin (Chemical Engineering Journal, 2024)

Construction of anticorrosive coatings with emergency response closure by introducing functionalized graphene oxide - Yuxuan Huang; Shaoheng Yang; Yang Hu; Haojun Lin; Jiesheng Tang; Chang-An Xu; Zhuohong Yang (Chemical Engineering Journal, 2024)

A novel brain targeting MnOx-based MI-3 nanoplatform for immunogenic cell death initiated high-efficiency antitumor immunity against orthotopic glioblastoma - Xuejie Wang; Zhanfeng Wang; Ping'an Ma; Sainan Liu; Meifang Wang; Ping Chen; Binbin Ding; Jun Lin (Chemical Engineering Journal, 2024)

Gelsenicine disrupted the intestinal barrier of Caenorhabditis elegans - Zekai Wu; Jian Zhang; Yajiao Wu; Mengting Chen; Hong Hu; Xinyue Gao; Chutao Li; Maodong Li; Youbo Zhang; Xiaohuang Lin; Qiaomei Yang; Li Chen; et al. (Chemico-Biological Interactions, 2024)

Blockade of aryl hydrocarbon receptor restricts omeprazole-induced chronic kidney disease - Nan Sun; Yimeng Zhang; Lin Ding; Xin An; Fang Bai; Yanjiang Yang; Kuipeng Yu; Jiahui Fan; Lei Liu; Huimin Yang; Xiangdong Yang (Journal of Molecular Medicine, 2024)

Impacts of physical parameterization scheme of snow and soil properties over the Tibetan Plateau on the simulation of summer rainfall in China - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Chan Wang; Hao Chen; Lunyu Shang; Shaoying Wang; Shiwen Wang; Yumeng Liu (Climate Dynamics, 2024)
Accurate representation of soil and snow state variables in the land surface model is crucial for good simulation results. In order to investigate the potential impacts of the overestimated snow cover over the Tibetan Plateau (TP) on precipitation over China, we designed comparative experiments over TP with and without updated soil texture data, soil hydrological parameters, and the fresh snow density scheme to address this issue with the Weather Research and Forecasting Model (WRF). The results show that snow cover fraction (SCF) and surface albedo in winter on the TP were overestimated in the WRF control experiment (CTL), with albedo bias exceeding 0.4 in the western TP. The SCF in the WRF improved experiment (WRFIM) is about 8% lower than that of the CTL, and the bias is decreased to 0.2–0.3 in the interior of the TP. The thermal and dynamic effects of the TP in winter have a significant impact on the weather and climate of East Asia during summer. Thus, the simulated summer rainfall bias is significantly reduced by WRFIM in North China, and the mid-lower reaches of the Yangtze River, along with the spatial correlation coefficient between the observed-based and WRF-simulated rainfall increased from 0.76 in CTL to 0.88 in WRFIM. The WRFIM-simulated reductions in snow cover and albedo cause a decrease in upward shortwave radiation and eventually increase net surface radiation. The horizontal temperature gradient of the atmosphere is increased in the WRFIM compared to the CTL, and the increased temperature in the lower and middle layers accommodates more water vapor, which is not conducive to precipitation formation. Correspondingly, the Western Pacific Subtropical High at 500 hPa in the middle troposphere weakened. The low-level anticyclonic circulation at 850 hPa also weakened to the east, affecting water vapor transport in eastern China. It leads to a decrease in the water vapor transported northward by southeasterly from the western Pacific Ocean and a decrease in the water vapor flux reaching North China. This work indicates that accurate characterization of soil properties and snow cover on the TP is crucial for improving the simulation bias of summer rainfall in China.

Distribution Patterns of Grey Mullet in the Taiwan Strait in Relation to Oceanographic Conditions - Sheng-Yuan Teng; Sandipan Mondal; Quang-Huy Lu; Platinasoka Lin; Ming-An Lee; Louis George Korowi (Journal of Marine Science and Engineering, 2024)
The depletion of the grey mullet population in the Taiwan Strait has generated interest in conservation initiatives and to enhance the effectiveness of restoration initiatives, it is essential to comprehend the specific habitat preferences of the species in question, particularly in relation to environmental changes. In this study, habitat suitability modelling was used to investigate the distribution patterns of grey mullet. Sea surface height (SSH) was the most significant predictor of the grey mullet standardized catch per unit effort (S.CPUE). Furthermore, sea surface temperature (SST) was the second most important oceanographic parameter, followed by mixed-layer depth (MLD). The grey mullet S.CPUE peaked in regions with the summed SST, Chla, salinity, SSH, MLD and current values being 20 °C, 0.9 mg/m3, 34.5 psu, 0.45 m, 18–38 m, and 0.25 m2/s2, respectively. From late October, HSI levels in the northern Taiwan ocean increased, with a consistent upward trend. The distribution expanded in November and December, focusing on the northern and mid-ocean regions west of Taiwan. HSI levels peak in January and February, especially in Taiwan’s coastal region. High HSI distribution shifts away from coastlines and diminishes in April. The findings of this study will contribute to the understanding of this specific species and the approach used in this study may be applicable to other fisheries stocks also.

PI3K/AKT mediated De novo fatty acid synthesis regulates RIG-1/MDA-5-dependent type I IFN responses in BVDV-infected CD8+T cells - Shan-shan Liu; Tong-tong Bai; Tao-lin Que; An Luo; Yu-xin Liang; Yu-xin Song; Tian-yi Liu; Jin-wei Chen; Jing Li; Nan Li; Ze-chen Zhang; Nan-nan Chen; et al. (Veterinary Microbiology, 2024)

Efficacy and mechanism of copper removal from electroplating wastewater by schwertmannite-like mineral - Ni Li; Mingyan Shi; Yimiao Lan; Hongguo Zhang; Guanfeng An; Shaonan Lin; Langming Xue (Journal of Environmental Chemical Engineering, 2024)

Atmospheric VOCs in an industrial coking facility and the surrounding area: Characteristics, spatial distribution and source apportionment - Meicheng Wen; Weiqiang Deng; Jin Huang; Shu Zhang; Qinhao Lin; Chao Wang; Shengtao Ma; Wanjun Wang; Xin Zhang; Guiying Li; Taicheng An (Journal of Environmental Sciences, 2024)

Pulsed electric field (PEF) activates immune activity in RAW 264.7 macrophages by altering pine nut peptide-TLR4 binding sites - Shuyu Zhang; Chuwen Mao; Ruowen Liu; Xin-an Zeng; Songyi Lin (Food Bioscience, 2024)

Microbiological mechanisms of sludge property variations under long-term landfill: From micro-omics perspective - Yunxin Xing; Ying An; Lifeng Lin; Peng Peng; Xiaolu Gong; Weijie Hu; Yuqing Ren; Zihang Ma; Jiafu Xi; Jing Cao; Ziyang Lou; Zhen Zhou (Chemical Engineering Journal, 2024)

Morphology and chemical composition of Taiwan oil millet (Eccoilopus formosanus) epicuticular wax - Marita Anggarani; Yu-Ying Lin; Shao-An Fang; Hshin-Ping Wu; Chi-Chih Wu; Wann-Neng Jane; Thomas James Roscoe; Frederic Domergue; Yue-Ie Caroline Hsing (Planta, 2024)

PCSK9 regulates myocardial ischemia–reperfusion injury through parkin/pink1-mediated autophagy pathway - Guangwei Huang; Hailong Bao; Peng Zhan; Xiyang Lu; Zonggang Duan; Xinlin Xiong; Muzhi Lin; Bing Wang; Hongxin An; Luanda Xiahou; Haiyan Zhou; Zhenhua Luo; et al. (Molecular & Cellular Toxicology, 2024)

Synergistic Effects of Bay of Bengal Tropical Cyclones and Tibetan Plateau Vortices on Water Vapor Transport over the Tibetan Plateau in Early Summer - Jialu Lin; Ying Li; Beiyao Liu; Pengchao An (Journal of Meteorological Research, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Review: The application of source analysis methods in tracing urban non-point source pollution: categorization, hotspots, and future prospects - Bingquan Lin; Fei Qi; Xinqi An; Chen Zhao; Yahong Gao; Yuxuan Liu; Yin Zhong; Bin Qiu; Zhenbei Wang; Qian Hu; Chen Li; Dezhi Sun (Environmental Science and Pollution Research, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

Satellite observations reveal a decreasing albedo trend of global cities over the past 35 years - Shengbiao Wu; Xingwen Lin; Zunjian Bian; Mathew Lipson; Raffaele Lafortezza; Qiang Liu; Sue Grimmond; Erik Velasco; Andreas Christen; Valéry Masson; Ben Crawford; Helen Claire Ward; et al. (Remote Sensing of Environment, 2024)

4,5-Difluoro-1,3-dioxolan-2-one as a film-forming additive improves the cycling and thermal stability of SiO/C anode Li-ion batteries - Yong-Qi Wang; Lin-Jie Xie; Hui-Qi Sun; Xiang Wang; Hai-Lin Zhou; Yan Tang; Jun-Cheng Jiang; An-Chi Huang (Process Safety and Environmental Protection, 2024)

Natural product-derived ferroptosis mediators - Yi-Li Chen; Lin-An Xiong; Lie-Feng Ma; Luo Fang; Zha-Jun Zhan (Phytochemistry, 2024)

Visible light-driven Cl-g-C3N4 activated peroxydisulfate process for TMP efficient degradation in a wide pH range - Jie Chen; Jiashuai Hu; Yuanmao Lin; Xiaoling Liu; Jie Liang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Xiaochan An; Xiaobing Chen; Xiaojun Chen; et al. (Journal of Water Process Engineering, 2024)

Improving the phosphorus bioavailability of sludge: Comparison of oxidation treatments based on Mn(VII)-Fe(III) catalysis - Chuangxin Gong; Wei Lin; Peinong Chen; Peter Desmond; Xu He; Huu Hao Ngo; An Ding (Journal of Water Process Engineering, 2024)

Effect of EDDS on the rhizosphere ecology and microbial regulation of the Cd-Cr contaminated soil remediation using king grass combined with Piriformospora indica - Haixiang Zhang; Kailu Zhang; Yali Duan; Xiaoyan Sun; Li Lin; Qianli An; Muhammad Mohsin Altaf; Zhiqiang Zhu; Fan Liu; Yangqiu Jiao; Jing Yin; Can Xie; et al. (Journal of Hazardous Materials, 2024)

Natural deep eutectic solvent: A promising eco-friendly food bio-inspired antifreezing - Xue Li; Jia-Ying Li; Muhammad Faisal Manzoor; Qiu-Ya Lin; Jia-ling Shen; Lan Liao; Xin-An Zeng (Food Chemistry, 2024)

Global meta-analysis and three-year field experiment shows that deep placement of fertilizer can enhance crop productivity and decrease gaseous nitrogen losses - Peng Wu; Qi Wu; Hua Huang; Lin Xie; Haoyuan An; Xintong Zhao; Fangtao Wang; Ziting Gao; Ruiting Zhang; Kemoh Bangura; Jianfu Xue; Min Sun; et al. (Field Crops Research, 2024)

Highly efficient activation of peroxymonosulfate by ZIF-67 anchored cotton derived for ciprofloxacin degradation - Yong Xiao; Jiahong He; Jibin An; Taiping Xie; Junjie Lin (Environmental Research, 2024)

Risk assessment of pesticide compounds: IPT and TCZ cause hepatotoxicity, activate stress pathway and affect the composition of intestinal flora in red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wei-Ren Dong; Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Guang-Xu Liu; Miao-An Shu (Environmental Pollution, 2024)

K-promoted Ru-based heterogeneous catalysts for ethylene hydroformylation - Dinghao Cui; Tingting Qin; Tiejun Lin; Jingrui Ti; Yunlei An; Liangshu Zhong (Chemical Engineering Journal, 2024)

Acoustoelectric materials & devices in biomedicine - Xinyue Zhang; Yihe Zhang; Jiahe Zhang; Jing Shang; Liping Lin; Qi Liu; Qi An (Chemical Engineering Journal, 2024)

Cathepsin B degrades RbcL during freezing-induced programmed cell death in Arabidopsis - Gang Yang; Tao Chen; Ting-ting Fan; Xiang-yu Lin; Yu-qiong Cui; Wei-chao Dong; Li-zhe An; Hua Zhang (Plant Cell Reports, 2024)

Integrating water and insect pest management in agriculture - Po-An Lin; Sulav Paudel; Pin-Chu Lai; Raj K. GC; Dan-Hong Yang; Gary W. Felton (Journal of Pest Science, 2024)

The two-back task leads to activity in the left dorsolateral prefrontal cortex in schizophrenia patients with predominant negative symptoms: a fNIRS study and its implication for tDCS - Chin-Chao Ma; Yen-Yue Lin; Yong-An Chung; Sonya Youngju Park; Cathy Chia-Yu Huang; Wei-Chou Chang; Hsin-An Chang (Experimental Brain Research, 2024)

Effects of an intraoperative intravenous Bolus Dose of Dexmedetomidine on postoperative catheter-related bladder discomfort in male patients undergoing transurethral resection of bladder tumors: a randomized, double-blind, controlled trial - Tianhua Zhang; Huiting Li; Chunnan Lin; Rui An; Wenqian Lin; Hongying Tan; Longhui Cao (European Journal of Clinical Pharmacology, 2024)

Prevalence and distribution of antibiotic-resistant bacteria in the rhizosphere and rhizoplane of Suaeda salsa and Sporobolus alterniflorus grown in a pristine environment - Yu Wang; Fang Yang; Qianwen Liu; Lin Sun; Weihua Chen; Qingfeng Yu; Chenglong Pan; Guanhong Jiang; Xin'an Jiao; Yunzeng Zhang (Applied Soil Ecology, 2024)

Improved soil moisture, nutrients, and economic benefits using plastic mulchs in balsa-based agroforestry systems - Chang-An Liu; Ming-Yue Liang; Jia-Lin Zhang; Shuai Hua; Zhu-Biao Duan (Environmental Science and Pollution Research, 2024)

Physiology, microcystin production, and transcriptomic responses of Microcystis aeruginosa exposed to calcium and magnesium - Li Yin; Lin Xu; Kaipian Shi; Weiyu Chen; Yong Zhang; Juan Wang; Junfeng An; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Science of The Total Environment, 2024)

Multi-source exposure and health risks of phthalates among university students in Northeastern China - Huicheng Zhu; Na Zheng; Changcheng Chen; Ning Li; Qirui An; Wenhui Zhang; Qiuyan Lin; Zhifei Xiu; Siyu Sun; Xiaoqian Li; Yunyang Li; Sujing Wang (Science of The Total Environment, 2024)

Three chemosensory proteins enriched in antennae and tarsi of Rhaphuma horsfieldi differentially contribute to the binding of insecticides - Yu-Juan Yao; Ning-Na Yin; Lin-Mei Pu; An-Jing Yang; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2024)

Chaepseubakerins A–J, ten undescribed cytotoxic [11]-chaetoglobosins from an endophytic fungus Pseudeurotium bakeri - Fangfang Duan; Xiaogang Peng; Lin Liu; Xianggao Meng; An Jin; Hanli Ruan (Phytochemistry, 2024)

Structural and functional analysis of transforming growth factor beta regulator 1 (TBRG1) in the red swamp crayfish Procambarus clarkii: The initial insight into TBRG1's role in invertebrate immunity - Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Miao-An Shu; Yan-Mei Zhang (Fish & Shellfish Immunology, 2024)

Association of urinary polycyclic aromatic hydrocarbon metabolites with gestational diabetes mellitus and gestational hypertension among pregnant women in Southwest China: A cross-sectional study - Dengqing Liao; Shimin Xiong; Songlin An; Lin Tao; Lulu Dai; Yingkuan Tian; Wei Chen; Caidie He; Pei Xu; Nian Wu; Xiang Liu; Haonan Zhang; et al. (Environmental Pollution, 2024)

Perturbation of IP3R-dependent endoplasmic reticulum calcium homeostasis by PPARδ-activated metabolic stress leads to mouse spermatocyte apoptosis: A direct mechanism for perfluorooctane sulfonic acid-induced spermatogenic disorders - Wang Yang; Xi Ling; Shijun He; Haonan Cui; Lihong Wang; Zeyu Yang; Huihui An; Peng Zou; Qing Chen; Lei Sun; Huan Yang; Jinyi Liu; et al. (Environmental Pollution, 2024)

Investigation of ammonia-induced lethal toxicity toward ion regulation in zebrafish embryos - Li-Yih Lin; Chieh-An Cheng; Sian-Tai Liu; Jiun-Lin Horng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

An asymmetric electrode matching reversible kinetics of oxygen reaction for a rechargeable Zn-air battery - Shuxin Li; Han Zhang; Lin Wu; Hongwei Zhao; Lin Tao; Lixiang Li; Chengguo Sun; Dongying Ju; Baigang An (Chemical Engineering Journal, 2024)

A mild and efficient sonothermal tumor therapy enhanced by sonodynamic effect with biodegradable red phosphorus nanoparticles - Zhizi Ma; Meng Yuan; Ziyong Cheng; Zhuang Yang; Ling Yang; Bin Liu; Yulong Bian; Abdulaziz A. Al Kheraif; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2024)

Application of an absolute reference frame for methane clumped-isotope analyses - Qingmei Liu; Jiacheng Li; Wenmin Jiang; Yun Li; Mang Lin; Wen Liu; Yanhua Shuai; Haizu Zhang; Ping'an Peng; Yongqiang Xiong (Chemical Geology, 2024)

Quantitative evaluation of the impact of hydrological forecasting uncertainty on reservoir real-time optimal operation - Feilin Zhu; Yaqin Wang; Bojun Liu; Qing Cao; Mingyu Han; Yurou Zeng; Meiyan Lin; Lingqi Zhao; Xinrong Wang; Zhiqi Wan; Ping-an Zhong (Stochastic Environmental Research and Risk Assessment, 2024)

The Influence of Surface Modification on the Shortwave Infrared Emission of Rare-Earth-Doped Nanoparticles - Mohd Yaqub Khan; Jen-Kun Chen; Vivek Jain; Lokesh Agrawal; Cheng-An J. Lin; Min-Hua Chen (Journal of Medical and Biological Engineering, 2024)

Groundwater Quality and Vulnerability Assessment in a Semiarid Karst Region of Northern China - Ran An; Shu Wang; Zongjun Gao; Zhenyan Wang; Wei Li; Qijun Deng; Lü Lin; Yuanqing Liu (Journal of Earth Science, 2024)

The impact of environmental livability on rural economic development in China - Yuhu Cui; Dong An; Wen Sun; Lin Yang; Bin Yuan (Environment, Development and Sustainability, 2024)

Foraging flight-based health indicators for honey bee colonies using automatic monitoring systems - Joe-Air Jiang; Jen-Cheng Wang; Chien-Peng Huang; Mu-Hwa Lee; An-Chi Liu; Hung-Jen Lin; Chien-Hao Wang; Cheng-Ying Chou; En-Cheng Yang (Computers and Electronics in Agriculture, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

Melatonin alleviates Hg toxicity by modulating redox homeostasis and the urea cycle in moss - Wen-Yue Hu; Hao-Tian Mao; Xiao-Yan Yin; Jing-Yi Chen; An-Qi He; Lin-Yan Huang; Zhong-Wei Zhang; Shu Yuan; Ming Yuan; Yan-Qiu Su; Yang-Er Chen (Science of The Total Environment, 2024)

Bibliometric analysis and systematic review of the adherence, uptake, translocation, and reduction of micro/nanoplastics in terrestrial plants - Yang Li; Lin Zhao; Yi An; Li Qin; Zhi Qiao; Daying Chen; Yihan Li; Hongzhi Geng; Yongkui Yang (Science of The Total Environment, 2024)

What role financial development and resource-curse situation play in inclusive growth of Asian countries - Thi Ha An Pham; Chia-Yang Lin; Massoud Moslehpour; Thi Thuy Van Vo; Hai-Tuan Nguyen; Tran Thai Ha Nguyen (Resources Policy, 2024)

Rare 7,9′-dinorlignans with neuroprotective activity from the roots of Lindera aggregata (Sims) Kosterm - Qian-Qing Liu; Lin-An Xiong; Jia-Yu Qian; Ting-Ting Gong; Lie-Feng Ma; Luo Fang; Zha-Jun Zhan (Phytochemistry, 2024)

Otolith microchemistry reveals diverse habitat uses and migratory patterns of two Coilia species (Engraulidae) in the Min River Estuary, southern China - Qing Xu; Qing-qiang Ren; Tao Jiang; Bai-an Lin; Xiao-bin Jiang; Jian Yang; Min Liu (Marine Environmental Research, 2024)

Diverse Late Triassic arc magmatism and porphyry Cu deposits in the southeastern Tibetan Plateau: Related to slab tear along a subducting passive margin? - Wan-Li Tang; Jian-Lin Chen; Tian-Nan Yang; An Yin; Ji-Feng Xu; Jiang-Bo Ren (Lithos, 2024)

Piriformospora indica colonization enhances remediation of cadmium and chromium co-contaminated soils by king grass through plant growth promotion and rhizosphere microecological regulation - Kailu Zhang; Haixiang Zhang; Can Xie; Zhiqiang Zhu; Li Lin; Qianli An; Xin Zhang; Weidong Wu; Dong Li (Journal of Hazardous Materials, 2024)

Association of hair polychlorinated biphenyls and multiclass pesticides with obesity, diabetes, hypertension and dyslipidemia in NESCAV study - Feng-Jiao Peng; Chia-An Lin; Rin Wada; Barbara Bodinier; Alba Iglesias-González; Paul Palazzi; Sylvie Streel; Michèle Guillaume; Dragana Vuckovic; Marc Chadeau-Hyam; Brice M.R. Appenzeller (Journal of Hazardous Materials, 2024)

Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Di Lv; Hongyun Liu; Qi An; Chengwei Lei; Yanxuan Wang; Jin Sun; Chuanhai Li; Yongfeng Lin; Qing Dong; Zhugen Yang; Kui Che; Wendong Liu; et al. (Journal of Hazardous Materials, 2024)

Anthropogenically-induced atmospheric Pb cycle in low-latitude Asia since the Industrial Revolution recorded by high-resolution stalagmites - Tianli Wang; Pei-Hsuan Yao; Chuan-Chou Shen; Sakonvan Chawchai; Adi Torfstein; Ashish Sinha; Hai Xu; Tsai-Luen Yu; Fangyuan Lin; Xiqian Wang; Dong Li; Hai Cheng; et al. (Global and Planetary Change, 2024)

Conformational flexibility and molecular weight influence the emulsification performance of pectin: A comparative study of sugar beet pectin and citrus pectin - Jiawei Lin; Huanqing Lei; Zhong Han; Xin-An Zeng (Food Hydrocolloids, 2024)

Regional complex system simulation optimization through linking governance and environment performance: A case study of water environmental carrying capacity based on the SDES model - An Huang; Li Tian; Yongfu Li; Binyu Xiong; Jianghao Yu; Yuan Gao; Qing Li; Chenjing Fan; Linxiner Liu; Xuejun Duan; Chen Lin (Environmental Impact Assessment Review, 2024)

pH-tailored activated water reservoir for rapid solar water purification via dual-layer hydrogel architecture - Xue-Tong Yang; Huan Lin; Jia-Chen Zhang; Gangqiang Yu; Yuelian Peng; Quan-Fu An (Chemical Engineering Journal, 2024)

Red blood cell membrane biomimetic nanoprobes for ratiometric imaging of reactive oxygen species level in atherosclerosis - Bo Liu; Gui-Mei Han; Dong-Xia Wang; Ding-Bin Liu; An-An Liu; Jing Wang; Yu-Ling Xiao; Lin Yuan; De-Ming Kong (Chemical Engineering Journal, 2024)

Association between obstructive sleep apnea and low bone mass in adults: a systematic review and meta-analysis - Xin-Yuan Wang; Xin-Yu Wang; Zhi-Xin Liao; Yue-An Zhao; Chang Wei; Lin-Jing Gong (Sleep and Biological Rhythms, 2024)

Metabolomics reveals that chronic restraint stress alleviates carbon tetrachloride-induced hepatic fibrosis through the INSR/PI3K/AKT/AMPK pathway - Shanshan Zhang; Binjie Liu; Lan Huang; Rong Zhang; Lin An; Zhongqiu Liu (Journal of Molecular Medicine, 2024)

Emerging and legacy perfluoroalkyl and polyfluoroalkyl substances (PFAS) in surface water around three international airports in China - Jing Liu; Zhen Zhao; Jie Li; Xia Hua; Boxuan Zhang; Caijun Tang; Xinyi An; Tian Lin (Chemosphere, 2023)

Development of a line following autonomous spraying vehicle with Machine vision-based leaf density estimation for cherry tomato greenhouses - Nhu Tuong An Nguyen; Cong Chuan Pham; Wei-Chih Lin (Computers and Electronics in Agriculture, 2023)

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

Remote sensing of urban greenspace exposure and equality: Scaling effects from greenspace and population mapping - Shengbiao Wu; Wenbo Yu; Jiafu An; Chen Lin; Bin Chen (Urban Forestry & Urban Greening, 2023)

Unveiling the potential for artificial upwelling in algae derived carbon sink and nutrient mitigation - Chunlei Shen; Xinya Hao; Dong An; Martin R. Tillotson; Lin Yang; Xu Zhao (Science of The Total Environment, 2023)

Influence of salinity on microalgae-bacteria symbiosis treating shrimp farming wastewater - Thi-Kim-Quyen Vo; Quang-Huy Hoang; Huu Hao Ngo; Cong-Sac Tran; Tung N.N. Ninh; Song-Lam Le; An-Tan Nguyen; Tan Thi Pham; Thanh-Binh Nguyen; Chitsan Lin; Xuan-Thanh Bui (Science of The Total Environment, 2023)

Long-lived Cenozoic positive relief of the south-Eastern Tian Shan: Insights from provenance analyses of the northwestern Kuqa Depression sediments - Jialun Huang; Xiubin Lin; Kaixuan An; Hanlin Chen; Xiaogan Cheng; Yang Qu; Yong Li; Xianzhang Yang; Liang Zhang; Cai Chen; Zhuxin Chen; Lin Jiang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Late Cretaceous bimodal volcanic rocks in Shuanghu induced by lithospheric delamination beneath the Southern Qiangtang, Tibet - Ding-Jun Wen; Xiumian Hu; Timothy Chapman; Gang Zeng; An-Lin Ma; Rui-Qiang Wang (Lithos, 2023)

Yuexiconcha nov. gen. – A resilifer-bearing palaeotaxodont (Bivalvia, Protobranchia) from the Ordovician of Guangdong, South China - Zhi-jun Niu; Ren-jie Zhang; Paul A. Johnston; Chu-an Li; Zhi-hong Wang; Kun Hu; Fang Song; Yao-yan He; Jin-lan He; Xiao-ming Lin; Wen-qiang Yang (Geobios, 2023)

Synthetic polymer fracturing fluid weighted by sodium formate enables fracture stimulations in Ultra-High pressure and High-Temperature reservoir - Xiaojiang Yang; An Chen; Jincheng Mao; Chong Zhang; Juanjuan Wang; Meitao Fu; Hu Zhang; Junjian Wang; Xianshi Song; Yang Zhang; Chong Lin (Fuel, 2023)

The first identification and functional analysis of two drosophila mothers against decapentaplegic protein genes (SpSmad1 and SpSmad2/3) and their involvement in the innate immune response in Scylla paramamosain - Bang-ze Li; Chen-yang Lin; Wen-bin Xu; Yan-mei Zhang; Qing-jun Shao; Wei-ren Dong; Miao-an Shu (Fish & Shellfish Immunology, 2023)

In-situ generated elemental selenium nanograins cooperated with NiSe2 microspheres for significantly enhanced magnesium-storage performance - Changchun Hu; Lin Ran; Hou-an Zhang; Shuai Cui; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2023)

Nitrogen removal from dewatering liquid of landfill sludge by partial nitrification and denitrification - Zihang Ma; Lifeng Lin; Jiafu Xi; Xiaolu Gong; Jianqiao Wang; Peng Peng; Ying An; Weijie Hu; Jing Cao; Zhichao Wu; Zhen Zhou (Bioresource Technology, 2023)

The benefits of high-resolution models in simulating the Kuroshio Extension and its long-term changes - Bo An; Yongqiang Yu; Helene Hewitt; Peili Wu; Kalli Furtado; Hailong Liu; Pengfei Lin; Yihua Luan; Kangjun Chen (Climate Dynamics, 2023)

Temperature mediates microbial multitrophic communities assembly and soil-borne fungal pathogens in coastal ecosystems - An-Qi Sun; Chang-Yi Lu; Qian Xiang; Qing-Lin Chen; Yong-Guan Zhu; Ji-Zheng He; Hang-Wei Hu (Applied Soil Ecology, 2023)

Effects of different Solanum sect. Solanum (Solanaceae) straw amendments on selenium accumulation and growth of grapevine - Kewen Huang; Xu Chen; Ran Zhang; Yiping Dong; Qunxian Deng; Yan Huang; Lei Liu; Ting Wang; Ming’an Liao; Lijin Lin (Acta Physiologiae Plantarum, 2023)

Iodine status and associated dietary factors among preschool children in Shanghai - Jing Li; Jun-Xia Liu; Yu-Qing Wang; An-Xin Lu; Yi-Hong Wang; Yin Lin; Chong-Huai Yan (Environmental Science and Pollution Research, 2023)

Tidal dynamics regulates potential coupling of carbon‑nitrogen‑sulfur cycling microbes in intertidal flats - Yuhui Niu; Zhirui An; Dengzhou Gao; Feiyang Chen; Jie Zhou; Bolin Liu; Lin Qi; Li Wu; Zhuke Lin; Guoyu Yin; Xia Liang; Hongpo Dong; et al. (Science of The Total Environment, 2023)

Characteristics of landscape and erosion in the Eastern Pamir and their implications for regional fault connections - Yunpeng Wu; Rong Yang; Junqing He; Hanlin Chen; Xiubin Lin; Xuhua Shi; Kaixuan An; Chunyang Li; Shibao Gao; Yaguang Chen (Geomorphology, 2023)

An end-to-end approach to predict physical properties of heterogeneous porous media: Coupling deep learning and physics-based features - Yuqi Wu; Senyou An; Pejman Tahmasebi; Keyu Liu; Chengyan Lin; Serveh Kamrava; Chang Liu; Chenyang Yu; Tao Zhang; Shuyu Sun; Samuel Krevor; Vahid Niasar (Fuel, 2023)

Chemical basis and self-assembly mechanism of submicroparticles forming in chrysanthemum tea infusion - An Peng; Lianzhu Lin; Mouming Zhao (Food Chemistry, 2023)

A novel integrated automatic strategy for amino acid composition analysis of seeds from 67 species - Yelin Ding; Qirui Bi; Dongdong Huang; Jingmei Liao; Lin Yang; Xiaoxiao Luo; Peilei Yang; Yun Li; Changliang Yao; Wenlong Wei; Jianqing Zhang; Jiayuan Li; et al. (Food Chemistry, 2023)

Association between glyphosate exposure and cognitive function, depression, and neurological diseases in a representative sample of US adults: NHANES 2013–2014 analysis - Ching Chung Hsiao; An-Ming Yang; ChiKang Wang; Chien-Yu Lin (Environmental Research, 2023)

Effects of food-borne docosahexaenoic acid supplementation on bone lead mobilisation, mitochondrial function and serum metabolomics in pre-pregnancy lead-exposed lactating rats - An-Xin Lu; Yin Lin; Jing Li; Jun-Xia Liu; Chong-Huai Yan; Lin Zhang (Environmental Pollution, 2023)

Metabolomics insights into the effects of pre-pregnancy lead exposure on bone metabolism in pregnant rats - Lin Zhang; Yin Lin; An-Xin Lu; Jun-Xia Liu; Jing Li; Chong-Huai Yan (Environmental Pollution, 2023)

Silver nanoparticle@catechol formaldehyde resin microspheres: One-pot synthesis and application for producing durable antimicrobial cotton fabrics - Lian-Yi Qu; Jiang-Long Liu; An-Le Yang; Lin Zhang; Ping Zhu; Ying-Jun Xu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Super-strong Zn and S atomic terminals in an organic/inorganic hybrid S-scheme polyimide based heterojunction for efficient photocatalytic treatment of mixed pollutant wastewater - Siyi Li; Yushu Wang; Hongli An; Junjun Lin; Shuang Jiang; Tianyong Zhang; Bin Li (Chemical Engineering Journal, 2023)

In-situ utilization of EPS improves the directional oxidation ability of Fe(III)/H2O2 and enhances sludge dewaterability - Wei Lin; Chuangxin Gong; Renglu Chen; Xu He; Jun Nan; Guibai Li; Huu Hao Ngo; An Ding (Chemical Engineering Journal, 2023)

Indicator of climate variability: low treeline displacement in arid valleys of mountain areas, China - Wei-po Yan; Qing Wang; Ya-lin Guo; Qi Hu; Min Yang; Yi-da An (Journal of Mountain Science, 2023)

Movement of protistan trophic groups in soil–plant continuums - Chenshuo Lin; Wen‐Jing Li; Li‐Juan Li; Roy Neilson; Xin‐Li An; Yong‐Guan Zhu (Environmental Microbiology, 2023)
Protists, functionally divided into consumers, phototrophs, and parasites act as integral components and vital regulators of microbiomes in soil–plant continuums. However, the drivers of community structure, assembly mechanisms, co‐occurrence patterns, and the associations with human pathogens and different protistan trophic groups remain unknown. Here, we characterized the phyllosphere and soil protistan communities associated with three vegetables under different fertilization treatments (none and organic fertilization) at five growth stages. In this study, consumers were the most diverse soil protist group, had the role of inter‐kingdom connector, and were the primary biomarker for rhizosphere soils which were subjected to decreasing deterministic processes during plant growth. In contrast, phototrophs had the greatest niche breadth and formed soil protistan hubs, and were the primary biomarkers for both bulk soils and the phyllosphere. Parasites had minimal input to microbial co‐occurrence networks. Organic fertilization increased the relative abundance (RA) of pathogenic protists and the number of pathogen–consumer connections in rhizosphere soils but decreased protistan richness and the number of internal protistan links. This study advances our understanding of the ecological roles and potential links between human pathogens and protistan trophic groups associated with soil–plant continuums, which is fundamental to the regulation of soil–plant microbiomes and maintenance of environmental and human health.

Association between Asbestos Exposure and the Incidence of Kidney Cancer: a Weight-of-Evidence Evaluation and Meta-analysis - Fu-Shiuan Whitney Lee; Yu-Han Chen; Ngoc Dang Tran; Cheng-Kuan Lin; Le An Pham (Current Environmental Health Reports, 2023)

RETRACTED ARTICLE: Green supply chain, green leadership, consumer preferences, sustainability attitudes, and sustainable business advantage: a case of Vietnamese textile industry - Ka Yin Chau; Chen-Hsien Lin; Purevdulam Altantsetseg; Bushra Tufail; Thi Ha An Pham; Tran Thai Ha Nguyen (Environmental Science and Pollution Research, 2023)

Three new hasubanan-type alkaloids from the Stephania longa - Rong-Xiao Lin; Lixia Fan; Xin Chen; Jundi Wu; Zheng Liu; Fang Liu; An-Ping Yang; Chenglai Xia; Hui Liu; Hong-Yuan Chen (Natural Product Research, 2023)

Monitoring and management of abandoned, lost and discarded fishing gear (ALDFG) in Penghu Islands, Taiwan - Wen-Hong Liu; Hung-An Chang; Hao-Tang Jhan; Chih-Cheng Lin; Li-Shu Chen; Chung-Lun Liu; Kuo-Huan Ting (Marine Pollution Bulletin, 2023)

An MLS-based high-accuracy measurement and automatic analysis method for roadway deformation - Chao Wu; Yuanhui Li; Long An; Erhu Dong; Lin Han (Tunnelling and Underground Space Technology, 2023)

The effect of glycerol additive on high value-added chemicals from tobacco waste pyrolysis - Jia-hao Wang; Xian-jie Zhang; Qian Xia; Shui yang Fang; An-fu Hu; Jun Wen; Sheng-jun Zhou; Wen-xian Chen; Gui-lin Zhuang (Journal of Environmental Chemical Engineering, 2023)

Inactivation of Alicyclobacillus acidoterrestris vegetative cells and spores induced by atmospheric cold plasma - Si-Qi Zhao; Lin Chen; Bing Yan; Lang-Hong Wang; Xin-An Zeng; Rana Muhammad Aadil (Innovative Food Science & Emerging Technologies, 2023)

Tectonic evolution of the Meso-Tethys Ocean in the Jurassic: Birth, growth, and demise of a missing intra-oceanic arc - Bo-Chuan Zhang; Jian-Jun Fan; An-Bo Luo; Xiao-Wen Zeng; Men-Long Duan; Si-Lin Sun (Gondwana Research, 2023)

Methylmercury induced ferroptosis by interference of iron homeostasis and glutathione metabolism in CTX cells - Xi Xu; Su-Su Wang; Lin Zhang; An-Xin Lu; Yin Lin; Jun-Xia Liu; Chong-Huai Yan (Environmental Pollution, 2023)

Emission characteristics of (halogenated) polycyclic aromatic hydrocarbons during printed circuit board combustion and estimated emission intensity of a typical e-waste dismantling site in South China - Xiang Ge; Muhammad Zaffar Hashmi; Shuo Lin; Zenghua Qi; Yingxin Yu; Taicheng An (Environmental Pollution, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Neuroprotective Effects of Probiotic Lactobacillus reuteri GMNL-263 in the Hippocampus of Streptozotocin-Induced Diabetic Rats - Jing-Ying Lin; Bruce Chi-Kang Tsai; Hui-Chuan Kao; Chien-Yi Chiang; Yun-An Chen; William Shao-Tsu Chen; Tsung-Jung Ho; Chun-Hsu Yao; Wei-Wen Kuo; Chih-Yang Huang (Probiotics and Antimicrobial Proteins, 2023)

Caterpillar Salivary Glucose Oxidase Decreases Green Leaf Volatile Emission and Increases Terpene Emission from Maize - Anne C. Jones; Po-An Lin; Michelle Peiffer; Gary Felton (Journal of Chemical Ecology, 2023)

Designing and planning sustainable customized bus service for departing attendees of planned special events: A two-phase methodology integrating data-driven and demand-responsive - Yuan Tian; Dan Yang; Jian Wang; Wenfeng Lin; Yin Jiang; Shi An (Sustainable Cities and Society, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Selenium alleviates biological toxicity of thiamethoxam (TMX): Bioaccumulation of TMX, organ damage, and antioxidant response of red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wen-Bin Xu; Chen-Yang Lin; Bang-Ze Li; Miao-An Shu (Journal of Hazardous Materials, 2023)

Succession of biochar addition for soil amendment and contaminants remediation during co-composting: A state of art review - Huu-Tuan Tran; Nanthi S. Bolan; Chitsan Lin; Quach An Binh; Minh-Ky Nguyen; The Anh Luu; Van-Giang Le; Cham Q. Pham; Hong-Giang Hoang; Dai-Viet N. Vo (Journal of Environmental Management, 2023)

Identification and functional analysis of cytosolic phospholipase A2 (cPLA2) from the red swamp crayfish Procambarus clarkii: The first evidence of cPLA2 involved in immunity in invertebrates - Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Miao-An Shu; Yan-Mei Zhang (Fish & Shellfish Immunology, 2023)

Identification and functional analysis of endoplasmic reticulum oxidoreductase 1 (ERO1) from the green mud crab Scylla paramamosain: The first evidence of ERO1 involved in invertebrate immune response - Chen-Yang Lin; Yan-Mei Zhang; Wen-Bin Xu; Miao-An Shu; Wei-Ren Dong (Fish & Shellfish Immunology, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Has China's low-carbon strategy pushed forward the digital transformation of manufacturing enterprises? Evidence from the low-carbon city pilot policy - Shuang Zhao; Liqun Zhang; Haiyan An; Lin Peng; Haiyan Zhou; Feng Hu (Environmental Impact Assessment Review, 2023)

Ultrafast self-assembled supramolecular nanoparticles for enhanced chemodynamic therapy and ferroptosis through lactic acid metabolism regulation - Qi Meng; Jia Tan; Weifang Tong; Changxiao Chen; Zhendong Liu; Sainan Liu; Meifang Wang; Ziyong Cheng; Binbin Ding; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2023)

Recognition of multivariate geochemical anomalies using a geologically-constrained variational autoencoder network with spectrum separable module – A case study in Shangluo District, China - Bo Zhao; Dehui Zhang; Panpan Tang; Xiaoyan Luo; Haoming Wan; Lin An (Applied Geochemistry, 2023)

Internal exposure risk based on urinary metabolites of PAHs of occupation and non-occupation populations around a non-ferrous metal smelting plant - Bizhi Wu; Meiqing Lin; Hailing Li; Yingjun Wu; Mengdie Qi; Jian Tang; Shengtao Ma; Guiying Li; Taicheng An (Journal of Hazardous Materials, 2023)

Effect of quorum quenching on biofouling control and microbial community in membrane bioreactors by Brucella sp. ZJ1 - Rui Wang; Zijing An; Lu Fan; Yan Zhou; Xiaomei Su; Junjie Zhu; Qian Zhang; Chongjun Chen; Hongjun Lin; Faqian Sun (Journal of Environmental Management, 2023)

Phenol degradation at high salinity by a resuscitated strain Pseudomonas sp. SAS26: kinetics and pathway - Shusheng Zhang; Zijing An; Xiaomei Su; Aiqin Hou; Leilei Liu; Lihua Zhang; Qiuyang He; Faqian Sun; Zupei Lei; Hongjun Lin; Jiahou Lai (Journal of Environmental Chemical Engineering, 2023)

Anaerobic membrane bioreactor for the treatment of high-strength waste/wastewater: A critical review and update - Zijing An; Junjie Zhu; Min Zhang; Yan Zhou; Xiaomei Su; Hongjun Lin; Faqian Sun (Chemical Engineering Journal, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

Population structure and reproductive dynamics of the ridged swimming crab Charybdis natator in the southern Taiwan Strait of China: significant changes within 25 years - Bai-an Lin; Yan Jiang; Min Liu (Frontiers in Marine Science, 2023)
The ridged swimming crab Charybdis natator (Portunidae) is a commercially important crustacean species in China. The purpose of this study is to compare its population structure and reproductive pattern within the same fishing area (the southern Taiwan Strait) from two datasets over 25 years; one from 1994−1996 (the early years of the C. natator fishery) and the other from 2019. The overall sex ratio (male:female) changed from a male bias (1:0.76, p < 0.01) in 1994−1996 to a female bias (1:1.38, p < 0.01) in 2019. Male body sizes (carapace width, CW) were significantly larger than those of females in both datasets ( p < 0.05). The average CW and body weight (BW) of males and females in 2019 were significantly smaller ( p < 0.01) and lighter ( p < 0.01) than those in 1994−1996. The maximum body size and the proportion of large-sized individuals (CW > 10 cm) decreased dramatically over 25 years. One spawning peak season was identified from each dataset, i.e., March−August 1994−1996 and February−April 2019, revealing a 1-month shift. The minimum body sizes for female maturation (carrying eggs) were 6.9 cm CW in 1994−1996 and 6.1 cm CW in 2019, an 11.6% reduction over 25 years. For the first time, the CW at 50% female maturation, the relationship between female absolute fecundity and CW, and egg diameters were obtained from the 2019 dataset, which can be applied in the future comparisons. Recent studies have revealed a consistent spawning peak in February–April for several commercially important crabs in the southern Taiwan Strait. These findings should be considered in crab fishery management. Furthermore, both fishery- and environment-associated factors influencing crustacean population structure and reproductive dynamics merit further investigation.

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Comparation of mesophilic and thermophilic anaerobic co-digestion of food waste and waste activated sludge driven by biochar derived from kitchen waste - Rong Zhang; Min Zhang; Huaqian Mou; Zijing An; Hailu Fu; Xiaomei Su; Chongjun Chen; Jianrong Chen; Hongjun Lin; Faqian Sun (Journal of Cleaner Production, 2023)

Emission and gas-particle partitioning characteristics of atmospheric halogenated and organophosphorus flame retardants in decabromodiphenyl ethane-manufacturing functional areas - Helong Ren; Xiang Ge; Zenghua Qi; Qinhao Lin; Guofeng Shen; Yingxin Yu; Taicheng An (Environmental Pollution, 2023)

Effect of using construction and demolition waste as substrate on methane and carbon dioxide emissions from green roofs - Xinping Li; Yuanmao Lin; Xiaoling Liu; Jie Liang; Xin Yang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Zhaolan Wei; Xiaochan An; Wei Chen; et al. (Ecological Engineering, 2023)

An elastic-viscoplastic model for time-dependent behavior of unsaturated soils - Guo-qing Cai; Yan-lin Su; An-nan Zhou; Feng-jie Yin; Ye-hui Shi (Computers and Geotechnics, 2023)

Elucidating the chemical structures of petroleum resin using solid-state 13C NMR - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Ping'’an Peng (Chemical Geology, 2023)

Ethanol production using the whole solid-state fermented sugarcane bagasse cultivated by Trichoderma reesei RUT-C30 supplemented with commercial cellulase - Ching An Lin; Cheng Cheng; Li Wei Chen; C. Will Chen; Kow Jen Duan (Biocatalysis and Agricultural Biotechnology, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Influence of microclimate control on the growth of asparagus under greenhouse in tropical climates - Kuo-An Hung; Yi-Wei Hsu; Yu-Cheng Chen; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

SHP2: its association and roles in systemic lupus erythematosus - Chan Yang; Rong Li; Lin-Chong Su; You-Yu Lan; You-Qiang Wang; Wang-Dong Xu; An-Fang Huang (Inflammation Research, 2023)

Potential response of dark carbon fixation to global warming in estuarine and coastal waters - Lin Qi; Yanling Zheng; Lijun Hou; Bolin Liu; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Global Change Biology, 2023)
Dark carbon fixation (DCF), through which chemoautotrophs convert inorganic carbon to organic carbon, is recognized as a vital process of global carbon biogeochemical cycle. However, little is known about the response of DCF processes in estuarine and coastal waters to global warming. Using radiocarbon labelling method, the effects of temperature on the activity of chemoautotrophs were investigated in benthic water of the Yangtze estuarine and coastal areas. A dome‐shaped thermal response pattern was observed for DCF rates (i.e., reduced rates at lower or higher temperatures), with the optimum temperature ( T opt ) varying from about 21.9 to 32.0°C. Offshore sites showed lower T opt values and were more vulnerable to global warming compared with nearshore sites. Based on temperature seasonality of the study area, it was estimated that warming would accelerate DCF rate in winter and spring but inhibit DCF activity in summer and fall. However, at an annual scale, warming showed an overall promoting effect on DCF rates. Metagenomic analysis revealed that the dominant chemoautotrophic carbon fixation pathways in the nearshore area were Calvin‐Benson‐Bassham (CBB) cycle, while the offshore sites were co‐dominated by CBB and 3‐hydroxypropionate/4‐hydroxybutyrate cycles, which may explain the differential temperature response of DCF along the estuarine and coastal gradients. Our findings highlight the importance of incorporating DCF thermal response into biogeochemical models to accurately estimate the carbon sink potential of estuarine and coastal ecosystems in the context of global warming.

Potential ecological risks of heavy metals and Cd accumulation characteristics of Suaeda salsa under different Cd input and water logging conditions in the Yellow River estuary, China - Hongli Song; Lin Kuang; Lizhi Wang; Wanni Yu; Yuanzhi Wu; Juan An; Xiyuan Wu (Environmental Science and Pollution Research, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

Sulfate-modified nanosized polystyrene impairs memory by inhibiting ionotropic glutamate receptors and the cAMP-response element binding protein (CREB) pathway in Caenorhabditis elegans - Ting-An Lin; Chun Ming How; Pei-Ling Yen; Vivian Hsiu-Chuan Liao (Science of The Total Environment, 2023)

Spatiotemporal changes of wetlands in China during 2000–2015 using Landsat imagery - Meng Zhang; Huaiqing Zhang; Bo Yao; Hui Lin; Xuexian An; Yang Liu (Journal of Hydrology, 2023)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

Phyllanthus emblica L. extract alleviates leptin resistance and lipid accumulation by inhibiting methylglyoxal production - Yue-Ning Huang; Sheng-Yi Chen; Jer-An Lin; I-Chen Chiang; Gow-Chin Yen (Food Bioscience, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Risk factors for acute kidney injury after high-dose methotrexate therapy: a single-center study and narrative review - Chun-An Liang; Yi-Chia Su; Shyh-Jer Lin; Tsung-Hsien Tsai (European Journal of Clinical Pharmacology, 2023)

Short- and medium-chain chlorinated paraffins in urban road dust of Shanghai, China: concentrations, source apportionment and human exposure assessment - Xue-Tong Wang; Cheng-Lin Wang; Ying Zhou; Guo-Fa Ren; Rui Fu; Jing An (Environmental Geochemistry and Health, 2023)

Characteristics of Cloud Water Resource and Precipitation Efficiency of Hydrometeors over Northwest China - Zhanyu Yao; Lin An; Pei Zhang; Liangshu Gao; Shuo Jia; Weijian Wang; Wenhui Zhao (Journal of Meteorological Research, 2023)

Carbon quantum dot fluorescent probe for labeling and imaging of stellate cell on liver frozen section below freezing point - Yan-Fei He; Kai Cheng; Zi-Tao Zhong; Xiao-Lin Hou; Chang-Zhi An; Jing Zhang; Wei Chen; Bo Liu; Jing Yuan; Yuan-Di Zhao (Analytica Chimica Acta, 2023)

Dataset of Comparative Observations for Land Surface Processes over the Semi-Arid Alpine Grassland against Alpine Lakes in the Source Region of the Yellow River - Xianhong Meng; Shihua Lyu; Zhaoguo Li; Yinhuan Ao; Lijuan Wen; Lunyu Shang; Shaoying Wang; Mingshan Deng; Shaobo Zhang; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2023)
Thousands of lakes on the Tibetan Plateau (TP) play a critical role in the regional water cycle, weather, and climate. In recent years, the areas of TP lakes underwent drastic changes and have become a research hotspot. However, the characteristics of the lake-atmosphere interaction over the high-altitude lakes are still unclear, which inhibits model development and the accurate simulation of lake climate effects. The source region of the Yellow River (SRYR) has the largest outflow lake and freshwater lake on the TP and is one of the most densely distributed lakes on the TP. Since 2011, three observation sites have been set up in the Ngoring Lake basin in the SRYR to monitor the lake-atmosphere interaction and the differences among water-heat exchanges over the land and lake surfaces. This study presents an eight-year (2012–19), half-hourly, observation-based dataset related to lake–atmosphere interactions composed of three sites. The three sites represent the lake surface, the lakeside, and the land. The observations contain the basic meteorological elements, surface radiation, eddy covariance system, soil temperature, and moisture (for land). Information related to the sites and instruments, the continuity and completeness of data, and the differences among the observational results at different sites are described in this study. These data have been used in the previous study to reveal a few energy and water exchange characteristics of TP lakes and to validate and improve the lake and land surface model. The dataset is available at National Cryosphere Desert Data Center and Science Data Bank.

Spatiotemporal variations and impact factors of nutrients in the Sanya Bay, northern South China Sea - Xinxing Geng; Chuanliang Wu; Ziwei Yang; Junying Zhu; Kai Tang; Jiamin Lin; Yaxing Liu; Yufang Zhang; Mingxun An; Weibin Zhao; Yang Yu (Environmental Science and Pollution Research, 2023)

Characteristics and provenances of rare earth elements and Nd isotopes in surface sediments of mangrove wetlands in the Jiulong River Estuary, China - Bo-sen Weng; Rui-an Wan; Rui-lian Yu; Gong-ren Hu; Yu Yan; Cheng-qi Lin; Hua-bin Huang (Environmental Science and Pollution Research, 2023)

Material flow analysis of commercial fishing gears in Taiwan - Ching-Tuan Su; Falk Schneider; Paritosh C. Deshpande; Hui-Ya Xiao; Tien-An Su; Ning Yen; Hsin-Tien Lin (Marine Pollution Bulletin, 2023)

Polybrominated diphenyl ethers and bromophenols in paired serum, hair, and urine samples of e-waste dismantlers: Insights into hair as an indicator of endogenous exposure - Meiqing Lin; Shengtao Ma; Jian Tang; Yingxin Yu; Guiying Li; Ruifang Fan; Guoxia Zhang; Bixian Mai; Taicheng An (Science of The Total Environment, 2023)

Enzyme activities and organic matter mineralization in response to application of gypsum, manure and rice straw in saline and sodic soils - Muhammad Shaaban; Yupeng Wu; Avelino Núñez-Delgado; Yakov Kuzyakov; Qi-An Peng; Shan Lin; Ronggui Hu (Environmental Research, 2023)

Outcomes between endoscopic-assisted minimally invasive surgery and conventional craniotomy in spontaneous intracerebral hemorrhage - Yi-Ying Hsieh; Bo-An Chen; Kuan-Hao Fu; Yi-Hsien Kuo; Ying-Yun Chen; Jiun-Lin Yan; Pin-Yuan Chen (Neurophysiology, 2023)

Failure mechanism of a large-scale composite deposits caused by the water level increases - Xin Zhang; Guo-xiang Tu; Qi-feng Luo; Hao Tang; Yu-lin Zhang; An-run Li (Journal of Mountain Science, 2023)

Improving NO2 prediction by integrating tree diversity, urban form, and scale sensitivity through mobile monitoring - Ye Tian; An Wang; Simone Mora; Priyanka deSouza; Xiaobai Yao; Fábio Duarte; Hui Lin; Carlo Ratti (Applied Geography, 2023)

Urinary di-(2-ethylhexyl) phthalate metabolites are independently related to serum neurofilament light chain, a biomarker of neurological diseases, in adults: results from NHANES 2013–2014 - An-Ming Yang; Tai-Shuan Lai; Yu-Ling Lin; ChiKang Wang; Chien-Yu Lin (Environmental Science and Pollution Research, 2023)

Protection of electroactive biofilms against hypersaline shock by quorum sensing - Shaofeng Zhou; Wenwen An; Kexin Zhao; Lizhou Lin; Shan Yang; Yifeng Zhang; Meiying Xu (Water Research, 2023)

In vitro and in vivo anti-tumor activity of Coenzyme Q0 against TWIST1-overexpressing HNSCC cells: ROS-mediated inhibition of EMT/metastasis and autophagy/apoptosis induction - Hsin-Ling Yang; Li-Wen Chiu; Yi-An Lin; Sudhir Pandey; Chithravel Vadivalagan; Jiunn-Wang Liao; Yugandhar Vudhya Gowrisankar; Hui-Jye Chen; Hui-Yi Lin; You-Cheng Hseu (Toxicology and Applied Pharmacology, 2023)

The ginsenoside Rh2 protects porcine oocytes against aging and oxidative stress by regulating SIRT1 expression and mitochondrial activity - Hongye Liu; Zhi-Yong An; Zhou-Yan Li; Liu-Hui Yang; Xiu-Li Zhang; Yan-Tong Lv; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2023)

Future hotter summer greatly increases residential electricity consumption in Beijing: A study based on different house layouts and shared socioeconomic pathways - Qiyuan Hu; Jiayue Tang; Xiang Gao; Sijia Wang; Dan Zhang; Yuting Qin; Qihan Wang; Yi Zhou; Na Huang; Josep Penuelas; Jordi Sardans; Josep G. Canadell; et al. (Sustainable Cities and Society, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

Involvement of microRNA164 in responses to heat stress in Arabidopsis - Wei-An Tsai; Po-Han Sung; Yun-Wei Kuo; Ming-Cheng Chen; Shih-Tong Jeng; Jeng-Shane Lin (Plant Science, 2023)

A novel strategy for enhancing bioremediation of polychlorinated biphenyl-contaminated soil with resuscitation promoting factor and resuscitated strain - Xinru Zhou; Shusheng Zhang; Rui Wang; Zijing An; Faqian Sun; Chaofeng Shen; Hongjun Lin; Xiaomei Su (Journal of Hazardous Materials, 2023)

Novel Al-doped UiO-66-NH2 nanoadsorbent with excellent adsorption performance for tetracycline: Adsorption behavior, mechanism, and application potential - Liangqian Fan; Jiaxin Miao; Xianda Wang; Jie Cai; Jiawei Lin; Fenghui Chen; Wei Chen; Hongbing Luo; Lin Cheng; Xiaochan An; Xiaoxiao Zhang; Ke Zhang; et al. (Journal of Environmental Chemical Engineering, 2023)

Underestimated contribution of fugitive emission to VOCs in pharmaceutical industry based on pollution characteristics, odorous activity and health risk assessment - Qinhao Lin; Zhong Gao; Weikun Zhu; Jiangyao Chen; Taicheng An (Journal of Environmental Sciences, 2023)

The content and distribution of 18 phenolic compounds in 462 batches of edible flowers from 73 species commercially available in China - Ziqing Li; Jianqing Zhang; Qian Meng; Lin Yang; Mingyang Qiu; Yun Li; Shuai Yao; Wenlong Wei; Changliang Yao; Qirui Bi; Jiayuan Li; De-an Guo (Food Research International, 2023)

Isolation, identification and the pathogenicity characterization of a Santee-Cooper ranavirus and its activation on immune responses in juvenile largemouth bass (Micropterus salmoides) - Xiaodan Liu; Yanbing Zhang; Zheling Zhang; Zhenhua An; Xiaojun Zhang; Vikram N. Vakharia; Li Lin (Fish & Shellfish Immunology, 2023)

Recent progress on highly efficient removal of heavy metals by layered double hydroxides - Tong He; Qian Li; Tong Lin; Jiaxin Li; Sha Bai; Sai An; Xianggui Kong; Yu-Fei Song (Chemical Engineering Journal, 2023)

Evolvement of carbamazepine under solar irradiation in the presence of chlorine: Efficiency, influences, degradation pathways and ecotoxicity - Haixiang Jia; Xiaoyan Y. Ma; Yu Lin; Shengjiong Yang; Yali An; Yihan Chen; Xiaochang C. Wang (Chemical Engineering Journal, 2023)

Lactiplantibacillus plantarum PS128 Alleviates Exaggerated Cortical Beta Oscillations and Motor Deficits in the 6-Hydroxydopamine Rat Model of Parkinson’s Disease - Yi-Fan Ma; Yi-An Lin; Chin-Lin Huang; Chih-Chieh Hsu; Sabrina Wang; Shih-Rung Yeh; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2023)

An Investigation of Bubble Motion in the Fluidic Oscillator - Haiyan Bie; Licheng Xue; Yulong Li; Yunxia Li; Zixin Lin; Weizhong An (Journal of Ocean University of China, 2023)

Yield gap of rice genotypes under N and P deficiencies: Evidence from differential recruitment of bacterial keystone taxa in the rhizosphere - Jia Lin Wang; Xun Xiao; An Yong Hu; Ren Fang Shen; Xue Qiang Zhao (Applied Soil Ecology, 2023)

Coenzyme Q0 defeats NLRP3-mediated inflammation, EMT/metastasis, and Warburg effects by inhibiting HIF-1α expression in human triple-negative breast cancer cells - Hsin-Ling Yang; Ping-Yu Lin; Chithravel Vadivalagan; Yi-An Lin; Kai-Yuan Lin; You-Cheng Hseu (Archives of Toxicology, 2023)

Human umbilical cord mesenchymal stem cell-derived exosomes carrying miR-1827 downregulate SUCNR1 to inhibit macrophage M2 polarization and prevent colorectal liver metastasis - Jierong Chen; Ziyue Li; Caifeng Yue; Jianhong Ma; Lixue Cao; Jiaxin Lin; Dandan Zhu; Ran An; Jinxin Lai; Yunmiao Guo; Bing Gu (Apoptosis, 2023)

The effect of dietary lecithin and lipid levels on the growth performance, body composition, hemolymph parameters, immune responses, body texture, and gene expression of juvenile white shrimp (Litopenaeus vannamei) - Chyng-Hwa Liou; Vu-An To; Zhong-Fu Zhang; Yu-Hung Lin (Aquaculture, 2023)

Astaxanthin, bile acid and chlorogenic acid attenuated the negative effects of high-fat diet on the growth, lipid deposition, and liver health of Oncorhynchus mykiss - Wei Zhao; Rong Yao; Han-Lin Wei; Yu-Cai Guo; An-Qi Chen; Bao-Yang Chen; Jin-Niu (Aquaculture, 2023)

Integrated optimization of real-time order acceptance and flexible job-shop rescheduling with multi-level imperfect maintenance constraints - Youjun An; Xiaohui Chen; Kaizhou Gao; Lin Zhang; Yinghe Li; Ziye Zhao (Swarm and Evolutionary Computation, 2023)

Do tillage systems affect the cadmium threshold in farmland soil for environmental quality standard setting? - Zhaolin Du; Weiqiang Dou; Dasong Lin; Li Qin; Yi An; Hongan Chen; Lina Wu; Liyan Mou (Science of The Total Environment, 2023)

Explication on distribution patterns of volatile organic compounds in petro-chemistry and oil refineries of China using a species-transport model and health risk assessment - Ting Zhang; Wei Kang; Xiang Ge; Qinhao Lin; Qiang Chen; Yingxin Yu; Taicheng An (Science of The Total Environment, 2023)

Thermomechanically micronized sugar beet pulp: Emulsification performance and the contribution of soluble elements and insoluble fibrous particles - Jiawei Lin; Zhong-Sheng Tang; Charles S. Brennan; Jayani Chandrapala; Wenhong Gao; Zhong Han; Xin-An Zeng (Food Research International, 2023)

Chronic exposure to di(2-ethylhexyl) phthalate (DEHP) weakens innate immunity and leads to immunosenescence in C. elegans - Pei-Ling Yen; Cai-Ru Yang; Mei-Lun Huang; Ting-An Lin; Vivian Hsiu-Chuan Liao (Environmental Toxicology and Pharmacology, 2023)

Behavior of solutes and membrane fouling in an electrodialysis to treat a side-stream: Migration of ions, dissolved organics and micropollutants - Byung Min An; Shine Lin Aung; Jihyeok Choi; Hoyoung Cha; Jinsoo Cho; Battuya Byambaa; Kyung Guen Song (Desalination, 2023)

Rational design of Multi-model ROS regulation Nano-platform for enhanced Mild-temperature photothermal therapy - Wenying Zhang; Meifang Wang; Bin Liu; Meng Yuan; Zhuang Yang; Jia Tan; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2023)

A new method for the determination of imidazole-like brown carbons using gas chromatography-mass spectrometry - Pingping Chen; Qinhao Lin; Taicheng An (Atmospheric Pollution Research, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Recent developments in horizontal gene transfer with the adaptive innovation of fermented foods - Ruhong Wang; Junrui Wu; Nan Jiang; Hao Lin; Feiyu An; Chen Wu; Xiqing Yue; Haisu Shi; Rina Wu (Critical Reviews in Food Science and Nutrition, 2023)

Effects of periodic drying-wetting on microbial dynamics and activity of nitrite/nitrate-dependent anaerobic methane oxidizers in intertidal wetland sediments - Feiyang Chen; Yuhui Niu; Zhirui An; Li Wu; Jie Zhou; Lin Qi; Guoyu Yin; Hongpo Dong; Xiaofei Li; Dengzhou Gao; Min Liu; Yanling Zheng; et al. (Water Research, 2023)

Enhanced sludge dewaterability by ferrate/ferric chloride: The key role of Fe(IV) on the changes of EPS properties - Wei Lin; Junmin Guo; Jie Zeng; Renglu Chen; Huu Hao Ngo; Jun Nan; Guibai Li; Jun Ma; An Ding (Science of The Total Environment, 2023)

Transcriptomic data recover a new superfamily-level phylogeny of Cucujiformia (Coleoptera, Polyphaga) - Ming-Long Yuan; Wen-Ting Chen; Qi-Lin Zhang; Min Li; Li Zhang; Pei-An Tang (Molecular Phylogenetics and Evolution, 2023)

Characterization of fibroblast growth factor receptor 4 (FGFR4) from the red swamp crayfish Procambarus clarkii and its role in antiviral and antimicrobial immune responses - Yan-Mei Zhang; Chen-Yang Lin; Bang-Ze Li; Wen-Bin Xu; Wei-Ren Dong; Miao-An Shu (Journal of Invertebrate Pathology, 2023)

Handwipes as indicators to assess organophosphate flame retardants exposure and thyroid hormone effects in e-waste dismantlers - Jian Tang; Shengtao Ma; Xin Hu; Meiqing Lin; Guiying Li; Yingxin Yu; Taicheng An (Journal of Hazardous Materials, 2023)

Goat milk-derived short chain peptides: Peptide LPYV as species-specific characteristic and their versatility bioactivities by MOF@Fe3O4@GO mesoporous magnetic-based peptidomics - Wei Jia; An Du; Zibian Fan; Lin Shi (Food Research International, 2023)

Elucidation of the cellulose nanocrystal-sugar beet pectin interactions for emulsification enhancement - Jiawei Lin; Zhong-Sheng Tang; Jayani Chandrapala; Charles Stephen Brennan; Zhong Han; Xin-An Zeng (Food Hydrocolloids, 2023)

Comprehensive application possibility: Construction hydrophilic, amphiphilic and hydrophobic system of modified zein by enzymatic or cysteine modification - An-Qi Zhang; Xiao-Yan Li; Bo-Hao Liu; Yu-Qi Yin; Han-Lin Zhang; Ying-Hua Zhang (Food Hydrocolloids, 2023)

The toxicity of nano polyethylene terephthalate to mice: Intestinal obstruction, growth retardant, gut microbiota dysbiosis and lipid metabolism disorders - Xiaoying Lin; Hongxin Xie; Yanfei Zhang; Xue Tian; Liwei Cui; Nianqiu Shi; Liming Wang; Jiating Zhao; Lihui An; Jing Wang; Bai Li; Yu-Feng Li (Food and Chemical Toxicology, 2023)

In vitro and in vivo anti-tumor activity of Antrodia salmonea against twist-overexpressing HNSCC cells: Induction of ROS-mediated autophagic and apoptotic cell death - Hsin-Ling Yang; Yi-An Lin; Sudhir Pandey; Jiunn-Wang Liao; Tzong-Der Way; Yu-lyu Yeh; Siang-Jyun Chen; You-Cheng Hseu (Food and Chemical Toxicology, 2023)

Iron–polyphenol dendritic complexes for regulating amplification of phenolic hydroxyl groups to improve magnetic resonance imaging - Ying Wan; Lu An; Zixuan Zhu; Qiwei Tian; Jiaomin Lin; Shiping Yang (Chemical Engineering Journal, 2023)

Effects of secondary impinging on flow features and mixing performance in T-T jet reactors - Haiyan Bie; Licheng Xue; Yue Wang; Zongrui Hao; Gang Liu; Yunxia Li; Zixin Lin; Weizhong An (Chemical Engineering Journal, 2023)

Research on type I kerogen molecular simulation and docking between kerogen and saturated hydrocarbon molecule during oil generation - Tian Liang; Zhao-Wen Zhan; Yan-Rong Zou; Xiao-Hui Lin; Yun Shan; Ping'’an Peng (Chemical Geology, 2023)

Molecular characteristics and compositions affecting light absorption features of cloud water revealed by Fourier transform ion cyclotron resonance mass spectrometry - Ziyong Guo; Wei Sun; Xiaodong Hu; Juying Lin; Yuzhen Fu; Xiaocong Peng; Bin Jiang; Yuhong Liao; Guohua Zhang; Xinming Wang; Ping'an Peng; Xinhui Bi (Atmospheric Environment, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

Attentional focus effect on dual-task walking in Parkinson’s disease with and without freezing of gait - Yu-An Chen; Ruey-Meei Wu; Chen-Hsing Sheu; Chin-Hsien Lin; Cheng-Ya Huang (GeroScience, 2023)

Fluid-structure interaction analysis on vibration characteristics of sleeve control valve - Zhen-hao Lin; Cong-wei Hou; Liang Zhang; An-qi Guan; Zhi-jiang Jin; Jin-yuan Qian (Annals of Nuclear Energy, 2023)

Marine environmental pollution and offshore aquaculture structure: Evidence from China - Bin Yuan; Yuhu Cui; Dong An; Zhaoxin Jia; Wenyan Ding; Lin Yang (Frontiers in Marine Science, 2023)
The marine environment pollution is becoming an important factor that restricts the sustainable development of mariculture in China. This study takes 10 Chinese coastal provinces (cities) as the study area, based on the rationalization and upgrading dimensions of industrial structure, and innovatively constructs an analytical framework of marine environmental pollution and offshore aquaculture structure to identify the intrinsic relationship between them; and introduces a spatial econometric model to alleviate the estimation bias caused by the public goods attribute of marine environment and improve the reliability of research conclusions. The results show that: (1) The rationalization of the offshore aquaculture structure in China is relatively weak, showing a “concentrated and contiguous” distribution pattern towards the developed aquaculture areas; at the same time, but the differences between regions are expanding; (2) The rationalization and upgrading of the offshore aquaculture structure are affected by the pollution of the marine environment. The degree of upgrading shows different trends; (3) There is a significant spatial adjacency and threshold effect of the negative impact of marine environmental pollution on offshore farming structure. However, due to the limitations of data, the accuracy of our data and the effectiveness of the measurement of industrial structure indicators still need to be improved. Therefore, governmental departments should consider the development of the surrounding areas as well as the pollution emission in the region, and jointly promote the optimization and adjustment of China’s offshore aquaculture structure through the construction of a coordinated management mechanism of marine pollution prevention and treatment.

Protolith origin of eclogites from the North Qaidam UHP metamorphic Belt, NW China: Implications for the breakup of the Rodinia supercontinent - Xiao-Dong Wang; Lin Ding; Deng Zeng; Ya-Hui Yue; Ling-Ping Yang; Zhe-Jun Wang; Lu-An Xiao; Chao Wang (Precambrian Research, 2023)

The largest rock avalanche in China at Iymek, Eastern Pamir, and its spectacular emplacement landscape - An-Wen Shi; Yu-Feng Wang; Qian-Gong Cheng; Qi-Wen Lin; Tian-Hua Li; Bernd Wünnemann (Geomorphology, 2023)

Molecular weight, chain length distribution and long-term retrogradation of cassava starch modified by amylomaltase - Hua-Tsung Lin; An-I Yeh; Tuan-Hua David Ho; Min-Hsiung Pan; Shih Hsin Chen (Food Hydrocolloids, 2023)

Bioaccumulation of Cd and comparative transcriptome analysis after the antagonism of Se in the hepatopancreas of estuary mud crab (Scylla paramamosain) - Yan-Mei Zhang; Chen-Yang Lin; Bang-Ze Li; Wei-Ren Dong; Miao-An Shu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Synthesis of N-doped sludge biochar using the hydrothermal route-enabled carbonization method for the efficient degradation of organic pollutants by peroxymonosulfate activation - Battuya Byambaa; Eun-Ju Kim; Mingizem Gashaw Seid; Byung-Min An; Jinsoo Cho; Shine Lin Aung; Kyung Guen Song (Chemical Engineering Journal, 2023)

Dual-targeting celecoxib nanoparticles protect intestinal epithelium and regulate macrophage polarization for ulcerative colitis treatment - Ruijie Chen; Xinlu Lin; Qian Wang; Xingsi An; Xinyu Zhao; Yujie Lin; Tuyue Sun; Chenyang Yan; Aimin Cai; Weilan Cao; Youting Zhang; Qing Yao; et al. (Chemical Engineering Journal, 2023)

Intimate interaction of TFSI− anions with MoO3−x oxygen vacancies boost ionic conductivity of cathode-supported solid polymer electrolyte - Rohan Paste; Chintam Hanmandlu; Po-Yu Su; Cheng-Hung Hou; Hsin-An Chen; Chun-Wei Pao; Jing-Jong Shyue; Kuei-Hsien Chen; Heng-Liang Wu; Hong-Cheu Lin; Chih Wei Chu (Chemical Engineering Journal, 2023)

One-step fabrication of self-healing poly(thioctic acid) coatings on ZE21B Mg alloys for enhancing corrosion resistance, anti-bacterial/oxidation, hemocompatibility and promoting re-endothelialization - Zhao-Qi Zhang; Pei-Duo Tong; Li Wang; Zheng-Hui Qiu; Jing-An Li; Hang Li; Shao-Kang Guan; Cun-Guo Lin; Hong-Yan Wang (Chemical Engineering Journal, 2023)

Correlation analysis between the occurrence of epidemic in ancient China and solar activity - Si Chen; Yong Wei; Xin’an Yue; Kaihua Xu; Mingkun Li; Wei Lin (Science China Earth Sciences, 2023)

Residues of polychlorinated biphenyls (PCBs) in a wild predatory fish from an e-waste site in South China between 2009 and 2016 - Chang-an Li; Si-sheng Li; Ying Zhang; Yichao Huang; Lin Tao (Environmental Science and Pollution Research, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Effects of exposure to phthalate during early pregnancy on gestational diabetes mellitus: a nested case–control study with propensity score matching - Wei Chen; Caidie He; Xiang Liu; Songlin An; Xia Wang; Lin Tao; Haonan Zhang; Yingkuan Tian; Nian Wu; Pei Xu; Dengqing Liao; Juan Liao; et al. (Environmental Science and Pollution Research, 2022)

Highly promoted phytoremediation with endophyte inoculation in multi-contaminated soil: plant biochemical and rhizosphere soil ecological functioning behavior - Chenjing Liu; Qian Song; Linhuazhi Ao; Nan Zhang; Haowen An; Hai Lin; Yingbo Dong (Environmental Science and Pollution Research, 2022)

Associations of exposure to lead and cadmium with risk of all-cause and cardiovascular disease mortality among patients with type 2 diabetes - Kai Zhu; Yuge Zhang; Qi Lu; Tingting Geng; Rui Li; Zhenzhen Wan; Xuena Zhang; Yujie Liu; Lin Li; Zixin Qiu; Meian He; Liegang Liu; et al. (Environmental Science and Pollution Research, 2022)

Aridity differentially alters the stability of soil bacterial and fungal networks in coastal and inland areas of Australia - Qing‐Lin Chen; Qian Xiang; An‐Qi Sun; Hang‐Wei Hu (Environmental Microbiology, 2022)
Despite the importance of soil bacterial and fungal communities for ecosystem services and human welfare, how their ecological networks respond to climatic aridity have yet been evaluated. Here, we collected soil samples from 47 sites across 2500 km in coastal and inland areas of eastern Australia with contrasting status of aridity. We found that the diversity of both bacteria and fungi significantly differed between inland and coastal soils. Despite the significant differences in soil nutrient availability and stoichiometry between the inland and coastal regions, aridity was the most important predictor of bacterial and fungal community compositions. Aridity has altered the potential microbial migration rates and further impacted the microbial assembly processes by increasing the importance of stochasticity in bacterial and fungal communities. More importantly, ecological network analysis indicated that aridity enhanced the complexity and stability of the bacterial network but reduced that of the fungal network, possibly due to the contrasting impacts of aridity on the community‐level habitat niche breadth and overlaps. Our work paves the way towards a more comprehensive understanding of how climate changes will alter soil microbial communities, which is integral to predicting their long‐term consequences for ecosystem sustainability and resilience to future disturbances.

How rainfalls influence urban traffic congestion and its associated economic losses at present and in future: taking cities in the Beijing-Tianjin-Hebei region, China for example? - Yi Zhou; Sicheng Mao; Haile Zhao; Guoliang Zhang; Xin Chen; Yuling Jin; Lin Xu; Zhihua Pan; Pingli An; Fei Lun (Theoretical and Applied Climatology, 2022)

New loci for refractive errors and ocular biometric parameters in young Chinese Han adults - Yunyun Sun; Zi-Bing Jin; Shifei Wei; Hongyan Jia; Kai Cao; Jianping Hu; Caixia Lin; Wenzai An; Jiyuan Guo; He Li; Jing Fu; Shi-Ming Li; et al. (Science China Life Sciences, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

Temperature has a strong impact on the abundance and community structure of comammox Nitrospira in an Ultisol - Mengmeng Feng; Zi-Yang He; Jianbo Fan; An-Hui Ge; Shengsheng Jin; Yongxin Lin; Ji-Zheng He (Journal of Soils and Sediments, 2022)

How Frequently Will the Persistent Heavy Rainfall over the Middle and Lower Yangtze River Basin in Summer 2020 Happen under Global Warming? - Zi-An Ge; Lin Chen; Tim Li; Lu Wang (Advances in Atmospheric Sciences, 2022)

Towards less invasive molecular diagnostics for endometrial cancer: massively parallel sequencing of endometrial lavage specimens in women attending for an office hysteroscopy - Angel Chao; Kai-Yun Wu; Chiao-Yun Lin; Yun-Shien Lee; Huei-Jean Huang; Yun-Hsin Tang; Cindy Hsuan Weng; An-Shine Chao; Ting-Chang Chang; Chyong-Huey Lai; Ren-Chin Wu (Journal of Molecular Medicine, 2022)

Adapting to climate risks through cross-border investments: industrial vulnerability and smart city resilience - Yao An; Ning Liu; Lin Zhang; Huanhuan Zheng (Climatic Change, 2022)

Modeling and Dynamic Analysis of a Triple-Tagline Anti-Swing System for Marine Cranes in an Offshore Environment - Maokai Sun; Shenghai Wang; Guangdong Han; Lin An; Haiquan Chen; Yuqing Sun (Journal of Marine Science and Engineering, 2022)
Payload lifting is inefficient and high-risk under rough sea conditions. Thus, it is not easy to achieve precise assembly, and the swing payload is liable to collide with other structures on deck and cause damage. In this paper, to explore the complex dynamic characteristics of a triple-tagline anti-swing system (TTAS) for marine cranes in an offshore environment, an irregular wave model was first integrated into a dynamic system model of TTAS, and the TTAS for offshore payload lifting was simplified as a constrained-pendulum system with moving base excitations. Further, the dynamic system model was established by applying the methods in robotics. Meanwhile, the dynamic characteristics were simulated and analyzed using Matlab/Simulink. The simulation results show that the in-plane angle and out-of-plane angle of the payload can be effectively suppressed, and the range of the two-dimensional trajectory of the payload is greatly reduced. The research results provide a theoretical basis for optimizing the mechanical structures of TTAS or similar equipment.

IL-38, a potential therapeutic agent for lupus, inhibits lupus progression - Wang-Dong Xu; Lin-Chong Su; Lu Fu; You-Yu Lan; Xiao-Yan Liu; Qi Huang; Qian Wu; Jie Zhou; An-Fang Huang (Inflammation Research, 2022)

Influence of asymmetric blockage of the drainage system of a deep-buried tunnel on water gushing - He-lin Fu; Peng-tao An; Yi-min Wu; Jie Li; Long Chen (Journal of Mountain Science, 2022)

Evaluation and Temporal-Spatial Deconstruction for High-Quality Development of Regional Marine Economy: A Case Study of China - Dong An; Chunlei Shen; Lin Yang (Frontiers in Marine Science, 2022)
The high-quality development of the marine economy has become a realistic choice to stimulate the vitality of regional economic growth and achieve the goal of building a powerful nation in the marine economy. This study constructs an evaluation index system from efficiency, coordination, innovation, sustainability, openness, and shareability to analyze the high-quality development level and temporal-spatial heterogeneity of China’s regional marine economy from 2010 to 2018. Methods used in this paper are entropy, kernel density estimation, and partial spatial autocorrelation analysis. The results are shown as follows: (1) The high-quality development level of China’s regional marine economy shows a slow fluctuating and upward trend, coordination, sustainability, and innovation are the primary driving forces. The ranking of the three marine economic circles in the development quality of the marine economy is Eastern> Southern>Northern, the ranking of coastal provinces is Guangdong> Shanghai> Shandong> Zhejiang> Fujian> Tianjin> Jiangsu> Liaoning> Hainan> Hebei> Guangxi. The primary driving forces for Guangdong, Shanghai, Shandong, and Zhejiang leading other coastal areas are openness, efficiency, innovation, and sustainability respectively; (2) the temporal differentiation of China’s regional marine economy shows a dynamic evolution process that is obvious in the early stages, alleviating in the middle stage, and balance in the later stage; (3) the spatial zoning types and high-quality development paths of 11 coastal provinces are determined based on spatial differentiation: Shanghai and Zhejiang are high-value congregate types and named as demonstration regions, which should build global marine center cities with deepening regional cooperation and high-standard opening-up; Shandong and Guangdong are high-value discrete types and named as key engine regions, which should enhance the international competitiveness of the marine industry with scientific and technological innovation; Tianjin, Hebei, and Liaoning are low-value congregate types and named as potential zooming regions, which should improve the efficiency of marine resources utilization with regional cooperation; Jiangsu, Fujian, Hainan, and Guangxi are low-value discrete types and named as land-sea coordination regions, which should build a modern and characteristic marine industrial system coordinated with land and sea.

Hasubanan alkaloids with anti-inflammatory activity from Stephania longa - Hui Liu; Wan-Qin Liao; Rong-Xiao Lin; Lixia Fan; Jinyan Sun; Hong-Yuan Chen; Fang Liu; An-Ping Yang (Natural Product Research, 2022)

Fine mapping qKRN5.04 provides a functional gene negatively regulating maize kernel row number - Yixin An; Lin Chen; Yong-Xiang Li; Chunhui Li; Yunsu Shi; Dengfeng Zhang; Yu Li; Tianyu Wang (Theoretical and Applied Genetics, 2022)

Advanced Treatment Technologies for the Removal of Organic Chemical Sunscreens from Wastewater: a Review - ‬Huu-Tuan Tran; Bao-Trong Dang; Le Thi Thu Thuy; Hong-Giang Hoang; Xuan-Thanh Bui; Van-Giang Le; Chitsan Lin; Minh-Ky Nguyen; Kim-Qui Nguyen; Phuong-Thao Nguyen; Quach An Binh; Thi-Phuong Thuy Bui (Current Pollution Reports, 2022)

Zkscan3 affects erythroblast development by regulating the transcriptional activity of GATA1 and KLF1 in mice - Zixuan Li; Binjie Sheng; Tingting Zhang; Tian Wang; Dan Chen; Gangli An; Xingbing Wang; Huimin Meng; Lin Yang (Journal of Molecular Histology, 2022)
ZKSCAN3 encodes a zinc-finger transcription factor that regulates the expression of important genes and plays a significant role in tumor development, pathogenesis, and metastasis. However, its biological functions under normal physiological conditions remain largely unknown. In our previous studies, using flow cytometry, we found that the deletion of Zkscan3 may cause abnormal erythropoiesis. In this study, we found that, in a Zkscan3 knockout mice model, the number of splenic early-stage (basophilic-erythroblasts) and late-stage (chromatophilic-erythroblasts to polychromatophilic-erythroblasts through orthochromatophilic-erythroblasts) erythroblasts increased, whereas the number of late erythroblasts in the bone marrow decreased. Moreover, the phenotype was exacerbated after treating mice with phenylhydrazine (PHZ), which causes severe hemolytic anemia. In the knockout mice treated with PHZ, the percentage of reticulocyte in the peripheral blood conspicuously increased, whereas MCHC and red blood cells decreased. Then, we performed RNA-seq and quantitative-polymerase chain reaction assay and found that the expression of GATA1 and Tiam1 in erythroblasts were upregulated, whereas KLF1 was downregulated. Luciferase assays showed that Zkscan3 inhibited the transcription of GATA1 and Tiam1 and promoted the expression of KLF1 . Additionally, ChIP and CO-IP results confirmed that Zkscan3 directly interacts with GATA1 and inhibits its transcriptional activity in MEL cells. Our results demonstrate, for the first time, the significant role of Zkscan3 in physiological erythropoiesis through the interaction with GATA1, both at the DNA and protein level, and with Tiam1 and KLF1 at the DNA level.

The impact of Alzheimer's disease susceptibility loci on lateral ventricular surface morphology in older adults - Shan Li; Na An; Nan Chen; Yin Wang; Lin Yang; Yalin Wang; Zhijun Yao; Bin Hu (Brain Structure and Function, 2022)

The significance of riparian communities in the energy flow of subtropical stream ecosystems - Yi-Chang Liao; An-Cheng Lin; Han-Ni Tsai; Yu-Ting Yen; Chyng-Shyan Tzeng; Man-Miao Yang; Hsing-Juh Lin (Aquatic Sciences, 2022)

Regional characteristics and exploitation potential of atmospheric water resources in China - Lin An; Zhanyu Yao; Pei Zhang; Shuo Jia; Jieyun Zhao; Liangshu Gao; Zhen Liu (International Journal of Climatology, 2022)
The atmospheric water resources (AWR) in China have evident regional characteristics. In order to scientifically and rationally exploit the AWR in different regions of China, we divided China into seven regions based on the ERA‐5, the CloudSat data, and so on. Such characteristics as water vapour, cloud characteristics, cloud water resources (CWR), precipitation efficiency of hydrometeors (PEh), and the exploitation potential of CWR were studied in this article. Some results in summer are shown. (a) There were relatively more precipitation, richer water vapour, stronger water vapour transport and convergence, more cloud covers, and relatively larger zones of rich total column cloud water content in China. Therefore, it is of important significance to study AWR in summer in China. (b) In respect of single‐layer clouds, low clouds were in the majority over the Tibetan Plateau (TP) and the southwest China (SW), medium clouds were predominant over the northern regions, and high clouds existed more over the central region (CR) and the southeast China (SE). The liquid water content (LWC) at each height of cloud was less than 800 mg·m −3 and decreased gradually with the increase in height in China. The convective development heights, the LWC at each altitude, and the frequencies of less LWCs over the northern regions were lower than those over the southern regions. The ice water content (IWC) at each height of cloud was less than 250 mg·m −3 , and more than 96% of them were less than 100 mg·m −3 . (c) CWR over the northeast China (NE), north China (NC), and CR were relatively rich, but with relatively low PEh, so there was relatively higher exploitation potential of CWR in these regions, followed by the northwest China (NW) and TP, and there was still some exploitation potential of CWR in SE and SW.

Towards a rapid assessment of highway slope disasters by using multidisciplinary techniques - Meng-Chia Weng; Cheng-Han Lin; Wen-Jie Shiu; Wei-An Chao; Chia-Chi Chiu; Ching-Fang Lee; Wei-Kai Huang; Che-Ming Yang (Landslides, 2022)
Mega-earthquakes and extreme climate events accompanied by intrinsic fragile geology lead to numerous landslides along mountain highways in Taiwan, causing enormous life and economic losses. In this study, a system for rapid slope disaster information integration and assessment is proposed with the aim of providing information on landslide occurrence, failure mechanisms, and subsequent landslide-affected areas to the highway authority rapidly. The functionality of the proposed system is deployed into three units: (1) geohazard rapid report (GeoPORT I), (2) multidisciplinary geological survey report (GeoPORT II), and (3) site-specific landslide simulation report (GeoPORT III). After landslide occurrence, the seismology-based monitoring network rapidly provides the initial slope disaster information, including preliminary location, event magnitude, earthquake activity, and source dynamics, within an hour. Within 3 days of the landslide, a multidisciplinary geological survey is conducted to collect high-precision topographical, geological, and remote-sensing data to determine the possible failure mechanism. After integrating the aforementioned information, a full-scale three-dimensional landslide simulation based on the discrete element method is performed within 10 days to reveal the failure process and to identify the areas potentially affected by subsequent disasters through scenario modeling. Overall, the proposed system can promptly provide comprehensive and objective information to relevant authorities after the event occurrence for hazard assessment. The proposed system was validated using a landslide event in the Central Cross-Island Highway of Taiwan.

Perchlorate contamination of tea leaves and a corresponding probabilistic dietary risk assessment using Monte Carlo simulation - Qinghua Yao; Sun-an Yan; Wenjing Liu; Minmin Huang; Qiu Lin (Food Additives & Contaminants: Part A, 2022)

Pathogenicity and genome-wide sequence analysis reveals relationships between soybean mosaic virus strains - Le Gao; Yueying Wu; Jie An; Wenxuan Huang; Xinlei Liu; Yongguo Xue; Xiaoyan Luan; Feng Lin; Lianjun Sun (Archives of Virology, 2022)

Evaluation of surface albedo over the Tibetan Plateau simulated by CMIP5 models using in‐situ measurements and MODIS - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Shaoying Wang; Lunyu Shang; Hao Chen; Shihua Lyu (International Journal of Climatology, 2022)
Surface albedo plays a key role in the energy and water cycles, and reasonable parameterizations of surface albedo will be greatly helpful to improve the simulation of radiation partition in climate models. In‐situ measurements of albedo from five sites over the Tibetan Plateau (TP) and MODIS albedo product are used to evaluate monthly, annual, and seasonal variations of the surface albedo simulated by 24 Global Climate Models (GCMs) archived by the Coupled Model Intercomparison Project Phase 5 (CMIP5). Potential factors contributing to the bias of simulated albedo were investigated. The results show that the monthly albedo of 24 GCMs varied across models, and the difference among the models was smaller in the June–July–August period than the December–January–February period. The ensemble mean albedo of the 24 GCMs was more consistent with the in‐situ measurements than the individual model. The albedo calculated from the BNU‐ESM, GFDL‐CM3, INM‐CM4, MIROC4h, MIROC‐ESM, and MIROC‐ESM‐CHEM models coincided with the observations from June to September, increasing rapidly to above 0.4 from November. However, the annual cycle of surface albedo was insignificant when simulated by some models, such as CanESM2, CSIRO‐Mk3.6.0, CMCC‐CMS, IPSL‐CM5A‐MR, and MPI‐ESM‐MR. Additionally, the surface albedo was overestimated by CMIP5 multi‐model ensemble mean—with a smaller amplitude of daily albedo—compared with the values estimated from in‐situ observations and MCD43A3. In all 24 models, snow albedo parameterization schemes were found to variably fit the attenuation of snow albedo over time. The cold temperature, relatively more precipitation, fresh snow density, and albedo in these models led to large biases in snow depth and ablation. The surface albedo tends to increase without the influence of blowing snow and withered grass on the model's albedo.

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Differential Affinities of a Pocillopora damicornis Galectin to Five Genera of Symbiodiniaceae at Different Temperatures - Xingjuan Wang; Zhongjie Wu; Yibo Wu; Mingxun An; Zhi Zhou; Senjie Lin (Frontiers in Marine Science, 2021)
The symbiosis of coral-Symbiodiniaceae is the quintessential basis of the coral reef ecosystem, and its breakdown results in coral bleaching, one of the most severe ecological catastrophes in the ocean. Critical to the establishment of the symbiosis is the host’s specific recognition of the symbionts through the binding of the coral host’s pattern recognition receptors (PRRs) to the symbiont cell surface’s glycoconjugates. However, the molecular basis for this recognition process is poorly understood. The present study investigated the binding affinities of the coral galectin PdGLT-1 to different symbiodiniacean species under different temperatures. At 25°C, the PdGLT-1 recombinant protein (rPdGLT-1) exhibited different binding affinities to different symbiodiniacean species from five genera, with a significantly higher binding affinity ( p < 0.05) to Fugacium kawagutii (2.6-fold) and Cladocopium goreaui (1.9-fold) than Symbiodinium microadriaticum . The binding topology of rPdGLT-1 differed among the five symbiodiniacean species; for S. microadriaticum , Breviolum minutum , and Durusdinium trenchii , the binding was on some specific sites on the cell surface, whereas for C. goreaui and F. kawagutii , the binding signals were detected over the whole cell surface. Interestingly, PdGLT-1 binding induced agglutination of F. kawagutii cells but not of C. goreaui , explaining why C. goreaui was the most dominant symbiodiniacean symbionts in corals. Moreover, the affinity of rPdGLT-1 to Symbiodiniaceae was affected by temperature, and the highest binding affinities were observed at 30, 20, 30, 35, and 30°C for S. microadriaticum , B. minutum , C. goreaui , D. trenchii , and F. kawagutii , respectively. The optimal binding temperatures were consistent with the current understanding that D. trenchii was the most thermal resistant among these species. These results suggest that the binding affinity of the PRR PdGLT-1 may determine the specificity of host-symbiont pairing and explain why Cladocopium is the dominant symbionts of coral P. damicornis at normal temperature, and corals with Durusdinium symbionts may survive better at high temperature.

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Bioinformatics-based study to identify immune infiltration and inflammatory-related hub genes as biomarkers for the treatment of rheumatoid arthritis - Sheng Fang; Xin Xu; Lin Zhong; An-quan Wang; Wei-lu Gao; Ming Lu; Zong-Sheng Yin (Immunogenetics, 2021)

Paternal exposure to microcystin-LR induces fetal growth restriction partially through inhibiting cell proliferation and vascular development in placental labyrinth - Lan Gao; An-Qi Cui; Jing Wang; Jing Chen; Xiao-Yi Zhang; Zhi-Jing Lin; Yuan-Hua Chen; Cheng Zhang; Hua Wang; De-Xiang Xu (Environmental Science and Pollution Research, 2021)

Streptococcus vaginalis sp. nov., a novel bacterial species isolated from vaginal swabs of a pregnant woman with diabetes - An-Shine Chao; Chiao-Yun Lin; Angel Chao; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Yi-Sheng Chen (Archives of Microbiology, 2021)

Population, Reproductive and Fishery Dynamics of Spotted Box Crab (Calappa philargius), a New Claw-Only Fishery Species, in the Southern Taiwan Strait, China - Bai-an Lin; Yan Jiang; Robert Boenish; Qing Xu; Min Liu (Frontiers in Marine Science, 2021)
The spotted box crab Calappa philargius (Calappidae) is an increasingly consumed species in China, mainly sourced from a claw-only fishery. Being a not well-characterized species in the literature, this study is warranted to inform sustainable management approaches. Here we report on the first in-depth overview on biology and fishery dynamics of C. philargius in the southern Taiwan Strait of China. Whole body crabs ( N = 1,009) were collected monthly from January to December 2019 from trawlers, operating in the southern Taiwan Strait; sample collection was absent from May to July because of the national fishing moratorium regulation. Sex ratio, growth pattern, size at maturity and fecundity were estimated. The overall male: female ratio was 1: 1.47, significantly differing from the 1: 1 ( p < 0.01); monthly sex ratio variations were also significant ( p < 0.01), suggesting possible seasonal sexual segregation. We found the carapace widths (CW) of males were significantly larger than those of females ( p < 0.01). Based on the occurrence and percentages of berried females, we identified twin spawning events in January–April and August–October with the overall peak occurring in February. Size at 50% female maturity was 11.47 cm CW. Female absolute fecundity was significantly related to CW via a power function relationship ( N = 14, p < 0.01). The estimated average claw yield was 36.28 ± 3.07% of the whole body weight ( N = 95), irrespective of sex and size ( p > 0.5). Capture and trade data of C. philargius using trawl and trap fishing gears were documented to characterize claw-only fishery dynamics for future research and sustainable use.

Circ_0020093 ameliorates IL-1β-induced apoptosis and extracellular matrix degradation of human chondrocytes by upregulating SPRY1 via targeting miR-23b - Mingli Feng; Lin Jing; Jingbo Cheng; Shuai An; Jiang Huang; Qi Yan (Molecular and Cellular Biochemistry, 2021)
Osteoarthritis (OA) is a chronic disease characterized by articular cartilage degeneration and uncontrolled chondrocyte apoptosis. At present, accumulating evidence introduces that circular RNA (circRNA) is involved in the development of OA. The aim of our study was to explore the role and the functional mechanism of circ_0020093 in OA cell model. Human chondrocytes were treated with interleukin-1 beta (IL-1β) to construct OA model. The expression of circ_0020093, miR-23b, and Sprouty 1 (SPRY1) mRNA was measured by quantitative real-time polymerase chain reaction (qRT-PCR). Cell apoptosis was assessed by flow cytometry assay. The expression of extracellular matrix (ECM)-associated markers and SPRY1 protein level was detected by qRT-PCR and Western blot. Bioinformatics analysis-predicted relationship between miR-23b and circ_0020093 or SPRY1 was further verified by dual-luciferase reporter assay and RNA pull-down assay. In this study, we found that the expression of circ_0020093 and SPRY1 was declined, while miR-23b expression was elevated in IL-1β-treated chondrocytes. IL-1β induced chondrocyte apoptosis and ECM degradation, while these negative effects were alleviated by circ_0020093 overexpression or miR-23b inhibition. MiR-23b was a target of circ_0020093, and SPRY1 was a downstream target of miR-23b. Rescue experiments showed that miR-23b enrichment reversed the role of circ_0020093 overexpression, and SPRY1 knockdown also reversed the effects of miR-23b inhibition. Importantly, circ_0020093 positively regulated SPRY1 expression by targeting miR-23b. In conclusion, circ_0020093 ameliorates IL-1β-induced apoptosis and ECM degradation of human chondrocytes by regulating the miR-23b/SPRY1 axis.

A Possible Role of Allatostatin C in Inhibiting Ecdysone Biosynthesis Revealed in the Mud Crab Scylla paramamosain - An Liu; Wenyuan Shi; Dongdong Lin; Haihui Ye (Frontiers in Marine Science, 2021)
C-type allatostatins (C-type ASTs) are a family of structurally related neuropeptides found in a wide range of insects and crustaceans. To date, the C-type allatostatin receptor in crustaceans has not been deorphaned, and little is known about its physiological functions. In this study, we aimed to functionally define a C-type ASTs receptor in the mud crab, Scylla paramamosian . We showed that C-type ASTs receptor can be activated by Scypa AST-C peptide in a dose-independent manner and by Scypa AST-CCC peptide in a dose-dependent manner with an IC 50 value of 6.683 nM. Subsequently, in vivo and in vitro experiments were performed to investigate the potential roles of Scypa AST-C and Scypa AST-CCC peptides in the regulation of ecdysone (20E) and methyl farnesoate (MF) biosynthesis. The results indicated that Scypa AST-C inhibited biosynthesis of 20E in the Y-organ, whereas Scypa AST-CCC had no effect on the production of 20E. In addition, qRT-PCR showed that both Scypa AST-C and Scypa AST-CCC significantly decreased the level of expression of the MF biosynthetic enzyme gene in the mandibular organ, suggesting that the two neuropeptides have a negative effect on the MF biosynthesis in mandibular organs. In conclusion, this study provided new insight into the physiological roles of AST-C in inhibiting ecdysone biosynthesis. Furthermore, it was revealed that AST-C family peptides might inhibit MF biosynthesis in crustaceans.

Effects of Fatigue on Inter-joint Coordination in Ballet Dancers During a Ballet Jumping Movement (petit échappé sauté) - Chai-Wei Lin; Jeng-Feng Yang; Yi-An Chen; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2021)

Deficiency of Klc2 Induces Low-Frequency Sensorineural Hearing Loss in C57BL/6 J Mice and Human - Xiaolong Fu; Yachun An; Hongyang Wang; Peipei Li; Jing Lin; Jia Yuan; Rongyu Yue; Yecheng Jin; Jiangang Gao; Renjie Chai (Molecular Neurobiology, 2021)

Estimation and Long-term Trend Analysis of Surface Solar Radiation in Antarctica: A Case Study of Zhongshan Station - Zhaoliang Zeng; Zemin Wang; Minghu Ding; Xiangdong Zheng; Xiaoyu Sun; Wei Zhu; Kongju Zhu; Jiachun An; Lin Zang; Jianping Guo; Baojun Zhang (Advances in Atmospheric Sciences, 2021)

GABA Signaling Pathway-associated Gene PLCL1 Rare Variants May be Associated with Autism Spectrum Disorders - Fengyun Zheng; Guoyuan Liu; Ting Dang; Qiaowen Chen; Yu An; Meng Wu; Xiangxuan Kong; Zilong Qiu; Bai-Lin Wu (Neuroscience Bulletin, 2021)

Nucleophosmin/B23 promotes endometrial cancer cell escape from macrophage phagocytosis by increasing CD24 expression - Chiao-Yun Lin; Chia-Lung Tsai; Angel Chao; Li-Yu Lee; Wei-Chun Chen; Yun-Hsin Tang; An-Shine Chao; Chyong-Huey Lai (Journal of Molecular Medicine, 2021)

Evaluation of Shale Reservoir Quality by Geophysical Logging for Shuijingtuo Formation of Lower Cambrian in Yichang Area, Central Yangtze - Xiaohong Chen; Lin Chen; Shu Jiang; An Liu; Shengyuan Luo; Hai Li; Peijun Li; Ping Chen (Journal of Earth Science, 2021)

Effects of diethyl aminoethyl hexanoate on the physiology and selenium absorption of grape seedlings - Lei Liu; Jiaxi Han; Lili Deng; Huixuan Zhou; Yuhui Bie; Qianhe Jing; Lijin Lin; Jin Wang; Ming’an Liao (Acta Physiologiae Plantarum, 2021)

Glaciibacter flavus sp. nov., isolated from a lichen sample - De-Feng An; Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Ming-Guo Jiang; Lei Lang; Li-Song Wang; Johannes F. Imhoff; Cheng-Lin Jiang; Yi Jiang (Archives of Microbiology, 2021)

Effects of mutual grafting Solanum photeinocarpum from two ecosystems on physiology and selenium absorption of their offspring under selenium stress - Kewen Huang; Yan Wang; Xiaohan Wei; Yuhui Bie; Huixuan Zhou; Lili Deng; Lijin Lin; Ming’an Liao (Acta Physiologiae Plantarum, 2021)

Characterization Of Secondary Metabolites From The Rhizome Of Cynara Scolymus And Their Antioxidant Properties - Chia-Lin Lee; Kuo-Chen Liao; Chien-Chih Chen; Yen-An Lin; Tung-Ying Wu; Yun-Lian Jhan; Chao-Jung Chen; Juan-Cheng Yang; Yang-Chang Wu (Natural Product Research, 2021)

Identification of Regeneration and Hub Genes and Pathways at Different Time Points after Spinal Cord Injury - Sheng Fang; Lin Zhong; An-quan Wang; Hui Zhang; Zong-Sheng Yin (Molecular Neurobiology, 2021)

Removal of Mn(II) by a nitrifying bacterium Acinetobacter sp. AL-6: efficiency and mechanisms - Qiang An; Lin Jin; Shuman Deng; Zheng Li; Chenyi Zhang (Environmental Science and Pollution Research, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Effects of indole acetic acid on the growth and selenium absorption characteristics of Cyphomandra betacea seedlings - Yunmin Huan; Liu Yang; Qin Liu; Lijin Lin; Ming’an Liao; Zhihui Wang; Dong Liang; Hui Xia; Yi Tang; Xiulan Lv; Jin Wang (Acta Physiologiae Plantarum, 2021)

Mesenchymal Stromal Cell-Derived Extracellular Vesicles in the Treatment of Diabetic Foot Ulcers: Application and Challenges - Tao An; Yi Chen; Yingchun Tu; Ping Lin (Stem Cell Reviews and Reports, 2021)

Kidney function change after transcatheter aortic valve replacement in patients with diabetes and/or hypertension - Jiaqi Fan; Changjie Yu; Kaida Ren; Wanbing Lin; Stella Ng; Zexin Chen; Xinping Lin; Lihan Wang; Qifeng Zhu; Yuxin He; Jubo Jiang; Xianbao Liu; et al. (Journal of Zhejiang University-SCIENCE B, 2021)

The regional difference in engineering-control and tillage factors of Chinese Soil Loss Equation - Rui-yin Chen; Dong-chun Yan; An-bang Wen; Zhong-lin Shi; Jia-cun Chen; Yuan Liu; Tai-li Chen (Journal of Mountain Science, 2021)

Warming Iron-Limited Oceans Enhance Nitrogen Fixation and Drive Biogeographic Specialization of the Globally Important Cyanobacterium Crocosphaera - Nina Yang; Carlin A. Merkel; Yu-An Lin; Naomi M. Levine; Nicholas J. Hawco; Hai-Bo Jiang; Ping-Ping Qu; Michelle A. DeMers; Eric A. Webb; Fei-Xue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
Primary productivity in the nutrient-poor subtropical ocean gyres depends on new nitrogen inputs from nitrogen fixers that convert inert dinitrogen gas into bioavailable forms. Temperature and iron (Fe) availability constrain marine nitrogen fixation, and both are changing due to anthropogenic ocean warming. We examined the physiological responses of the globally important marine nitrogen fixer, Crocosphaera watsonii across its full thermal range as a function of iron availability. At the lower end of its thermal range, from 22 to 27°C, Crocosphaera growth, nitrogen fixation, and Nitrogen-specific Iron Use Efficiencies (N-IUEs, mol N fixed hour –1 mol Fe –1 ) increased with temperature. At an optimal growth temperature of 27°C, N-IUEs were 66% higher under iron-limited conditions than iron-replete conditions, indicating that low-iron availability increases metabolic efficiency. However, Crocosphaera growth and function decrease from 27 to 32°C, temperatures that are predicted for an increasing fraction of tropical oceans in the future. Altogether, this suggests that Crocosphaera are well adapted to iron-limited, warm waters, within prescribed limits. A model incorporating these results under the IPCC RCP 8.5 warming scenario predicts that Crocosphaera N-IUEs could increase by a net 47% by 2100, particularly in higher-latitude waters. These results contrast with published responses of another dominant nitrogen fixer ( Trichodesmium ), with predicted N-IUEs that increase most in low-latitude, tropical waters. These models project that differing responses of Crocosphaera and Trichodesmium N-IUEs to future warming of iron-limited oceans could enhance their current contributions to global marine nitrogen fixation with rates increasing by ∼91 and ∼22%, respectively, thereby shifting their relative importance to marine new production and also intensifying their regional divergence. Thus, interactive temperature and iron effects may profoundly transform existing paradigms of nitrogen biogeochemistry and primary productivity in open ocean regimes.

The adaptability of typical precipitation ensemble prediction systems in the Huaihe River basin, China - Han Wang; Ping-an Zhong; Fei-lin Zhu; Qing-wen Lu; Yu-fei Ma; Sun-yu Xu (Stochastic Environmental Research and Risk Assessment, 2021)

Changes in arthropod community but not plant quality benefit a specialist herbivore on plants under reduced water availability - Po-An Lin; Chia-Ming Liu; Jia-Ang Ou; Cheng-Han Sun; Wen-Po Chuang; Chuan-Kai Ho; Natsuko Kinoshita; Gary W. Felton (Oecologia, 2021)

Evaluation and application of an efficient plant DNA extraction protocol for laboratory and field testing - Qi Wang; Xiaoxia Shen; Tian Qiu; Wei Wu; Lin Li; Zhi’an Wang; Huixia Shou (Journal of Zhejiang University-SCIENCE B, 2021)

First report of turnip mosaic virus on yellow passion fruit in China - Li Juan Chen; Xing Xing Zhang; Ying Lin Lu; Yu Xing An (Journal of Plant Pathology, 2021)

Paracoccus lichenicola sp. nov., Isolated from Lichen - Lei Lang; De-Feng An; Long-Qian Jiang; Gui-Ding Li; Li-Song Wang; Xin-Yu Wang; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

Multifractal characteristics and spatial variability of soil particle-size distribution in different land use patterns in a small catchment of the Three Gorges Reservoir Region, China - Tai-li Chen; Zhong-lin Shi; An-bang Wen; Dong-chun Yan; Jin Guo; Jia-cun Chen; Yuan Liu; Rui-yin Chen (Journal of Mountain Science, 2021)

Hepato-protective effect of fucoidan extracted from acid-processed Sargassum fusiformis in ethanol-treated Chang liver cells and in a zebrafish model - Yu-Lin Dai; Yun-Fei Jiang; Yu-Hang Nie; Yu-An Lu; Min-Cheol Kang; You-Jin Jeon (Journal of Applied Phycology, 2020)

Functional human brain connectivity during labor and its alteration under epidural analgesia - Fan-Pei Yang; An-Shine Chao; Sung-Han Lin; Anne Chao; Tzu-Hao Wang; Yao-Lung Chang; Hong-Shiu Chang; Jiun-Jie Wang (Brain Imaging and Behavior, 2020)

First report of ramie mosaic virus on passion fruit in Guangdong, southern China - Li Juan Chen; Dong Lei Sun; Ying Lin Lu; Yu Xing An (Journal of Plant Pathology, 2020)

Effects of intercropping accumulator plants and applying their straw on the growth and cadmium accumulation of Brassica chinensis L. - Yi Tang; Liming Wang; Yongdong Xie; Xuena Yu; LiJin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Guochao Sun; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2020)

A Novel Assessment of Baroreflex Activity Through the Similarity of Ternary Codes of Oscillations Between Arterial Blood Pressure and R–R Intervals - Po-Wei Chen; Chun-Keng Lin; Wei-Min Liu; Yu-Chen Chen; Sheng-Tzung Tsai; An-Bang Liu (Journal of Medical and Biological Engineering, 2020)

Simulation and Improvements of Oceanic Circulation and Sea Ice by the Coupled Climate System Model FGOALS-f3-L - Yuyang Guo; Yongqiang Yu; Pengfei Lin; Hailong Liu; Bian He; Qing Bao; Bo An; Shuwen Zhao; Lijuan Hua (Advances in Atmospheric Sciences, 2020)

Evaluating the severity of building fires with the analytical hierarchy process, big data analysis, and remote sensing - Ching-An Lee; Yu-Chi Sung; Yuan-Shang Lin; Gary Li-Kai Hsiao (Natural Hazards, 2020)

Asymmetric Responses to Climate Change: Temperature Differentially Alters Herbivore Salivary Elicitor and Host Plant Responses to Herbivory - Sulav Paudel; Po-An Lin; Kelli Hoover; Gary W. Felton; Edwin G. Rajotte (Journal of Chemical Ecology, 2020)
The effect of temperature on insect-plant interactions in the face of changing climate is complex as the plant, its herbivores and their interactions are usually affected differentially leading to an asymmetry in response. Using experimental warming and a combination of biochemical and herbivory bioassays, the effects of elevated temperatures and herbivore damage ( Helicoverpa zea) on resistance and tolerance traits of Solanum lycopersicum var. Better boy (tomato), as well as herbivory performance and salivary defense elicitors were examined. Insects and plants were differentially sensitive towards warming within the experimental temperature range. Herbivore growth rate increased with temperature, whereas plants growth as well as the ability to tolerate stress measured by photosynthesis recovery and regrowth ability were compromised at the highest temperature regime. In particular, temperature influenced the caterpillars’ capacity to induce plant defenses due to changes in the amount of a salivary defense elicitor, glucose oxidase (GOX). This was further complexed by the temperature effects on plant inducibility, which was significantly enhanced at an above-optimum temperature; this paralleled with an increased plants resistance to herbivory but significantly varied between previously damaged and undamaged leaves. Elevated temperatures produced asymmetry in species’ responses and changes in the relationship among species, indicating a more complicated response under a climate change scenario.

(–)-β-Homoarginine anhydride, a new antioxidant and tyrosinase inhibitor, and further active components from Trichosanthes truncata - I-Ting Weng; Yen-An Lin; Guan-Yu Chen; Hsiu-Mei Chiang; Yi-Jung Liu; Chao-Jung Chen; Yu-Hsuan Lan; Chia-Lin Lee (Natural Product Research, 2020)

Dietary risk assessment of pesticide residues on Tremella fuciformis Berk (snow fungus) from Fujian Province of China - Qinghua Yao; Sun-an Yan; Hanzhen Chen; Jie Li; Qiu Lin (Food Additives & Contaminants: Part A, 2020)

Alfalfa MsCBL4 enhances calcium metabolism but not sodium transport in transgenic tobacco under salt and saline–alkali stress - Yimin An; Xiao-Xue Yang; Lishuang Zhang; Jun Zhang; Binghao Du; Lin Yao; Xiu-ting Li; Changhong Guo (Plant Cell Reports, 2020)

Nakamurella albus sp. nov.: A Novel Actinobacterium Isolated from a Lichen Sample - Long-Qian Jiang; De-Feng An; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Lei Lang; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Experimental investigation for dynamic instability of coal-rock masses in horizontal section mining of steeply inclined coal seams - Zheng-yi Wang; Lin-ming Dou; Jiang He; An-ye Cao; Xiong-wei Li; Peng-bo Li; Chang-sheng Wu (Arabian Journal of Geosciences, 2020)

Selenium accumulation characteristics of Cyphomandra betacea (Solanum betaceum) seedlings - Linjin Lin; Jing Sun; Tonghao Cui; Xiong Zhou; Ming’an Liao; Yunmin Huan; Liu Yang; Caifang Wu; Xianmin Xia; Yuxi Wang; Zhiyu Li; Jinpeng Zhu; et al. (Physiology and Molecular Biology of Plants, 2020)

Miscanthus cultivation shapes rhizosphere microbial community structure and function as assessed by Illumina MiSeq sequencing combined with PICRUSt and FUNGUIld analyses - Yan Chen; Wei Tian; Yang Shao; Ying-Jun Li; Li-An Lin; Ying-Jun Zhang; Hui Han; Zhao-Jin Chen (Archives of Microbiology, 2020)

Description of Gemmobacter aestuarii sp. nov., isolated from estuarine surface water and reclassification of Cereibacter changlensis as Gemmobacter changlensis Chen et al. 2013 - Asif Hameed; Mariyam Shahina; Shih-Yao Lin; Wen-Ming Chen; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Archives of Microbiology, 2020)

Outflow sediment concentration forecasting by integrating machine learning approaches and time series analysis in reservoir desilting operation - Ming-Jui Chang; Gwo-Fong Lin; Fong-Zuo Lee; Yi-Cheng Wang; Peng-An Chen; Ming-Chang Wu; Jihn-Sung Lai (Stochastic Environmental Research and Risk Assessment, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Induction of defensive proteins in Solanaceae by salivary glucose oxidase of Helicoverpa zea caterpillars and consequences for larval performance - Po-An Lin; Michelle Peiffer; Gary W. Felton (Arthropod-Plant Interactions, 2020)

Potentials and opportunities towards the low carbon technologies – From literature review to new classification - Julie Metta; Yao An; Huanhuan Zheng; Lin Zhang (Critical Reviews in Environmental Science and Technology, 2020)

A novel narnavirus from the plant-pathogenic fungus Magnaporthe oryzae - Yuan Lin; Jia Zhou; Xuan Zhou; Simin Shuai; Rendi Zhou; Hongliu An; Shouguo Fang; Songbai Zhang; Qingchao Deng (Archives of Virology, 2020)

Development of a real-time forecasting model for turbidity current arrival time to improve reservoir desilting operation - Ming-Jui Chang; Gwo-Fong Lin; Peng-An Chen; Fong-Zuo Lee; Jihn-Sung Lai (Hydrological Sciences Journal, 2020)

Oral cues are not enough: induction of defensive proteins in Nicotiana tabacum upon feeding by caterpillars - Po-An Lin; Gary W. Felton (Planta, 2020)

Effects of carboxymethyl chitosan on the growth and nutrient uptake in Prunus davidiana seedlings - Dandi Xu; Hongyan Li; Lijin Lin; Ming’an Liao; Qunxian Deng; Jin Wang; Xiulan Lv; Honghong Deng; Dong Liang; Hui Xia (Physiology and Molecular Biology of Plants, 2020)

Assessing dietary exposure risk to neonicotinoid residues among preschool children in regions of Taiwan - Min-Pei Ling; Huai-An Hsiao; Szu-Chieh Chen; Wei-Yu Chen; Wei-Chun Chou; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Hsing-Chieh Lin; Chi-Yun Chen; Tien-Hsuan Lu; Chung-Min Liao (Environmental Science and Pollution Research, 2020)

Effects of reciprocal hybridization on cadmium accumulation in F1 hybrids of two Solanum photeinocarpum ecotypes - Lijin Lin; Caifang Wu; Jin Wang; Ming’an Liao; Daiyu Yang; Honghong Deng; Xiulan Lv; Hui Xia; Dong Liang; Qunxian Deng (Environmental Science and Pollution Research, 2020)

Non-motor Symptoms in Parkinson’s Disease Patients with Parkin Mutations: More Depression and Less Executive Dysfunction - Jie Song; Bo Shen; Yu-Jie Yang; Feng-tao Liu; Jue Zhao; Yi-Lin Tang; Chen Chen; Zheng-Tong Ding; Yu An; Jian-Jun Wu; Yi-Min Sun; Jian Wang (Journal of Molecular Neuroscience, 2020)

Morphological characteristics and genetic diversity of Colletotrichum horii infecting persimmon tree in China - Quan-en Deng; Xiang-yang Ding; Jian-an Li; Lin-kai Cui; Jian-qiang Xu (European Journal of Plant Pathology, 2020)

Aureimonas leprariae sp. nov., Isolated from a Lepraria sp. Lichen - Kun Zhang; Long-Qian Jiang; Li-Song Wang; De-Feng An; Lei Lang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

In situ tests on improvement of collapsible loess with large thickness by down-hole dynamic compaction pile - Yu-chuan Zhang; Yong-guo Yao; An-gang Ma; Chen-lin Liu (European Journal of Environmental and Civil Engineering, 2020)

Characterization and fine mapping of qkrnw4, a major QTL controlling kernel row number in maize - Ningning Nie; Xiaoyu Ding; Lin Chen; Xun Wu; Yixin An; Chunhui Li; Yanchun Song; Dengfeng Zhang; Zhizhai Liu; Tianyu Wang; Yu Li; Yong-xiang Li; et al. (Theoretical and Applied Genetics, 2019)

Microfluidic tools for lipid production and modification: a review - Jin-Zheng Wang; Lin-Lin Zhu; Fan Zhang; Richard Ansah Herman; Wen-Jing Li; Xue-Jiao Zhou; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2019)

Experimental study on the physical modeling of loess tunnel-erosion rate - Li Wang; Xi-An Li; Lin-Cui Li; Bo Hong; Jia Liu (Bulletin of Engineering Geology and the Environment, 2019)

Rubellimicrobium rubrum sp. nov., a novel bright reddish bacterium isolated from a lichen sample - Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; De-Feng An; Lei Lang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Effects of mutual grafting on cadmium accumulation characteristics of first post-generations of Bidens pilosa L. and Galinsoga parviflora Cav. - Hongyan Li; Jin Wang; Lijin Lin; Ming’an Liao; Xiulan Lv; Yi Tang; Xun Wang; Hui Xia; Dong Liang; Wei Ren; Wei Jiang (Environmental Science and Pollution Research, 2019)

Seasonal precipitation change in the Western North Pacific and East Asia under global warming in two high-resolution AGCMs - Chao-An Chen; Huang-Hsiung Hsu; Chi-Cherng Hong; Ping-Gin Chiu; Chia-Ying Tu; Shian-Jiann Lin; Akio Kitoh (Climate Dynamics, 2019)

A Novel Event Detection Model for Water Distribution Systems Based on Data-Driven Estimation and Support Vector Machine Classification - Xiang-Yun Zou; Yi-Li Lin; Bin Xu; Zi-Bo Guo; Sheng-Ji Xia; Tian-Yang Zhang; An-Qi Wang; Nai-Yun Gao (Water Resources Management, 2019)

Effects of self-rooted grafting on growth and cadmium accumulation in post-grafting generations of soybean (Glycine max) - Jin Wang; Huan Yao; Lijin Lin; Yi Tang; Dong Liang; Hui Xia; Xiulan Lv; Ming’an Liao; Guochao Sun; Huanxiu Li; Xun Wang; Wei Ren (Environmental Monitoring and Assessment, 2019)

Experimental study on the disintegration of loess in the Loess Plateau of China - Xi-An Li; Li Wang; Yong-li Yan; Bo Hong; Lin-Cui Li (Bulletin of Engineering Geology and the Environment, 2019)

Using two contrasting methods with the same tracers to trace the main sediment source in a mountainous catchment - Han Wu; Dong-hong Xiong; Su Zhang; Yong Yuan; Wan-Xin Li; Lin Liu; Zheng-an Su; Xiao-ning Lu (Journal of Mountain Science, 2019)

Self-rooted grafting influences the growth and cadmium accumulation characteristics in the post generation of Cosmos sulphureus - Jin Wang; Yumei Tan; Ming’an Liao; Lijin Lin; Yi Tang; Huifen Zhang; Hui Xia; Dong Liang; Qunxian Deng; Xiulan Lv; Cheng Chen; Wei Ren (Environmental Science and Pollution Research, 2019)

First report of Dickeya fangzhongdai causing soft rot disease of Welsh onion in Taiwan - Wei-An Tsai; Pei-Rong Lin; Chien-Jui Huang (Journal of Plant Pathology, 2019)

Effects of intercropping with floricultural accumulator plants on cadmium accumulation in grapevine - Hongqiang Chen; Lijin Lin; Ming’an Liao; Jin Wang; Yi Tang; Guochao Sun; Dong Liang; Hui Xia; Qunxian Deng; Xun Wang; Xiulan Lv; Wei Ren (Environmental Science and Pollution Research, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

Induced Plant Defenses Against Herbivory in Cultivated and Wild Tomato - Sulav Paudel; Po-An Lin; Majid R. Foolad; Jared G. Ali; Edwin G. Rajotte; Gary W. Felton (Journal of Chemical Ecology, 2019)

Phytochrome-interacting factor-like protein OsPIL15 integrates light and gravitropism to regulate tiller angle in rice - Chuanmiao Xie; Ge Zhang; Lin An; Xiaoying Chen; Rongxiang Fang (Planta, 2019)

Loss of soil microbial diversity exacerbates spread of antibiotic resistance - Qing-Lin Chen; Xin-Li An; Bang-Xiao Zheng; Michael Gillings; Josep Peñuelas; Li Cui; Jian-Qiang Su; Yong-Guan Zhu (Soil Ecology Letters, 2019)

Cutting after grafting affects the growth and cadmium accumulation of Nasturtium officinale - Xingyu Zhang; Fenqin Zhang; Jin Wang; Lijin Lin; Ming’an Liao; Yi Tang; Guochao Sun; Xun Wang; Xiulan Lv; Qunxian Deng; Cheng Chen; Wei Ren (Environmental Science and Pollution Research, 2019)

Phytoremediation potential of Pterocypsela laciniata as a cadmium hyperaccumulator - Lisha Zhong; Lijin Lin; Ming’an Liao; Jin Wang; Yi Tang; Guochao Sun; Dong Liang; Hui Xia; Xun Wang; Huifen Zhang; Wei Ren (Environmental Science and Pollution Research, 2019)

Synthesis and anticancer activity evaluation of novel oxacalix[2]arene[2]pyrimidine derivatives - Tonghui Huang; Xin Wu; Tianya Liu; Lin An; Xiaoxing Yin (Medicinal Chemistry Research, 2019)

3D stability of partially saturated soil slopes after rapid drawdown by a new layer-wise summation method - Long Wang; De’an Sun; Lin Li (Landslides, 2019)

Does Regional Development Influence Sedimentary Blue Carbon Stocks? A Case Study From Three Australian Estuaries - Stephen Conrad; Dylan R. Brown; Paula Gomez Alvarez; Bronte Bates; Nizam Ibrahim; Alex Reid; Luciana Silva Monteiro; Daniela A. Silva; Lea T. Mamo; Jacob R. Bowtell; Huang An Lin; Nathaniel L. Tolentino; et al. (Frontiers in Marine Science, 2019)

RETRACTED ARTICLE: Tetraspanin 1 inhibits TNFα-induced apoptosis via NF-κB signaling pathway in alveolar epithelial cells - Lawei Yang; Yahong Wang; Zhanchun Pan; Shenglan Gao; Bao’an Zou; Ziying Lin; Dehui Feng; Changmei HuangFu; Gang Liu (Inflammation Research, 2018)

Cadmium-accumulator straw application alleviates cadmium stress of lettuce (Lactuca sativa) by promoting photosynthetic activity and antioxidative enzyme activities - Yi Tang; Yongdong Xie; Guochao Sun; Huaqiang Tan; Lijin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Xiulan Lv; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2018)

Combined ultrasound with Fenton treatment for the degradation of carcinogenic polycyclic aromatic hydrocarbons in textile dying sludge - Jian-Hao Zhang; Hai-Yuan Zou; Xun-An Ning; Mei-Qing Lin; Chang-Min Chen; Tai-Cheng An; Jian Sun (Environmental Geochemistry and Health, 2018)

Elatostema brachyodontum subsp. lengshuiheensis (Urticaceae), a new subspecies from Guizhou, China - Yun Lin; Ming-Tai An; Zhi-Rong Yang; Yan-Qiang Dai; Deng-Li Yu (Kew Bulletin, 2018)

Effects of dietary supplementation with algal astaxanthin on growth, pigmentation, and antioxidant capacity of the blood parrot ( Cichlasoma citrinellum × Cichlasoma synspilum ) - Feng Li; Shuiying Huang; Xiaoxia Lu; Jun Wang; Mingwei Lin; Yu An; Shaoting Wu; Minggang Cai (Journal of Oceanology and Limnology, 2018)

Clinical and microbiological characteristics of peritoneal dialysis-related peritonitis caused by Escherichia coli in southern Taiwan - Wei-Hung Lin; Chin-Chung Tseng; An-Bang Wu; Yu-Tzu Chang; Te-Hui Kuo; Jo-Yen Chao; Ming-Cheng Wang; Jiunn-Jong Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Subassemblage tests and design of steel channels assembled buckling-restrained braces - Yan-Lin Guo; Jing-Zhong Tong; Xiao-An Wang; Peng Zhou (Bulletin of Earthquake Engineering, 2018)

The regulation of skeletal muscle fiber-type composition by betaine is associated with NFATc1/MyoD - Jingjing Du; Linyuan Shen; Peiwen Zhang; Zhendong Tan; Xiao Cheng; Jia Luo; Xue Zhao; Qiong Yang; Hao Gu; An’an Jiang; Jideng Ma; Qianzi Tang; et al. (Journal of Molecular Medicine, 2018)

A Novel Fluorescent Nanoparticle for Sensitive Detection of Cry1Ab Protein In Vitro and In Vivo - Xiao Xu; Hao Chen; Yuancheng Cao; Yongjun Lin; Jun’an Liu (Journal of Fluorescence, 2018)

The dynamic observation of dissolved organic matter in the Zhujiang (Pearl River) Estuary in China from space - Dong Liu; Yan Bai; Xianqiang He; Delu Pan; Difeng Wang; Ji’an Wei; Lin Zhang (Acta Oceanologica Sinica, 2018)

24-Epibrassinolide-induced alterations in the root cell walls of Cucumis sativus L. under Ca(NO3)2 stress - Ya-Hong An; Heng Zhou; Ying-Hui Yuan; Lin Li; Jin Sun; Sheng Shu; Shi-Rong Guo (Protoplasma, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Effects of indole-3-butytric acid on lead and zinc accumulations in Pseudostellaria maximowicziana - Zhi Ran; Cheng Chen; Fabo Chen; Ming’an Liao; Lijin Lin; Xiulan Lv; Qunxian Deng; Xun Wang; Jin Wang; Yi Tang; Huaxiong Li (Environmental Monitoring and Assessment, 2018)

Variations in the northern permafrost boundary over the last four decades in the Xidatan region, Qinghai–Tibet Plateau - Jing Luo; Fu-jun Niu; Zhan-ju Lin; Ming-hao Liu; Guo-an Yin (Journal of Mountain Science, 2018)

Discovery of potent and selective acetylcholinesterase (AChE) inhibitors: acacetin 7- O -methyl ether Mannich base derivatives synthesised from easy access natural product naringin - Hao-ran Liu; Xue Men; Xiao-hui Gao; Lin-bo Liu; Hao-qun Fan; Xin-hua Xia; Qiu-an Wang (Natural Product Research, 2018)

Effects of melatonin on the growth and cadmium characteristics of Cyphomandra betacea seedlings - Lijin Lin; Jianhua Li; Fabo Chen; Ming’an Liao; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai; Xun Wang; Cheng Chen; Wei Ren (Environmental Monitoring and Assessment, 2018)

Levels of PCDD/Fs, PBDEs, and PBDD/Fs in Breast Milk from Southern Taiwan - Men-Wen Chen; Bryan Angelo A. Castillo; Din-Yan Lin; How-Ran Chao; Lemmuel L. Tayo; Yan-You Gou; Fu-An Chen; Kuo-Lin Huang (Bulletin of Environmental Contamination and Toxicology, 2018)

Evidence that NF-κB and MAPK Signaling Promotes NLRP Inflammasome Activation in Neurons Following Ischemic Stroke - David Yang-Wei Fann; Yun-An Lim; Yi-Lin Cheng; Ker-Zhing Lok; Prasad Chunduri; Sang-Ha Baik; Grant R. Drummond; S. Thameem Dheen; Christopher G. Sobey; Dong-Gyu Jo; Christopher Li-Hsian Chen; Thiruma V. Arumugam (Molecular Neurobiology, 2018)

Tempo-spatial variations of sediment-associated nutrients and contaminants in the Ruxi tributary of the Three Gorges Reservoir, China - Zhong-lin Shi; Yong-yan Wang; An-bang Wen; Dong-chun Yan; Jia-cun Chen (Journal of Mountain Science, 2018)

Climatology of cloud-base height from long-term radiosonde measurements in China - Yong Zhang; Lejian Zhang; Jianping Guo; Jinming Feng; Lijuan Cao; Yang Wang; Qing Zhou; Liangxu Li; Bai Li; Hui Xu; Lin Liu; Ning An; et al. (Advances in Atmospheric Sciences, 2018)

A quantitative method for risk assessment of agriculture due to climate change - Zhiqiang Dong; Zhihua Pan; Pingli An; Jingting Zhang; Jun Zhang; Yuying Pan; Lei Huang; Hui Zhao; Guolin Han; Dong Wu; Jialin Wang; Dongliang Fan; et al. (Theoretical and Applied Climatology, 2018)

Effects of mutual intercropping on the cadmium accumulation in accumulator plants Stellaria media, Malachium aquaticum, and Galium aparine - Qiyu Lu; Jianhua Li; Fabo Chen; Ming’an Liao; Lijin Lin; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai; Xun Wang; Cheng Chen; Wei Ren (Environmental Monitoring and Assessment, 2017)

Influences of meteorological conditions on interannual variations of particulate matter pollution during winter in the Beijing–Tianjin–Hebei area - Jianjun He; Sunling Gong; Hongli Liu; Xingqin An; Ye Yu; Suping Zhao; Lin Wu; Congbo Song; Chunhong Zhou; Jie Wang; Chengmei Yin; Lijuan Yu (Journal of Meteorological Research, 2017)

Major transgression during Late Cretaceous constrained by basin sediments in northern Africa: implication for global rise in sea level - Kaixuan An; Hanlin Chen; Xiubin Lin; Fang Wang; Shufeng Yang; Zhixin Wen; Zhaoming Wang; Guangya Zhang; Xiaoguang Tong (Frontiers of Earth Science, 2017)

Numerical investigation of the evolution of overlying strata and distribution of static and dynamic loads in a deep island coal panel - Guang-an Zhu; Lin-ming Dou; Chang-bin Wang; Jing Li; Wu Cai; Zi-wei Ding (Arabian Journal of Geosciences, 2017)

Quaternary Ammonium Polyamidoamine Dendrimer Modified Quantum Dots as Fluorescent Probes for p-Fluorophenoxyacetic Acid Detection in Aqueous Solution - Xiao Xu; Yuan-Cheng Cao; Jun’An Liu; Yongjun Lin (Journal of Fluorescence, 2017)

Effects of live Myriophyllum aquaticum and its straw on cadmium accumulation in Nasturtium officinale - Kewen Huang; Lijin Lin; Fabo Chen; Ming’an Liao; Jin Wang; Yi Tang; Yunsong Lai; Dong Liang; Hui Xia; Xun Wang; Wei Ren (Environmental Science and Pollution Research, 2017)

Soil organic phosphorus transformation during ecosystem development: A review - Lai-Ming Huang; Xiao-Xu Jia; Gan-Lin Zhang; Min-An Shao (Plant and Soil, 2017)

Hyperaccumulator straw improves the cadmium phytoextraction efficiency of emergent plant Nasturtium officinale - Keqiang Li; Lijin Lin; Jin Wang; Hui Xia; Dong Liang; Xun Wang; Ming’an Liao; Li Wang; Li Liu; Cheng Chen; Yi Tang (Environmental Monitoring and Assessment, 2017)

Violent transient sloshing-wave interaction with a baffle in a three-dimensional numerical tank - Mi-An Xue; Jinhai Zheng; Pengzhi Lin; Zhong Xiao (Journal of Ocean University of China, 2017)

First complete genome sequence of a virulent bacteriophage infecting the opportunistic pathogen Serratia rubidaea - Shaozhen Xing; Taping Ma; Xianglilan Zhang; Yong Huang; Zhiqiang Mi; Qiang Sun; Xiaoping An; Hang Fan; Shuhui Wu; Lin Wei; Yigang Tong (Archives of Virology, 2017)

Punicalagin protects bovine endometrial epithelial cells against lipopolysaccharide-induced inflammatory injury - An Lyu; Jia-jia Chen; Hui-chuan Wang; Xiao-hong Yu; Zhi-cong Zhang; Ping Gong; Lin-shu Jiang; Feng-hua Liu (Journal of Zhejiang University-SCIENCE B, 2017)

HCV core inhibits hepatocellular carcinoma cell replicative senescence through downregulating microRNA-138 expression - Tzu-Yue Shiu; Yu-Lueng Shih; An-Chieh Feng; Hsuan-Hwai Lin; Shih-Ming Huang; Tien-Yu Huang; Chung-Bao Hsieh; Wei-Kuo Chang; Tsai-Yuan Hsieh (Journal of Molecular Medicine, 2017)

Addition of straw from hyperaccumulator plants to cadmium-contaminated soil increases cadmium uptake by loquat seedlings - Lijin Lin; Ming’an Liao; Xiulan Lv; Dong Liang; Hui Xia; Jin Wang; Xun Wang (Environmental Monitoring and Assessment, 2017)

Influence of ameliorating soil acidity with dolomite on the priming of soil C content and CO2 emission - Muhammad Shaaban; Lei Wu; Qi-an Peng; Lukas van Zwieten; Muhammad Afzal Chhajro; Yupeng Wu; Shan Lin; Muhammad Mahmood Ahmed; Muhammad Salman Khalid; Muhammad Abid; Ronggui Hu (Environmental Science and Pollution Research, 2017)

Effects of sand burial on the survival and growth of two shrubs dominant in different habitats of northern China - Hao Qu; Ha-Lin Zhao; Xue-Yong Zhao; Xiao-An Zuo; Shao-Kun Wang; Min Chen (Environmental Monitoring and Assessment, 2017)

Rock burst assessment in multi-seam mining: a case study - Wei Shen; Lin-ming Dou; Hu He; Guang-an Zhu (Arabian Journal of Geosciences, 2017)

Development of a fluorescence resonance energy transfer–based intracellular assay to identify novel enterovirus 71 antivirals - Wen-Wen Lu; Fang-Yen Kung; Po-An Deng; Yu-Chu Lin; Cheng-Wen Lin; Szu-Hao Kung (Archives of Virology, 2017)

Contrasting ecosystem CO 2 fluxes of inland and coastal wetlands: a meta‐analysis of eddy covariance data - Weizhi Lu; Jingfeng Xiao; Fang Liu; Yue Zhang; Chang'an Liu; Guanghui Lin (Global Change Biology, 2017)
Wetlands play an important role in regulating the atmospheric carbon dioxide ( CO 2 ) concentrations and thus affecting the climate. However, there is still lack of quantitative evaluation of such a role across different wetland types, especially at the global scale. Here, we conducted a meta‐analysis to compare ecosystem CO 2 fluxes among various types of wetlands using a global database compiled from the literature. This database consists of 143 site‐years of eddy covariance data from 22 inland wetland and 21 coastal wetland sites across the globe. Coastal wetlands had higher annual gross primary productivity ( GPP ), ecosystem respiration ( R e ), and net ecosystem productivity ( NEP ) than inland wetlands. On a per unit area basis, coastal wetlands provided large CO 2 sinks, while inland wetlands provided small CO 2 sinks or were nearly CO 2 neutral. The annual CO 2 sink strength was 93.15 and 208.37 g C m −2 for inland and coastal wetlands, respectively. Annual CO 2 fluxes were mainly regulated by mean annual temperature ( MAT ) and mean annual precipitation ( MAP ). For coastal and inland wetlands combined, MAT and MAP explained 71%, 54%, and 57% of the variations in GPP , R e , and NEP , respectively. The CO 2 fluxes of wetlands were also related to leaf area index ( LAI ). The CO 2 fluxes also varied with water table depth ( WTD ), although the effects of WTD were not statistically significant. NEP was jointly determined by GPP and R e for both inland and coastal wetlands. However, the NEP / R e and NEP / GPP ratios exhibited little variability for inland wetlands and decreased for coastal wetlands with increasing latitude. The contrasting of CO 2 fluxes between inland and coastal wetlands globally can improve our understanding of the roles of wetlands in the global C cycle. Our results also have implications for informing wetland management and climate change policymaking, for example, the efforts being made by international organizations and enterprises to restore coastal wetlands for enhancing blue carbon sinks.

A mechanism of low molecular weight fucoidans degraded by enzymatic and acidic hydrolysis for the prevention of UVB damage - Pai-An Hwang; Ming-De Yan; Ko-Liang Kuo; Nam Nhut Phan; Yen-Chang Lin (Journal of Applied Phycology, 2017)

Spatial distribution, sources and ecological risk assessment of heavy metals in Shenjia River watershed of the Three Gorges Reservoir Area - Yong-yan Wang; An-bang Wen; Jin Guo; Zhong-lin Shi; Dong-chun Yan (Journal of Mountain Science, 2017)

Novel interaction between CCR4 and CAF1 in rice CCR4–NOT deadenylase complex - Wei-Lun Chou; Yue-Lin Chung; Jhen-Cheng Fang; Chung-An Lu (Plant Molecular Biology, 2017)

Design of size-tunable molecularly imprinted polymer for selective adsorption of acetaminophen - Shih-hui Lee; Ong Hui Lin; Ruey-an Doong (Clean Technologies and Environmental Policy, 2017)

Case Study of Passive Seismic Velocity Tomography in Rock Burst Hazard Assessment During Underground Coal Entry Excavation - Guang-an Zhu; Lin-ming Dou; Wu Cai; Zhen-lei Li; Min Zhang; Yong Kong; Wei Shen (Rock Mechanics and Rock Engineering, 2016)

Isolation and Analysis of Salt Response of Lactobacillus plantarum FS5-5 from Dajiang - Xuefei Song; Qianqian Wang; Xin Xu; Jingwei Lin; Xiaorui Wang; Yating Xue; Rina Wu; Yingfeng An (Indian Journal of Microbiology, 2016)

Soil properties and species composition under different grazing intensity in an alpine meadow on the eastern Tibetan Plateau, China - Zhen’an Yang; Wan Xiong; Yingyi Xu; Lin Jiang; Erxiong Zhu; Wei Zhan; Yixin He; Dan Zhu; Qiuan Zhu; Changhui Peng; Huai Chen (Environmental Monitoring and Assessment, 2016)

Microseismic Precursory Characteristics of Rock Burst Hazard in Mining Areas Near a Large Residual Coal Pillar: A Case Study from Xuzhuang Coal Mine, Xuzhou, China - An-ye Cao; Lin-ming Dou; Chang-bin Wang; Xiao-xiao Yao; Jing-yuan Dong; Yu Gu (Rock Mechanics and Rock Engineering, 2016)

The modulation of Th2 immune pathway in the immunosuppressive effect of human umbilical cord mesenchymal stem cells in a murine asthmatic model - Chin-Kan Chan; Ting-Chun Lin; Yung-An Huang; Ya-Shan Chen; Chia-Ling Wu; Huei-Yu Lo; Ming-Ling Kuo; Kang-Hsi Wu; Jing-Long Huang (Inflammation Research, 2016)

Cadmium accumulation characteristics of F1 hybrids by reciprocal hybridizing of Solanum nigrum in two climate–ecology regions - Lijin Lin; Jing He; Xun Wang; Jin Wang; Xiulan Lv; Ming’an Liao; Zhihui Wang; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai (Environmental Science and Pollution Research, 2016)

A study of sea level variability and its long-term trend in the South China Sea - Ying Xu; Mingsen Lin; Quan’an Zheng; Qingtao Song; Xiaomin Ye (Acta Oceanologica Sinica, 2016)

Piperine potentiates the effects of trans-resveratrol on stress-induced depressive-like behavior: involvement of monoaminergic system and cAMP-dependent pathway - Ying Xu; Chong Zhang; Feiyan Wu; Xiaoxiao Xu; Gang Wang; Mengmeng Lin; Yingcong Yu; Yiran An; Jianchun Pan (Metabolic Brain Disease, 2016)

Performance comparison of permafrost models in Wudaoliang Basin, Qinghai-Tibet Plateau, China - Guo-an Yin; Fu-jun Niu; Zhan-ju Lin; Jing Luo; Ming-hao Liu (Journal of Mountain Science, 2016)

Magnolol pretreatment attenuates heat stress-induced IEC-6 cell injury - Chen Mei; Sha-sha He; Peng Yin; Lei Xu; Ya-ran Shi; Xiao-hong Yu; An Lyu; Feng-hua Liu; Lin-shu Jiang (Journal of Zhejiang University-SCIENCE B, 2016)

Expression Profiling of Several Gene Families Involved in Anthocyanin Biosynthesis in Apple (Malus domestica Borkh.) Skin During Fruit Development - Rui Meng; Juan Zhang; Lin An; Bohu Zhang; Xiaobing Jiang; Yazhou Yang; Zhengyang Zhao (Journal of Plant Growth Regulation, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Mining-induced stress changes and rock burst control in a variable-thickness coal seam - Guang-an Zhu; Lin-ming Dou; Zhen-lei Li; Wu Cai; Yong Kong; Jing Li (Arabian Journal of Geosciences, 2016)

Effects of dicyandiamide and dolomite application on N2O emission from an acidic soil - Muhammad Shaaban; Yupeng Wu; Qi-an Peng; Shan Lin; Yongliang Mo; Lei Wu; Ronggui Hu; Wei Zhou (Environmental Science and Pollution Research, 2016)

High Sensitivity Bacillus thuringiensis Cry1Ac Protein Detections Using Fluorescein Diacetate Nanoparticles - Cui Liu; Zhen Zhou; Linling Zou; Yuan-Cheng Cao; Jun’An Liu; Yongjun Lin (Journal of Fluorescence, 2016)

The effects of abscisic acid (ABA) addition on cadmium accumulation of two ecotypes of Solanum photeinocarpum - Jin Wang; Lijin Lin; Li Luo; Ming’an Liao; Xiulan Lv; Zhihui Wang; Dong Liang; Hui Xia; Xun Wang; Yunsong Lai; Yi Tang (Environmental Monitoring and Assessment, 2016)

miR156 modulates rhizosphere acidification in response to phosphate limitation in Arabidopsis - Kai Jian Lei; Ya Ming Lin; Guo Yong An (Journal of Plant Research, 2016)

Effects of grafting on the cadmium accumulation characteristics of the potential Cd-hyperaccumulator Solanum photeinocarpum - Lijin Lin; Daiyu Yang; Xun Wang; Ming’an Liao; Zhihui Wang; Xiulan Lv; Fuyi Tang; Dong Liang; Hui Xia; Yunsong Lai; Yi Tang (Environmental Monitoring and Assessment, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

A set of GFP-based organelle marker lines combined with DsRed-based gateway vectors for subcellular localization study in rice (Oryza sativa L.) - Tsung-Meng Wu; Ke-Chun Lin; Wei-Shiang Liau; Yun-Yang Chao; Ling-Hung Yang; Szu-Yun Chen; Chung-An Lu; Chwan-Yang Hong (Plant Molecular Biology, 2016)

Wide-area ionospheric delay model for GNSS users in middle- and low-magnetic-latitude regions - An-Lin Tao; Shau-Shiun Jan (GPS Solutions, 2016)

Dolomite application to acidic soils: a promising option for mitigating N2O emissions - Muhammad Shaaban; Qi-an Peng; Ronggui Hu; Yupeng Wu; Shan Lin; Jinsong Zhao (Environmental Science and Pollution Research, 2015)

Differences in ozone photochemical characteristics between the megacity Nanjing and its suburban surroundings, Yangtze River Delta, China - Junlin An; Jianan Zou; Junxiu Wang; Xu Lin; Bin Zhu (Environmental Science and Pollution Research, 2015)

Evaluation of Immunosuppressive Activity of Demethylzeylasteral in a Beagle Dog Kidney Transplantation Model - Huimin An; Yu Zhu; Wenping Xu; Yujun Liu; Jianping Zhang; Zongming Lin (Cell Biochemistry and Biophysics, 2015)

Parenting stress and affective symptoms in parents of autistic children - Yun Gong; YaSong Du; HuiLin Li; XiYan Zhang; Yu An; Bai-Lin Wu (Science China Life Sciences, 2015)

Associations between TRPV4 genotypes and body mass index in Taiwanese subjects - De-Min Duan; Semon Wu; Lung-An Hsu; Ming-Sheng Teng; Jeng-Feng Lin; Yu-Chen Sun; Ching-Feng Cheng; Yu-Lin Ko (Molecular Genetics and Genomics, 2015)

Molecular phylogenetic lineage of Plagiopogon and Askenasia (Protozoa, Ciliophora) revealed by their gene sequences - An Liu; Zhenzhen Yi; Xiaofeng Lin; Xiaozhong Hu; Saleh A. Al-Farraj; Khaled A. S. Al-Rasheid (Journal of Ocean University of China, 2015)

Research on Chinese public finance in response to domestic natural disasters - Yong-ling Zhang; Yan-nan Ma; An Chen; Yu-han Lin (Natural Hazards, 2015)

Expression profiling of NBS-encoding genes in a triploid white poplar - Qian Zhang; Shanzhi Lin; Huiquan Zheng; Yuanzhen Lin; Xinmin An; Zhiyi Zhang (Journal of Plant Biochemistry and Biotechnology, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

A Systematic Study of Topography Effect of ERT Based on 3-D Modeling and Inversion - De-Bao Lu; Qi-You Zhou; S. A. Junejo; An-Lin Xiao (Pure and Applied Geophysics, 2015)

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia - Shuangmei Liu; Qingming Shi; Qicheng Zhu; Ting Zou; Guilin Li; An Huang; Bing Wu; Lichao Peng; Miaomiao Song; Qin Wu; Qiuyu Xie; Weijian Lin; et al. (Purinergic Signalling, 2015)

Lysobacter lycopersici sp. nov., isolated from tomato plant Solanum lycopersicum - Shih-Yao Lin; Asif Hameed; Cheng-Zhe Wen; You-Cheng Liu; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Dorsal hippocampal brain receptor complexes linked to the protein synthesis-dependent late phase (LTP) in the rat - Lin Li; Han Wang; Maryam Ghafari; Gunyong An; Volker Korz; Gert Lubec (Brain Structure and Function, 2015)

Oricola cellulosilytica gen. nov., sp. nov., a cellulose-degrading bacterium of the family Phyllobacteriaceae isolated from surface seashore water, and emended descriptions of Mesorhizobium loti and Phyllobacterium myrsinacearum - Asif Hameed; Mariyam Shahina; Wei-An Lai; Shih-Yao Lin; Li-Sen Young; You-Cheng Liu; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Resource availability differentially drives community assemblages of plants and their root-associated arbuscular mycorrhizal fungi - Yongjun Liu; Lin Mao; Junyong Li; Guoxi Shi; Shengjing Jiang; Xiaojun Ma; Lizhe An; Guozhen Du; Huyuan Feng (Plant and Soil, 2015)

Youngia erythrocarpa, a newly discovered cadmium hyperaccumulator plant - Lijin Lin; Bo Ning; Ming’an Liao; Yajun Ren; Zhihui Wang; Yingjie Liu; Ji Cheng; Li Luo (Environmental Monitoring and Assessment, 2015)

Effects of the joint exposure of decabromodiphenyl ether and tetrabromobisphenol A on soil bacterial community structure - Wei Zhang; Lei Chen; Shuai An; Kou Liu; Kuangfei Lin; Rongbing Fu (Environmental Science and Pollution Research, 2015)

Spatial distribution characteristics of surface tidal currents in the southwest of Taiwan Strait - Zhiben Shen; Xiongbin Wu; Hang Lin; Xiaofeng Chen; Xing’an Xu; Lun Li (Journal of Ocean University of China, 2014)

Description of Algoriphagus taiwanensis sp. nov., a xylanolytic bacterium isolated from surface seawater, and emended descriptions of Algoriphagus mannitolivorans, Algoriphagus olei, Algoriphagus aquatilis and Algoriphagus ratkowskyi - Mariyam Shahina; Asif Hameed; Shih-Yao Lin; Wei-An Lai; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

Impacts of uncertainty in AVOC emissions on the summer ROx budget and ozone production rate in the three most rapidly-developing economic growth regions of China - Feng Wang; Junling An; Ying Li; Yujia Tang; Jian Lin; Yu Qu; Yong Chen; Bing Zhang; Jing Zhai (Advances in Atmospheric Sciences, 2014)

Typhoon-enhanced upwelling and its influence on fishing activities in the southern East China Sea - Yi Chang; Jui-Wen Chan; Yuan-Chao Angelo Huang; Wei-Quan Lin; Ming-An Lee; Kuo-Tien Lee; Cheng-Hsin Liao; Kae-Yih Wang; Yi-Chun Kuo (International Journal of Remote Sensing, 2014)

A dual tyrosine kinase inhibitor lapatinib suppresses overexpression of matrix metallopeptidase 1 (MMP1) in endometrial cancer - Chiao-Yun Lin; Angel Chao; Tzu-Hao Wang; Swei Hsueh; Yun-Shien Lee; Tzu-I Wu; An-Shine Chao; Huei-Jean Huang; Hung-Hsueh Chou; Ting-Chang Chang; Chyong-Huey Lai (Journal of Molecular Medicine, 2014)

Mechanism-Based Pharmacokinetic Modeling to Evaluate Transporter-Enzyme Interplay in Drug Interactions and Pharmacogenetics of Glyburide - Manthena V. S. Varma; Renato J. Scialis; Jian Lin; Yi-An Bi; Charles J. Rotter; Theunis C. Goosen; Xin Yang (The AAPS Journal, 2014)

Cadmium accumulation characteristics of the winter farmland weeds Cardamine hirsuta Linn. and Gnaphalium affine D. Don - Lijin Lin; Jun Shi; Qihua Liu; Ming’an Liao; Luoyin Mei (Environmental Monitoring and Assessment, 2014)

Clinically Relevant Reperfusion in Acute Ischemic Stroke: MTT Performs Better than Tmax and TTP - Andria L. Ford; Hongyu An; Linglong Kong; Hongtu Zhu; Katie D. Vo; William J. Powers; Weili Lin; Jin-Moo Lee (Translational Stroke Research, 2014)

Description of Niveispirillum fermenti gen. nov., sp. nov., isolated from a fermentor in Taiwan, transfer of Azospirillum irakense (1989) as Niveispirillum irakense comb. nov., and reclassification of Azospirillum amazonense (1983) as Nitrospirillum amazonense gen. nov - Shih-Yao Lin; Asif Hameed; Fo-Ting Shen; You-Cheng Liu; Yi-Han Hsu; Mariyam Shahina; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

Interactive influence of light intensity and soil fertility on root-associated arbuscular mycorrhizal fungi - Guoxi Shi; Yongjun Liu; Nancy Collins Johnson; Pål Axel Olsson; Lin Mao; Gang Cheng; Shengjing Jiang; Lizhe An; Guozhen Du; Huyuan Feng (Plant and Soil, 2014)

Endophytic nitrogen-fixing Klebsiella variicola strain DX120E promotes sugarcane growth - Chun-Yan Wei; Li Lin; Li-Jing Luo; Yong-Xiu Xing; Chun-Jin Hu; Li-Tao Yang; Yang-Rui Li; Qianli An (Biology and Fertility of Soils, 2014)

Intraneuronal accumulation of Aβ42 induces age-dependent slowing of neuronal transmission in Drosophila - Jing-Ya Lin; Wen-An Wang; Xiao Zhang; Hai-Yan Liu; Xiao-Liang Zhao; Fu-De Huang (Neuroscience Bulletin, 2014)

Heterologous expression of artificial miRNAs from rice dwarf virus in transgenic rice - Runhong Sun; Peng Du; Lin Jiang; Derong An; Yi Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

More insights into early brain development through statistical analyses of eigen-structural elements of diffusion tensor imaging using multivariate adaptive regression splines - Yasheng Chen; Hongtu Zhu; Hongyu An; Diane Armao; Dinggang Shen; John H. Gilmore; Weili Lin (Brain Structure and Function, 2014)

Changes in land use and agricultural production structure before and after the implementation of grain for green program in Western China — taking two typical counties as examples - Ping Zhou; An-bang Wen; Dong-chun Yan; Zhong-lin Shi; Jin Guo; Zhan-sheng Ju; Yi-lan Zhang (Journal of Mountain Science, 2014)

The relationship between typhoons' peripheral circulation and ground-level ozone concentrations in central Taiwan - Wan-Li Cheng; Li-Wei Lai; Walter Den; Meng-Ting Wu; Chao-An Hsueh; Pay-Liam Lin; Chueh-Ling Pai; Yeou-Lih Yan (Environmental Monitoring and Assessment, 2014)

Identification of Key Licorice Constituents Which Interact with Cytochrome P450: Evaluation by LC/MS/MS Cocktail Assay and Metabolic Profiling - Xue Qiao; Shuai Ji; Si-wang Yu; Xiong-hao Lin; Hong-wei Jin; Yao-kai Duan; Liang-ren Zhang; De-an Guo; Min Ye (The AAPS Journal, 2014)

Wheat cultivars form distinctive communities of root-associated arbuscular mycorrhiza in a conventional agroecosystem - Lin Mao; Yongjun Liu; Guoxi Shi; Shengjing Jiang; Gang Cheng; Xingmao Li; Lizhe An; Huyuan Feng (Plant and Soil, 2014)

Association between the characteristics of metabolic syndrome and Alzheimer’s disease - Hui-Ting Yang; Yi-Jing Sheen; Chuen-Der Kao; Chin-An Chang; Ya-Chun Hu; Jiann-Liang Lin (Metabolic Brain Disease, 2013)

A pthA homolog from a variant of Xanthomonas axonopodis pv. citri enhances virulence without inducing canker symptom - Hsin-Cheng Lin; Yu-An Chang; Hsiang Chang (European Journal of Plant Pathology, 2013)

Analysis of synonymous codon usage patterns in the genus Rhizobium - Xinxin Wang; Liang Wu; Ping Zhou; Shengfeng Zhu; Wei An; Yu Chen; Lin Zhao (World Journal of Microbiology and Biotechnology, 2013)

Effects of sub-chronic donepezil on brain Abeta and cognition in a mouse model of Alzheimer’s disease - Amy Easton; Sethu Sankaranarayanan; An Tanghe; Dick Terwel; Alan X. Lin; Nina Hoque; Clotilde Bourin; Huidong Gu; Michael Ahlijanian; Linda Bristow (Psychopharmacology, 2013)

Partial least squares based identification of Duchenne muscular dystrophy specific genes - Hui-bo An; Hua-cheng Zheng; Li Zhang; Lin Ma; Zheng-yan Liu (Journal of Zhejiang University-SCIENCE B, 2013)

Functional identification of the gene encoding the enzyme involved in mannosylation in ramoplanin biosynthesis in Actinoplanes sp. - Jun-Sheng Chen; Yuan-Xi Wang; Lei Shao; Hai-Xue Pan; Ji-An Li; Hui-Min Lin; Xiao-Jing Dong; Dai-Jie Chen (Biotechnology Letters, 2013)

Indole-based Fluorescent Sensors for Selective Detection of Hg2+ - Yao-Lin Sun; An-Tai Wu (Journal of Fluorescence, 2013)

Cell Hypertrophy and MEK/ERK Phosphorylation are Regulated by Glyceraldehyde-Derived AGEs in Cardiomyocyte H9c2 Cells - Shun-Yao Ko; I-Hsuan Lin; Tzong-Ming Shieh; Hsin-An Ko; Hong-I Chen; Tzong-Cherng Chi; Shu-Shing Chang; Yi-Chiang Hsu (Cell Biochemistry and Biophysics, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

A study of the frequency of methylation of gene promoter regions in colorectal cancer in the Taiwanese population - CHANG-CHIEH WU; JEN-CHUN KUAN; CHIH-HSIUNG HSU; TZU-AN CHEN; CHIEN-AN SUN; TSAN YANG; SHINN-LONG LIN; YU-CHING CHOU (Journal of Genetics, 2013)

MicroRNA-210 targets antiapoptotic Bcl-2 expression and mediates hypoxia-induced apoptosis of neuroblastoma cells - Chung-Ching Chio; Jia-Wei Lin; Heien-An Cheng; Wen-Ta Chiu; Yuan-Hung Wang; Jhi-Joung Wang; Chung-Hsi Hsing; Ruei-Ming Chen (Archives of Toxicology, 2013)

Evaluation of landslide risk based on synchronization of nonlinear motions in observed data - Da-Chao Lin; Jing-Luo Cai; Zhang-Lin Guo; Fan-Lei Zeng; Feng-Ping An; Hai-Bo Liu (Natural Hazards, 2013)

β2-Glycoprotein I inhibits VEGF-induced endothelial cell growth and migration via suppressing phosphorylation of VEGFR2, ERK1/2, and Akt - Wen-Chin Chiu; Jan-Yu Lin; Tzong-Shyuan Lee; Li-Ru You; An-Na Chiang (Molecular and Cellular Biochemistry, 2013)

Development of a substrate-coupled biocatalytic process driven by an NADPH-dependent sorbose reductase from Candida albicans for the asymmetric reduction of ethyl 4-chloro-3-oxobutanoate - Ping Cai; Mingdong An; Lin Xu; Sheng Xu; Ning Hao; Yan Li; Kai Guo; Ming Yan (Biotechnology Letters, 2012)

An Improved AhR Reporter Gene Assay for Analyzing Dioxins in Soil, Sediment and Fish - How-Ran Chao; Ya-Fan Wang; Yao-Nan Wang; Ding-Yan Lin; Yan-You Gou; Chien-Yu Chen; Kuan-Chung Chen; Wen-Kai Wu; Bao-An Chiang; Yu-Ting Huang; Lien-Te Hsieh; Kuei-Jyum C. Yeh; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Photocatalytic Degradation of Reactive Black 5 by Fish Scale-Loaded TiO2 Composites - Li-Ngee Ho; Soon-An Ong; Yee Lin See (Water, Air, & Soil Pollution, 2012)

miR-15b and miR-16 regulate TNF mediated hepatocyte apoptosis via BCL2 in acute liver failure - Fangmei An; Bangdong Gong; Hui Wang; Dongshan Yu; Gangde Zhao; Lanyi Lin; Weiliang Tang; Hong Yu; Shisan Bao; Qing Xie (Apoptosis, 2012)

Defining the Ischemic Penumbra Using Hyperacute Neuroimaging: Deriving Quantitative Ischemic Thresholds - Andria L. Ford; Hongyu An; Katie D. Vo; Weili Lin; Jin-Moo Lee (Translational Stroke Research, 2012)

Noninvasive Measurements of Cerebral Blood Flow, Oxygen Extraction Fraction, and Oxygen Metabolic Index in Human with Inhalation of Air and Carbogen using Magnetic Resonance Imaging - Hongyu An; Souvik Sen; Yasheng Chen; William J. Powers; Weili Lin (Translational Stroke Research, 2012)

Cryotherapy is Associated with Improved Clinical Outcomes of Sorafenib Therapy for Advanced Hepatocellular Carcinoma - Yongping Yang; Yinying Lu; Chunping Wang; Wenlin Bai; Jianhui Qu; Yan Chen; Xiujuan Chang; Linjing An; Lin Zhou; Zhen Zeng; Min Lou; Jiyun Lv (Cell Biochemistry and Biophysics, 2012)

Determination of organophosphorus pesticide residues in vegetables by an enzyme inhibition method using α-naphthyl acetate esterase extracted from wheat flour - Jun-liang Wang; Qing Xia; An-ping Zhang; Xiao-yan Hu; Chun-mian Lin (Journal of Zhejiang University-SCIENCE B, 2012)

Characterizations of volatile organic compounds during high ozone episodes in Beijing, China - An Jun-lin; Wang Yue-si; Wu Fang-kun; Zhu Bin (Environmental Monitoring and Assessment, 2012)

Overexpression of microRNA-378 attenuates ischemia-induced apoptosis by inhibiting caspase-3 expression in cardiac myocytes - Ji Fang; Xiao-Wei Song; Jing Tian; Hu-Yan Chen; Dong-Feng Li; Jian-Fei Wang; An-Jing Ren; Wen-Jun Yuan; Li Lin (Apoptosis, 2012)

Oxygen Metabolism in Ischemic Stroke Using Magnetic Resonance Imaging - Hongyu An; Qingwei Liu; Yasheng Chen; Katie D. Vo; Andria L. Ford; Jin-Moo Lee; Weili Lin (Translational Stroke Research, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Association of SERPINE2 gene with the risk of chronic obstructive pulmonary disease and spirometric phenotypes in northern Han Chinese population - Li An; Ting Yang; Yongbiao Zhang; Yingxiang Lin; Hong Zhang; Xia Jiao; Lin Hua; Huaping Dai; Chen Wang (Molecular Biology Reports, 2012)

Soluble expression and purification of Brucella cell surface protein (BCSP31) of Brucella melitensis and preparation of anti-BCSP31 monoclonal antibodies - Lei Zhang; Xing An Wu; Fang Lin Zhang; Cui Hong An; Yang Xin Sun; Wen Tao Bai; Zhi Kai Xu (Molecular Biology Reports, 2012)

Nicotine promotes proliferation and collagen synthesis of chondrocytes isolated from normal human and osteoarthritis patients - Xiaozhou Ying; Shaowen Cheng; Yue Shen; Xiaojie Cheng; Ferdinand An Rompis; Wei Wang; Zhongqin Lin; Qingyu Chen; Wei Zhang; Dongquan Kou; Lei Peng; Xin Qiao Tian; et al. (Molecular and Cellular Biochemistry, 2012)

Analysis of promoter activity of PtDrl02 gene in white poplars - Huiquan Zheng; Yang Lei; Zhiyi Zhang; Shanzhi Lin; Qian Zhang; Wenfeng Liu; Juan Du; Xinmin An; Xiyang Zhao (Journal of Plant Biochemistry and Biotechnology, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Rapid change of AM fungal community in a rain-fed wheat field with short-term plastic film mulching practice - Yongjun Liu; Lin Mao; Xinhua He; Gang Cheng; Xiaojun Ma; Lizhe An; Huyuan Feng (Mycorrhiza, 2012)

Classification of non-vegetated areas using Formosat-2 high spatiotemporal imagery: the case of Tseng-Wen Reservoir catchment area (Taiwan) - Cheng-Chien Liu; Chjeng-Lun Shieh; Jia-Chin Lin; An-Ming Wu (International Journal of Remote Sensing, 2011)

Transformation of alfalfa chloroplasts and expression of green fluorescent protein in a forage crop - Zhengyi Wei; Yanzhi Liu; Chunjing Lin; Yunpeng Wang; Qin’an Cai; Yingshan Dong; Shaochen Xing (Biotechnology Letters, 2011)

Effect of Boron on Osteogenic Differentiation of Human Bone Marrow Stromal Cells - Xiaozhou Ying; Shaowen Cheng; Wei Wang; Zhongqin Lin; Qingyu Chen; Wei Zhang; Dongquan Kou; Yue Shen; Xiaojie Cheng; Ferdinand An Rompis; Lei Peng; Chuan zhu Lu (Biological Trace Element Research, 2011)

Effect of Low-Intensity Pulsed Ultrasound on MMP-13 and MAPKs Signaling Pathway in Rabbit Knee Osteoarthritis - Xueping Li; Jianan Li; Kai Cheng; Qiang Lin; Daxin Wang; Hongfei Zhang; Hengyuan An; Mingxia Gao; Anliang Chen (Cell Biochemistry and Biophysics, 2011)

The diversity of arbuscular mycorrhizal fungi in the subtropical forest of Huangshan (Yellow Mountain), East-Central China - An Na Yang; Lin Lu; Nan Zhang (World Journal of Microbiology and Biotechnology, 2011)

Precise mapping Fhb5, a major QTL conditioning resistance to Fusarium infection in bread wheat (Triticum aestivum L.) - Shulin Xue; Feng Xu; Mingzhi Tang; Yan Zhou; Guoqiang Li; Xia An; Feng Lin; Haibin Xu; Haiyan Jia; Lixia Zhang; Zhongxin Kong; Zhengqiang Ma (Theoretical and Applied Genetics, 2011)

Ningdong granule: a complementary and alternative therapy in the treatment of attention deficit/hyperactivity disorder - Ji-Jun Li; Zai-Wang Li; Shu-Zhen Wang; Fang-Hua Qi; Lin Zhao; Hong Lv; An-Yuan Li (Psychopharmacology, 2011)

Association between SNP rs1800875, serum chymase and immunoglobulin E levels in patients with coronary heart disease - Chun-na Jin; Hong Ma; Yan Lin; Jian-an Wang; Mei-xiang Xiang (Journal of Zhejiang University-SCIENCE B, 2011)

A nested case–control study of low birthweight among cosmetologists - Michele L. Herdt-Losavio; Shao Lin; Charlotte M. Druschel; Syni-An Hwang; Matthew P. Mauer; G. Anders Carlson (International Archives of Occupational and Environmental Health, 2011)

Levels and Congener Profiles of Particle-bound Polybrominated Dibenzo-p-dioxins/furans (PBDD/Fs) in Ambient Air around Guangzhou, China - Huiru Li; Lin Zhou; Ligui Mo; Ping’an Peng; Guoying Sheng; Jiamo Fu; Zhiqiang Yu (Bulletin of Environmental Contamination and Toxicology, 2011)

Regulation of expression of trehalose-6-phosphate synthase during cold shock in Arthrobacter strain A3 - Xi-Ming Chen; Ying Jiang; Yuan-Ting Li; Hai-Hong Zhang; Jie Li; Xing Chen; Qi Zhao; Jing Zhao; Jing Si; Zhi-Wei Lin; Hua Zhang; Paul Dyson; et al. (Extremophiles, 2011)

Novel Fluorescent Molecular Clips: Selective Recognition Towards Fe3+ in Aqueous Solution - Lin Li; Neng-fang She; Zhuan Fei; Pui-kin So; Yu-zhou Wang; Li-ping Cao; An-xin Wu; Zhong-ping Yao (Journal of Fluorescence, 2011)

Analysis of the Composition and Characteristics of Culturable Endophytic Bacteria Within Subnival Plants of the Tianshan Mountains, Northwestern China - Hong Mei Sheng; Hong Shan Gao; Lin Gui Xue; Shuo Ding; Chun Li Song; Hu Yuan Feng; Li Zhe An (Current Microbiology, 2011)

Isolation of a LEAFY homolog from Populus tomentosa: expression of PtLFY in P. tomentosa floral buds and PtLFY-IR-mediated gene silencing in tobacco (Nicotiana tabacum) - Xin-Min An; Dong-Mei Wang; Ze-Liang Wang; Bo Li; Wen-Hao Bo; Guan-Lin Cao; Zhi-Yi Zhang (Plant Cell Reports, 2011)

Determination of Ozonization Reaction Rate Constants of Aromatic Pollutants and QSAR Study - Jian Lin Jiang; Xiang An Yue; Qiu Fen Chen; Zhen Gao (Bulletin of Environmental Contamination and Toxicology, 2010)

Linking root morphology, longevity and function to root branch order: a case study in three shrubs - Gang Huang; Xue-yong Zhao; Ha-lin Zhao; Ying-xin Huang; Xiao-an Zuo (Plant and Soil, 2010)

Evaluation of surface heat fluxes in Chiayi plain of Taiwan by remotely sensed data - Tzu-Yin Chang; Yuei-An Liou; Chuan-Yao Lin; Shaw-Chen Liu; Yi-Chen Wang (International Journal of Remote Sensing, 2010)

Relation of uric acid levels to aortic root dilatation in hypertensive patients with and without metabolic syndrome - Li-jiang Tang; Jian-jun Jiang; Xiao-feng Chen; Jian-an Wang; Xian-fang Lin; Yu-xi Du; Cong-feng Fang; Zhao-xia Pu (Journal of Zhejiang University-SCIENCE B, 2010)

Fine mapping Fhb4, a major QTL conditioning resistance to Fusarium infection in bread wheat (Triticum aestivum L.) - Shulin Xue; Guoqiang Li; Haiyan Jia; Feng Xu; Feng Lin; Mingzhi Tang; Yao Wang; Xia An; Haibin Xu; Lixia Zhang; Zhongxin Kong; Zhengqiang Ma (Theoretical and Applied Genetics, 2010)

Proteomic Analysis of Interactions Between the Generalist Herbivore Spodoptera exigua (Lepidoptera: Noctuidae) and Arabidopsis thaliana - Ju-Hong Zhang; Li-Wen Sun; Lin-Lin Liu; Jie Lian; Shao-Li An; Xu Wang; Jing Zhang; Jun-Ling Jin; Shan-Yu Li; Jing-Hui Xi (Plant Molecular Biology Reporter, 2010)

Trophic coupling between Synechococcus and pigmented nanoflagellates in the coastal waters of Taiwan, western subtropical Pacific - Lin Yun-Chi; Tsai An-Yi; Chiang Kuo-Ping (Journal of Oceanography, 2009)

Production of cyclodextrin glucanotransferase from an alkalophilic Bacillus sp. by pH-stat fed-batch fermentation - Chou-Chiang Kuo; Ching-An Lin; Jing-Yi Chen; Ming-Tse Lin; Kow-Jen Duan (Biotechnology Letters, 2009)

Prognostic factors and recurrence of hepatitis B-related hepatocellular carcinoma after argon-helium cryoablation: a prospective study - Chunping Wang; Yinying Lu; Yan Chen; Yongyi Feng; Linjing An; Xinzhen Wang; Shuhui Su; Wenlin Bai; Lin Zhou; Yongping Yang; Dongping Xu (Clinical & Experimental Metastasis, 2009)

A high-performance temperature-control scheme: growth of sea cucumber Apostichopus japonicus with different modes of diel temperature fluctuation - Zhen-Hua An; Yun-Wei Dong; Shuang-Lin Dong (Aquaculture International, 2009)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

A cell strain cloned from Spodoptera exigua cell line (IOZCAS-Spex-II) highly susceptible to S. exigua nucleopolyhedrovirus infection - Huan Zhang; Yong-an Zhang; Qilian Qin; Xuan Li; Lin Miao; Yuzhu Wang; Liangjian Qu; Aijun Zhang; Qing Yang (In Vitro Cellular & Developmental Biology - Animal, 2009)

Shear-wave splitting in the southeast of Cathaysia block, South China - Yuan Gao; Jing Wu; Jin-An Cai; Yu-Tao Shi; Shu Lin; Ting Bao; Zu-Ning Li (Journal of Seismology, 2009)

5-Hydroxymethyl-2-furfural, a clinical trials agent for sickle cell anemia, and its mono/di-glucosides from classically processed steamed Rehmanniae Radix - An-Shen Lin; Keduo Qian; Yoshihide Usami; Li Lin; Hideji Itokawa; Charleson Hsu; Susan L. Morris-Natschke; Kuo-Hsiung Lee (Journal of Natural Medicines, 2008)

Spatio-temporal variation of stable isotopes of river waters, water source identification and water security in the Heishui Valley (China) during the dry-season - Yuhong Liu; Shuqing An; Zhen Xu; Ningjiang Fan; Jun Cui; Zhongsheng Wang; Shirong Liu; Jiayong Pan; Guanghui Lin (Hydrogeology Journal, 2008)

Evolutionary characterization of influenza virus A/duck/Hubei/W1/2004 (H9N2) isolated from central China - Xiao-Juan Xu; Gao-Yuan Xu; Hong-Bo Zhou; Zheng-Jun Yu; An-Ding Zhang; Yun-Feng Song; Mei-Lin Jin; Huan-Chun Chen (Virus Genes, 2008)

Development of a molecular marker for a bruchid (Callosobruchus chinensis L.) resistance gene in mungbean - Huei-Mei Chen; Chien-An Liu; C. George Kuo; Ching-Mei Chien; Horng-Chi Sun; Chung-Chu Huang; Yu-Chung Lin; Hsin-Mei Ku (Euphytica, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effects of cold eddy on phytoplankton production and assemblages in Luzon strait bordering the South China Sea - Yuh-Ling Lee Chen; Houng-Yung Chen; I. -I. Lin; Ming-An Lee; Jeng Chang (Journal of Oceanography, 2007)

Down-regulation of neuropathy target esterase by protein kinase C activation with PMA stimulation - Rui Chen; Ping-An Chang; Ding-Xin Long; Lin Yang; Yi-Jun Wu (Molecular and Cellular Biochemistry, 2007)

Genotyping of Trichophyton rubrum by analysis of ribosomal-DNA intergenic spacer regions - Guoling Yang; Lijia An; Qiao Li; Jingrong Lin; Weida Liu; Liji Jin; Xiran Lin (Mycopathologia, 2007)

Genetic structure and habitat selection of the tall form Spartina alterniflora Loisel. in China - Zifa Deng; Shuqing An; Changfang Zhou; Zhongsheng Wang; Yingbiao Zhi; Yunjing Wang; Suhua Shi; Lin Chen; Congjiao Zhao (Hydrobiologia, 2007)

Cloning and characterization of a novel albinism-related zinc finger protein gene in Japanese flounder - Jiaqing Wang; Lin Hou; Xiangyang Zou; Feng Yao; Xiaoyan Li; Xintao Zhao; Ruifeng Zhang; Lijuan Jiang; Wenjing Sun; Jialu An (Fish Physiology and Biochemistry, 2007)

Basic Characteristics of Sporolactobacillus inulinus BCRC 14647 for Potential Probiotic Properties - Hui-Ying Huang; Shih-Yi Huang; Pei-Yu Chen; V. An-Erl King; Yeu-Pyng Lin; Jen-Horng Tsen (Current Microbiology, 2007)

Cloning and identification of partial DNA fragment for the B mating-type factor in Lentinula edodes using degenerate PCR - An-Zheng Li; Xue-Feng Xu; Fan-Xue Lin; Shui-Ming Cheng; Fang-Can Lin (World Journal of Microbiology and Biotechnology, 2007)

Overexpression of proline oxidase induces proline-dependent and mitochondria-mediated apoptosis - Chien-an A. Hu; Steven P. Donald; Jian Yu; Wei-Wen Lin; Zhihe Liu; Gary Steel; Cassandra Obie; David Valle; James M. Phang (Molecular and Cellular Biochemistry, 2007)

Improving debris flow monitoring in Taiwan by using high-resolution rainfall products from QPESUMS - Chien-Yuan Chen; Lee-Yao Lin; Fan-Chieh Yu; Ching-Sheng Lee; Chun-Chieh Tseng; An-Hsiang Wang; Kei-Wai Cheung (Natural Hazards, 2007)

Summer rain pulse size and rainwater uptake by three dominant desert plants in a desertified grassland ecosystem in northwestern China - Xiaoli Cheng; Shuqing An; Bo Li; Jiquan Chen; Guanghui Lin; Yuhong Liu; Yiqi Luo; Shirong Liu (Plant Ecology, 2006)

A Study on Stability of Phenotype and Genotype of Trichophyton rubrum - Yang Guoling; Yu Xiaohong; Lin Jingrong; Jin Liji; An Lijia (Mycopathologia, 2006)

Functional polymorphisms of FGA, encoding α fibrinogen, are associated with susceptibility to venous thromboembolism in a Taiwanese population - Yu-Lin Ko; Lung-An Hsu; Tsu-Shiu Hsu; Chia-Ti Tsai; Ming-Sheng Teng; Semon Wu; Chi-Jen Chang; Ying-Shiung Lee (Human Genetics, 2006)

Characterization of Usher syndrome type I gene mutations in an Usher syndrome patient population - Xiao Mei Ouyang; Denise Yan; Li Lin Du; J. Fielding. Hejtmancik; Samuel G. Jacobson; Walter E. Nance; An Ren Li; Simon Angeli; Muriel Kaiser; Valerie Newton; Steve D. M. Brown; Thomas Balkany; et al. (Human Genetics, 2005)

An interspecific somatic hybrid between Actinidia chinensis and Actinidia kolomikta and its chilling tolerance - Zun-an Xiao; Lin-chen Wan; Bi-wen Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Tidal front and the convergence of anchovy ( Engraulis japonicus ) eggs in the Yellow Sea - Wei Hao; Su Jian; Wan Ruijing; Wang Lei; Lin Yi'an (Fisheries Oceanography, 2003)
Anchovy recruitment determines fish production and thus the sustainable exploitation of anchovy in the Yellow Sea. Haizhou Bay is a traditional spawning and nursery ground for anchovy. The retention of anchovy in its early life stages appears to be related to observed fronts. Cruises have confirmed that anchovy eggs are distributed in high density patches, particularly in the tidal frontal zone. Front and egg patches shift to the shallow area in the warm season. A diagnostic Hamburg Shelf Ocean Model was applied in the East China Sea and Yellow Sea to simulate the frontal circulation and particle movement, forced by monthly wind speed and measured temperatures. It was observed that the jet along the front and upwelling in the mixed side of the front play an important role in the transport of eggs. Convergence and divergence areas are frequently induced by frontal shear instability and topography potential vorticity balance. Numerical experiments show that tidal mixing and front play an important role to converge particles like eggs. When eggs are caught in the convergence zone they are aggregated into a patch. The convergence zone has good feeding condition for eggs to hatch and larvae to grow.

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

Genetic variations in the cholesteryl ester transfer protein gene and high density lipoprotein cholesterol levels in Taiwanese Chinese - Lung-An Hsu; Yu-Lin Ko; Kuang-Hung Hsu; Yu-Hsien Ko; Ying-Shiung Lee (Human Genetics, 2002)

Litter decomposition and nitrogen mineralization of soils in subtropical plantation forests of southern China, with special attention to comparisons between legumes and non-legumes - Zhi-an Li; Shao-lin Peng; Debbie J. Rae; Guo-yi Zhou (Plant and Soil, 2001)

Effects of shear and sharp gradients in static stability on two-dimensional flow over an isolated mountain ridge - Ting-An Wang; Yuh-Lang Lin (Meteorology and Atmospheric Physics, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)